Nitrate pollution sources and associated biogeochemical mechanisms in coastal groundwater affected by seawater intrusion using multiple isotopes and source apportionment models - Shengwei Cao; Guoli Yang; Jinlong Zhou; Junru Liu; Chunlei Liu; Jun Li; Yasong Li (Marine Pollution Bulletin, 2026)

Electrode-Triggered niche differentiation and endogenous electron cycling boost bioremediation of mixed aromatic contaminants in oligotrophic groundwater - Jun Huang; Fan Chen; Zimeng Zhang; Yunxia Zu; Di Cao; Tianyi Huang; Zhiling Li; Aijie Wang (Water Research, 2026)

Concentration effects of proanthocyanidins on protein oxidation and quality deterioration of refrigerated golden pompano (Trachinotus blochii) fillets: Insights from metabolomic analysis - Liyuan Xiao; Longteng Zhang; Xin Zhang; Dongyin Liu; Yunuo Zhou; Yongqi Tian; Lulu Zhu; Yanfu He; Jun Cao; Chuan Li (Food Research International, 2026)

Built-in electric field for synergistically regulating electronic structure and interfacial hydrogen-bond network toward ampere-level current anion exchange membrane water electrolysis - Yujie Liang; Xinyu Lao; Jiaying Zhang; Hao Feng; Rui Min; Jingjing Wang; Yingying Zheng; Jiaqi Pan; Chaorong Li; Jun Cao (Chemical Engineering Journal, 2026)

Prokaryotic Argonautes as programmable tools for foodborne biological hazards detection: mechanisms, applications, and prospects - Jing-bo Jiao; Cheng-long Zhao; Jiang-li Cao; Tong Lin; Qing Kang; Li-jun Wang; Nan Wang; Xin-jun Du; Shuo Wang (Critical Reviews in Food Science and Nutrition, 2026)

From efficient nitrite accumulation to complete collapse: how a microbial community and its antibiotic resistance genes in a nitrification system respond to long-term exposure to ciprofloxacin and copper - Xiao-Yan Fan; Meng-Hao Hao; Jun-Ru Zhao; Xing Li; Shen-Bin Cao; Jia-Wei Ren; Ding-Chang Li (Journal of Water Process Engineering, 2026)

Climate network-based synchronized structural identification of extreme drought and pluvial events in cross-basin regions - Wenyu Li; Jun Xie; Juan Cao; Kaiwen Li; Kai Liu; Ming Wang (Journal of Hydrology, 2026)

Seasonal hydrogeochemical controls on groundwater heavy metals and associated health risks at a petrochemical-contaminated site - Chen Liu; Yifei Wang; Yanyan Wang; Le Song; Zhe Wang; Jun Zhang; Wenbei Du; Shijia Xu; Yidong Wang; Li Meng; Wengeng Cao (Journal of Environmental Chemical Engineering, 2026)

Structural framework and formation mechanism of northern Western Desert, Egypt: Insights from bouguer gravity and seismic data - Min Gao; Zhe Cao; Jun Li; Zhongmin Zhang; Tong Wang; Zixuan Liu; Hong Zhang; Yongjie Hu; Walid A. Makled (Journal of African Earth Sciences, 2026)

Wheat seedling vigor classification under field conditions using low-cost ground-level RGB imagery and a lightweight attention model - Runzhi Xu; Lixin Qiu; Fei Yuan; Dashuai Wang; Kang Yu; Wei Li; Jun Lu; Xiaojun Liu; Yongchao Tian; Yan Zhu; Weixing Cao; Qiang Cao (European Journal of Agronomy, 2026)

An objective detection method for tinnitus using memristors - Hui Ma; Xiaoyan Ma; Yingying Xuan; Zelin Cao; Lin Li; Kaikai Gao; Mengna Wang; Ruifeng Qiao; Qin Hu; Wentao Yan; Kun Wang; Haoyuan Wang; et al. (Chemical Engineering Journal, 2026)

Phase diagram engineering advances the thermoelectric performance of Zintl phase EuZn2Sb2 - Baopeng Ma; Honghao Yao; Shanghao Chen; Xiaofang Li; Shiquan Lu; Wenhua Xue; Tianyu Zhang; Linmao Wen; Sichen Duan; Yunzi Ren; Yumei Wang; Feng Cao; et al. (Chemical Engineering Journal, 2026)

Interpretable causal machine learning elucidates performance regulation via atomic Fe‑S synergistic pathways in Sulfidated zero‑valent Iron - Zimin Yan; Rupeng Wang; Zhiling Li; Tianyi Huang; Yunxia Zu; Xiaoxi Zeng; Di Cao; Bin Wu; Jun Huang; Shih-Hsin Ho; Aijie Wang (Water Research, 2026)

nZVI-Ryegrass Integrated System for Risk Mitigation of Chromium-PFAS Co-contaminated Soil: Pollutant Immobilization and Microbial Niche Regulation - Jingming Li; Zhengkun Zhao; Xiaoyu Ma; Bo Chen; Wei Ma; Wenbo Guo; Jun Liang; Xiaoyun Xu; Hao Qiu; Xinde Cao; Ling Zhao (Journal of Hazardous Materials, 2026)

Dual-site ionized covalent organic frameworks with enhanced charge density for highly efficient and selective adsorption of 99TcO4-/ReO4- - Meng Li; Shiyuan Wei; Hao Wang; Jun Cao; Jiawei Li; Jianhan Huang; You-Nian Liu (Journal of Hazardous Materials, 2026)

“Lotus leaf meets nacre”: a dual biomimetic approach to creating highly humidity-stable films with exceptional barrier properties for food packaging - Ningkang Deng; Jinsong Zeng; Pengfei Li; Junzhang Wu; Jianqiao Su; Zhiqiang Gong; Yuan Peng; Ting Yao; Jinpeng Li; Daxian Cao; Bin Wang; Jun Xu; et al. (Food Chemistry, 2026)

Strong dipole bond engineering via BN curvature-controlled geometric-electronic coupling for high performance lithium‑sulfur batteries - Xingchao Dong; Chunting Song; Zihan Wang; Qiaoling Li; Lanlan Li; Fang Liu; Jun Cao; Weimeng Si (Chemical Engineering Journal, 2026)

A geometry-aware multi-level optimization framework for enhancing range hood capture performance - Mingyao Ma; Yiqun Li; Yukun Xu; Qingqin Wang; Zheng Jiao; Jingjing Pei; Bin Li; Lina Zhang; Yongzhe Meng; Changsheng Cao; Jun Gao (Building and Environment, 2026)

Benzoic acid inhibits peach root growth and lateral root emergence by disrupting auxin homeostasis through salicylic acid accumulation - Qing Rong Zhang; Jilin Yao; Feiyang Ji; Zhilin Sun; Bing Bai; Jun Zhao; Huchen Li; Yueping Liu; Qingqin Cao; Qing Zhang; Ting Ting Xiao (Plant Cell Reports, 2026)

Removal of antibiotics by an oleaginous green microalga Chromochloris zofingiensis under photoautotrophic, heterotrophic and mixotrophic conditions - Kai-Lu Cao; Juan Peng; Meng-Zhen Li; Lin-Yun Liao; Zi-Wen Song; Hong-Zhi He; Jun Zhao (Algal Research, 2026)

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

Vitamin B2 Affects Growth Performance of Sea Urchin Mesocentrotus nudus by Regulating Collagen-Related Exercise and Feeding Capacity - Haijing Liu; Yulong Zheng; Jiahao Cao; Sai Zhang; Ruixue Li; Jun Ding; Yaqing Chang; Rantao Zuo (Journal of Ocean University of China, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Corrigendum to “Polar sea vector wind ensemble forecasting with TD3 guided multi-objective optimization” [Ocean Eng. 364, Part 4 (2026) 127243] - Jun Zhang; Chunxiang Li; Liyuan Cao (Ocean Engineering, 2026)

Polar sea vector wind ensemble forecasting with TD3 guided multi-objective optimization - Jun Zhang; Chunxiang Li; Liyuan Cao (Ocean Engineering, 2026)

Per- and polyfluoroalkyl substances and type 2 diabetes risk: Evidence from metabolomics and triglyceride-glucose index-related pathways - Jun Zhu; Yu Xia; Ningbin Dai; Wanying Wang; Zeyuan Chen; Weiyi Cao; Haibing Yang; Jing Shi; Fang Zhou; Liuqing Zhao; Lei Li; Zhan Zhang (International Journal of Hygiene and Environmental Health, 2026)

Effects of age-related gastrointestinal conditions on the digestion of myofibrillar protein-stabilized fish oil oleogel emulsions - Yumin Niu; Li Hu; Zongyuan Han; Hongli Wang; Yu-ang Jiang; Xueyan Cao; Jun-Hua Shao (Food Research International, 2026)

Electrostatic effect and spatial conformation regulating interfacial stability and digestion of shrimp myofibrillar protein-fish oil oleogel emulsions - Yanmo Pan; Yumin Niu; Shucheng Liu; Yuxuan Wu; Zhuoyan Li; Xueyan Cao; Zongyuan Han; Jun-Hua Shao; Hongwu Ji; Mouming Zhao (Food Chemistry, 2026)

Mobile self-assembled membranes: A novel strategy for boosting light hydrocarbon separation efficiency - Yanan Jia; Zixuan Huang; Minglong Wang; Zhi Li; Hongyi Yu; Jun Xu; Bei Liu; Mingjun Deng; Jingming Li; Kun Li; Mingke Yang; Ruihang Zhang; et al. (Chemical Engineering Journal, 2026)

Electronic communication between platinum single atom and metal-organic framework enable efficient photo-assisted hydrogen production - Xu Li; Yu Zhang; Dantong Zhang; Qunzhi Ma; Jun Zhang; Jiayi Li; Wei Liu; Xiaojie Ma; Ying Wang; Wenyu Wang; Liyun Cao; Jianfeng Huang; et al. (Chemical Engineering Journal, 2026)

Gravity-assisted dual-mode biosensor based on CbAgo-driven gel-sol transition of DNA hydrogels for Salmonella detection - Jing-bo Jiao; Cheng-long Zhao; Bei-bei Tian; Jiang-li Cao; Qing Kang; Li-jun Wang; Nan Wang; Xin-jun Du; Shuo Wang (Chemical Engineering Journal, 2026)

Efficiency loss risk in rotating disk separating droplets: the role of rebound and splashing dynamics - Lianjie He; Yukun Xu; Lina Zhang; Zheng Jiao; Bin Li; Changsheng Cao; Jun Gao (Building and Environment, 2026)

Effects of photoperiod on gonadal development and neuropeptide Y and NPY1 receptor in Nile tilapia (Oreochromis niloticus) - Yujie Cao; Jun Xiao; Pengfei Gao; Yufang Chen; Zhanyang Tang; Liping Li; Zhongbao Guo; Ming Li; Zhuanling Lu; Ting Huang (Fish Physiology and Biochemistry, 2026)

Study on the present-day crustal deformation characteristics and mechanism of the Yangyuan basin - Chen Gao; Jun Cao; Jian-Bao Sun; Jiang-Tao Qiu; Guang-Qing Ma; Fan Li (Applied Geophysics, 2026)

Compatibility of three adjuvants with Cordyceps fumosorosea and their synergistic effects on controlling the diamondback moth, Plutella xylostella - Mei-Qiong Xie; Long-Jiang Wang; Yong-Qiang Han; Jin-Cui Chen; Li-Ying Cao; Shi-Chuan Luo; Fan-Fan Jiao; Shu-Jun Wei (Crop Protection, 2026)

Transcriptomic-proteomic integration reveals RNGTT as a critical host factor mediating the replication of virulent but not attenuated SADS-CoV - Zexin Chen; Yihui Huang; Mingchong Li; Ouyang Peng; Jun Luo; Yue Pan; Zhanpeng Kuang; Zhichao Xu; Yongchang Cao; Xiaona Wei; Chunyi Xue (Veterinary Microbiology, 2026)

Tumor empowered binary macrophages regulate T cell interferon signaling to mediate immunotherapy resistance in gastric cancer - Tong Xie; Bohan Zhang; Lei Jiang; Wenwen Zhang; Boxin Liu; Yang Shi; Xiaotian Zhang; Jian Li; Yifan Zhang; Jun Zhou; Yanshuo Cao; Yakun Wang; et al. (Science Bulletin, 2026)

Deep learning and hyperspectral imaging for non-destructive amino acid detection in live carp fillets - Ying-jie Qi; Yi-Ming Cao; Yan Zhang; Qi Wang; Ran Zhao; Kai-Kuo Wang; Ying-Jie Chen; Xia-Jun Qi; Jiong-Tang Li (Food Research International, 2026)

Pyraclostrobin triggers pulmonary inflammation, oxidative stress, and fibrosis in mouse via Wnt/β-catenin signaling - Jun Wang; Shihua Li; Yan Cao; Feibiao Wang; Xiangjun Li; Yuyan Zha; Yiwen Wang; Huizhen Chen (Chemico-Biological Interactions, 2026)

Mechanic simulation of aquatic biodisturbation enhances phosphorus uptake and lead immobilization in paddy soils - Hui Gao; Qingnan Chu; Jun Wang; Detian Li; Jin Zhou; Wenya Hao; Min Zhang; Yumei Mao; Linkui Cao; Chengming Zhang; Zhimin Sha (Journal of Soils and Sediments, 2026)

Hydroxyapatite nanoparticles improve vitrified bovine MII oocyte developmental competence by reducing ultrastructural damage and modulating gene expression - Xiao-Xia Li; Yi-Hang Wang; Jun Wang; Shi-Yu Zhang; Jia-Hao Zhang; Shi-Han Zhao; Qi Yan; Ping-Hua Cao; Zi-Qiang Zhang; Chen Zhou; Zhen Zhang; Qiao-Ting Shi; et al. (Animal Reproduction Science, 2026)

Mechanism-based inactivation of CYP2D6 by imperatorin and drug-drug interaction in vitro and in vivo - Hualu Wu; Lu Cao; Peiqi Wang; Ruibin Li; Jun Wu; Haoxin Fu; Yan Chen; Shiqi Jiang; Ren-ai Xu (Archives of Toxicology, 2026)

High-density lipoprotein antioxidant function is associated with lipid profiles and lipid-lowering therapy - Hong-Yu Cao; Zhi-Wei Mo; Zhen-Sheng Ma; Yi-Fang Liu; Chen Wang; Yue-Ming Peng; Yue-Ting Kang; Yan Li; Zhi-Jun Ou; Jing-Song Ou (Science China Life Sciences, 2026)

Biofilm-based immobilized fermentation of Bacillus subtilis coupled with Ni2+-NTA in situ adsorption for efficient hydrolysis of silkworm pupa protein - Xin-Chen Li; Zhi-Ang Zhang; Yi-Nan Cao; Chao Deng; Fu-Ling Wang; Hai-Fei Zhang; Richard Ansah Herman; Le-Yun Yang; Jun Wang (Sustainable Chemistry and Pharmacy, 2026)

A novel maritime traffic complexity model based on ship trajectory prediction - Zhongming Xiao; Jiaxue Zhang; Chanshu Li; Wenjie Cao; Jun Yu; Feng Bo; Xinjian Wang (Ocean Engineering, 2026)

Abnormal lipoylation of aceF in proteobacteria induced by AgNPs during the storage of ozone-treated wastewater - Muxinjian Luo; Yuhe Wang; Qiang Sun; Heng Zhang; Jun Yuan; Weiyi Zhou; Xiyun Dong; Shihao Peng; Wenbo Cao; Hong Li; Huaili Zheng (Journal of Environmental Chemical Engineering, 2026)

Fabrication of a novel Zr-Ce composite oxide for efficiently capturing Se(IV) and Se(VI) in water-based systems: Performance and underlying mechanisms - Wei Zhang; Chunting Chen; Hongpeng Cao; Jianbo Lu; Zengbao Hu; Zhaojia Li; Guanghuan Jia; Jun Ma (Journal of Environmental Chemical Engineering, 2026)

Global K cycle revisited: The role of arc hydrothermal systems - Cheng Cao; Weiqiang Li; Tianyu Chen; Jun Chen; Yuanfeng Cai (Geochimica et Cosmochimica Acta, 2026)

Biomimetic engineering of active Zn-doped macrocyclic polyamine carbon dots as organophosphorus hydrolases-like nanozymes for colorimetric and fluorescence on-site detection of methyl-paraoxon - Xiaoyu Deng; Feng Cao; Yanli Li; Lijun Wang; Xianggui Chen; Jun Li; Zhouyu Wang; Xiaoqi Yu (Food Chemistry, 2026)

Integrated assembly the multifunctional composite films using carbon dots greenly synthesized in situ on cellulose nanofibers for active fruit preservation - Lijuan Lan; Jiazhen Cao; Zichen Li; Jun-Hu Cheng (Food Chemistry, 2026)

Tetrahedral-site doping modulation in Mn3O4 toward improved water oxidation activity and stability - Shaokai Ma; Zihang Cao; Yiran Zhao; Zihao Wang; Ying Li; Xuewen Xu; Yuanhui Ma; Yanming Xue; Chengchun Tang; Jun Zhang (Chemical Engineering Journal, 2026)

Green biomass-derived degradable hydrogel electrolytes for highly stable zinc-ion batteries - Danli Qian; Qiyun Pan; Lijing Zhang; Linbin Guan; Ganghua Li; Zhong Li; Dabei Wu; Yi Cao; Hao Wu; Jun-Ming Liu (Chemical Engineering Journal, 2026)

Enhancing combined composting with cattle slurry solids as a bulking agent: Synergistic improvements in earthworm performance, lignocellulose degradation, and greenhouse gas mitigation - Jun Li; Mei Bai; Long Cheng; Yifan Shao; Yang Xu; Chao Xu; Xin Zhang; Hongliang Cao; Qiaoxia Yuan (Bioresource Technology, 2026)

Quartz compositions decipher the source and magmatic-hydrothermal evolution of Himalayan LCT-type pegmatites - Yong-Neng Zhao; Jun-Xing Zhao; Noreen J. Evans; Chang-Tong He; Rui-Zhe Shi; Shen Gao; Li-Qun Zhu; Ke-Zhang Qin; Ming-Jian Cao (Mineralium Deposita, 2026)

Long-term integration of Chinese milk vetch and controlled-release urea enhances rice yield stability by improving nutrient use efficiency and soil quality - Haoliang Yuan; Jianglin Zhang; Peng Li; Jun Nie; Weidong Cao; Yanhong Lu; Yulin Liao (Applied Soil Ecology, 2026)

One-Time Contact-Seedling Fertilization Enhances Rice Yield and Nitrogen Uptake in Mechanical Transplantation Systems - Jintao Li; Zijuan Ding; Xiaowei Ma; Yuxian Cao; Jun Hou; Bing Cao (Journal of Soil Science and Plant Nutrition, 2026)

Bioleaching enhanced by milliampere-level direct current for green recovery of palladium: impact of carbon electrode structures - Yiting Cao; Chenxi Pang; Jun Zhang; Ruohong Li; Jie Zhu; Jujun Ruan (Waste Management, 2026)

Distribution of microplastics and microorganisms and their relationship in high-salinity soil - Yuping Ma; Jing Bian; Jianguo Liu; Yunping Han; Weiying Feng; Yuxin Deng; Xuezheng Yu; Jun Zhang; Haiping Li; Yingnan Cao (Journal of Environmental Sciences, 2026)

Gaδ+-H active sites-driven reverse water gas shift reaction with high CO selectivity - Zhenzhong Tao; Huaixiang Li; Dedong He; Zijun Huang; Jun Liang; Jiaming Dong; Xiaohua Cao; Yongming Luo (Chemical Engineering Journal, 2026)

Discovery of anti-glioblastoma natural products based on andrographolide derivatives: efficiently identifying potential multi-target and multifunctional molecules through the integration of in silico methods and experimental verification - Ya-Lin Li; Jun Mao; Xin-Yu Zhou; Duan-Na Zhang; Yu-Zhi Li; Zhi-Xing Cao; Ji-Xia Ren (Molecular Diversity, 2026)

Ternary network derived from polyphenol-inspired sticky nanoparticle: nanofiltration separation efficiency and end-of-life membrane regeneration potential - Jiaying Yan; Panpan Wang; Ying Cao; Jinlong Zhu; Xingyan Jin; Luwei Li; Chuandong Wu; Hao Zhang; Hui Xie; Jun Ma (Water Research, 2026)

Contour constraint iterative algorithm for geotechnical reliability-based design with transformed performance function - Bin Li; Zi-Jun Cao; Xiao Huang (Transportation Geotechnics, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Cissatriterpenoids D-L, nine undescribed polyhydroxylated oleanane triterpenoids from Cissampelos pareira var. hirsuta - Shuang-Qin Cao; Ru-Yi Pan; Tong-Tong Zhang; Jian-Hong Gong; Meng Li; Hui Chen; Jing-Ke Zhang; Zhi-You Hao; Xiao-Ke Zheng; Yan-Jun Sun; Wei-Sheng Feng (Phytochemistry, 2026)

Nano-zero-valent iron promotes early-phase PFOA phytoaccumulation by enhancing root surface adsorption, ROS/anion channel-mediated transmembrane uptake, and soluble protein-facilitated translocation for enhanced phytoremediation - Jingming Li; Bo Chen; Xiaoyu Ma; Zhengkun Zhao; Wei Ma; Jun Liang; Xiaoyun Xu; Hao Qiu; Xinde Cao; Ling Zhao (Journal of Hazardous Materials, 2026)

Reutilization of digestate (residue and liquid) in the anaerobic digestion of sole corn stover: biochar preparation, methane performance and microbial responses - Haipeng Wang; Hao Sun; Sheng-Nan Zhuo; Jianrui Li; Zetang Chai; Jingwen Jia; Guangli Cao; Guo-Jun Xie; Defeng Xing; Nan-Qi Ren; Bing-Feng Liu (Journal of Environmental Management, 2026)

The formation mechanism of ultra-deep gas condensate reservoirs: A case study of the Shunbei No. 4 strike-slip fault zone in the Tarim Basin, NW China - Xin Yang; Hongwei Ping; Zicheng Cao; Lu Yun; Haiying Li; Jun Han; Feng Geng; Cheng Huang; Xinle Zhang; Zhongdeng Lu; Honghan Chen (Journal of Asian Earth Sciences, 2026)

The pore and fracture structure evolution and fractal characteristics of coal under the coupling effect of shock wave and acidification - Feng Chen; Jun Yin; Yanwei Qu; Lulu Ma; Peiwen Jiang; Zhilin Cao; ChengtaoYang; Mi Tian; Bing Li; Zhimin Song (Fuel, 2026)

Oxidative profile and degradation patterns of plasma-activated water-treated golden pompano (Trachinotus ovatus) during chilled storage: Insights based on data independent acquisition (DIA) quantitative proteomics - Xin Zhang; Boyan Zhao; Ying Liang; Andi Febrisiantosa; Qian Li; Bin Zhang; Soojin Jun; Yanfu He; Longteng Zhang; Jun Cao; Chuan Li (Food Chemistry, 2026)

Functional division of labor within defined yeast consortia drives flavor formation during early solid-state fermentation of sichuan shai vinegar - Jiajie Zhu; Yuting Liao; Yulin Zhao; Jun Liu; Zhicheng Li; Xiangpeng Kong; Suyi Zhang; Chuan Song; Qixu Fu; Xianbin Wang; Ruiqi Xue; Xuemei Shi; et al. (Food Microbiology, 2026)

Two CC motif chemokine 20-like genes differentially regulate leukocyte migration and survival via CC chemokine receptor 6 in ayu (Plecoglossus altivelis) - Jia-Feng Cao; Yan Zhou; Li-Jun Duan; Shi-Li Shang; Qian-Jin Zhou; Jiong Chen (Fish & Shellfish Immunology, 2026)

Slow-release fertilizers applied in conjunction with manure enhanced soil quality and rice grain yield by regulating labile nutrient pools, soil enzyme activities, and soil structure - Qing Shan Xu; Yu Lian Yan; Hang Feng Wang; Shang Pan Li; Chun Xin Chi; Ya Li Kong; Wen Hao Tian; Xiao Chuang Cao; Lian Feng Zhu; Qiao Ling Li; Jing Wang Li; Jun Hua Zhang; et al. (Field Crops Research, 2026)

Occurrence and distribution of phthalate esters in stormwater runoff and coastal water receiving bodies, Macao, South China - Yutang Luo; Tianyi Zhang; Yaru Cao; Qiying Jian; Aolei Du; Jun Yan; Yanjun Li; Youxiang Xu; Guoyuan Zhu; Xiong Xiong; Chenxi Wu; Kai Zhang (Environmental Pollution, 2026)

Side-deep fertilization increases rice yield and nutrient use efficiency in China: A meta-analysis - Kaiqin Yuan; Jintao Li; Zifang Chen; Xiaowei Ma; Richard W. Bell; Yuxian Cao; Jun Hou (European Journal of Agronomy, 2026)

Improving rice cooking and eating quality: Panicle nitrogen fertilizer modifies amylopectin structure and amylopectin-protein interactions in post-ripening - Zongkui Chen; Xinrui Li; Yue Huang; Xiangyu Xu; Jinghan Cao; Jiayue Wang; Ziyou Yu; Wenqi Yuan; Zhixin Li; Jingsha Tang; Zhonglin Wang; Zhiyuan Yang; et al. (Carbohydrate Polymers, 2026)

Population pharmacokinetics of rivaroxaban after transjugular intrahepatic portosystemic shunt - Min Jia; Yiming Chai; Yuan Gao; Changyou Jing; Kunlei Zhu; Tong Zhu; Liang Wang; Aili Sun; Jun Yang; Yanqiu Zhu; Yingmei Feng; Yu Cao; et al. (European Journal of Clinical Pharmacology, 2026)
Purpose Rivaroxaban, a new direct oral anticoagulant (DOAC), has demonstrated better efficacy and safety than traditional anticoagulants. Individualized anticoagulation is crucial in patients with a transjugular intrahepatic portosystemic shunt (TIPS) and portal vein hypercoagulability to avoid stent thrombosis. As TIPS shunts portal blood directly into the systemic circulation and may substantially affect the first-pass extraction/distribution of direct oral anticoagulants, no population prospective pharmacokinetic studies have been published in patients undergoing TIPS placement so far. The goal of this study was to establish a PopPK model for rivaroxaban in post-TIPS patients, investigate clinical covariate effects on PK, and provide an optimized dosing regimen. Methods In this single-centre prospective study, 39 adult patients underwent TIPS and received rivaroxaban 5 or 10 mg once daily thereafter. Population PK analysis was conducted in NONMEM with 131 plasma concentrations available from 38 evaluable patients (median age: 56 years; median body weight: 63.8 kg). Parameterized model was then applied to simulate steady-state exposure of 5, 7.5, 10, and 15 mg once daily regimen. Results The final PopPK model was based on a one-compartment with sequential zero-order followed by first-order absorption kinetics, and included the effects of an absorption lag time and linear elimination. The apparent clearance and volume of distribution were 7.48 L/h and 4.75 L, respectively. Based on patient-specific simulations of 38 subjects, at the 5 mg/day dose, an exposure within predefined limits was potentially preserved in 96.7% of the cases vs. 62.5% for the 10 mg/day (thresholds: AUC ss,24 ≤ 1.77 mg·h/L and C max, ss ≤ 140 µg/L). This trend was confirmed by Monte-Carlo simulations in 1,000 virtual patients and suggests TDM when the higher dosage is given. Conclusions This PopPK model provides an initial characterisation of rivaroxaban disposition in post-TIPS patients and reveals a markedly reduced apparent V/F relative to non-TIPS populations. The 5 mg once-daily regimen is generally safe, while the 10 mg dose may be considered with therapeutic drug monitoring to account for substantial inter-individual pharmacokinetic variability in post-TIPS patients. Trial registration Chinese Clinical Trial Registry, ChiCTR (ChiCTR2300073784); registered 20 July 2023.

Response of carbonate weathering and CO2 sink to agricultural HNO3 in the river water of a piedmont region: a case study from the Qingshui River - Jun Li; Baoqi Wang; Wei Liu; Shengwei Cao; Beichang Zhang; Changsong Zhou; Guoli Yang (Environmental Geochemistry and Health, 2026)

Loss of soil ecosystem multifunctionality during alpine grassland restoration with reseeding and organic fertilization - Zuonan Cao; Guozheng Hu; Xuyang Han; Guoxu Ji; Yandan Ma; Zheng Li; Hasbagan Ganjurjav; Jun Yan; Youxia Wang; Qingzhu Gao (Agriculture, Ecosystems & Environment, 2026)

Lake Water Depth and Nutrient Gradients Mediate Aquatic Plant Distribution via the Strength of Trait Network Associations - Guixiang Yuan; Huan Long; Jun Liu; Qiling Xie; Yaoxuan Tan; Zihui Hong; Jiahui Yue; Aimin Zhou; Hexuan Zhou; Weilin Xu; Bao Wang; Huanyao Liu; et al. (Global Change Biology, 2026)
Aquatic macrophyte responses and adaptation to water depth and nutrient gradients are of critical importance for understanding the functional ecology of lakes and their restoration when degraded. However, the role of plant trait networks (PTNs), a powerful tool for decoding trait–environment–function relationships, in mediating these adaptations remains unclear, particularly across species and community scales. We conducted cross‐scale PTN analyses at species and community levels for aquatic macrophytes, integrating assessments of phylogenetic signals and hierarchical environmental filtering. At species level, aquatic macrophytes exhibited two complementary PTN‐based adaptive strategies: trait compartmentalization to enhance stress tolerance and trait integration to optimize resource utilization. Notably, local environmental conditions (rather than phylogenetic signals) dominated the pattern of PTN metrics, highlighting the primacy of immediate habitat constraints over evolutionary relatedness in driving species‐specific adaptations. At community level, environmental filtering operated hierarchically, acting sequentially by water depth, nutrient availability, and lake morphology. PTNs further mediated the trade‐off between community diversity and productivity, providing a mechanistic link between abiotic filtering and ecosystem function. Our findings advance network theory in functional ecology by extending its application to aquatic systems, bridging longstanding gaps between terrestrial and aquatic PTN research, and offering actionable guidance for eutrophic lake restoration (e.g., by targeting PTN‐linked core traits related to nutrient adaptation). Overall, our work provides a cross‐scale framework for understanding PTN mediated adaptation of aquatic macrophytes and its implications for ecosystem management.

Downregulation of intracellular ATP levels by PANX1 inhibits ovarian granulosa cell proliferation and mediates follicular dysplasia in elderly women - Zhiqin Zhang; Xuechen Sun; Xin Li; Peipei Liu; Liyun Cao; Shenggen Long; Jun Tan (Reproductive Biology, 2026)

Development of β-carotene microcapsules based on collagen peptides: Improving bioaccessibility and application in functional biscuits - Liyuan Xiao; Jun Yang; Shanshan Lu; Yuan Xu; Fawen Yin; Yang Hu; Aiguo Feng; Chuan Li; Jun Cao (Journal of Food Engineering, 2026)

Process design and techno-economic evaluation of hydrogen production from microalgae conversion in molten salts - Jun Li; Ling Lei; Xiaoxia Yang; Wenxuan Cao; Dian Zhong; Kuo Zeng; Haiping Yang (Journal of Cleaner Production, 2026)

Identifying the genesis and evolution of geothermal water in the coal mining area, North China: Insights from hydrochemistry and δ2H, δ18O, δ13C, δ34S and 87Sr/86Sr isotopes - Jie Zhang; Herong Gui; Luwang Chen; Manli Lin; Huifang Rong; Jun Li; Ruirui Li; Mingda Cao (Geothermics, 2026)

Efficient capillary electrophoretic analysis of anthraquinones and phenolic acids in functional foods using a novel deep eutectic solvent–in–deep eutectic solvent microemulsion - Kai-Yang Fan; Shi-Qi Niu; Tian Zhang; Jun Cao; Li-Hong Ye (Food Chemistry, 2026)

Effect of pH-shifting combined with ultrasound treatment on the physicochemical, structural, and gelation properties of oxidized pea protein isolate - Qian Li; Siying Liu; Yi Cao; Yujie Cheng; Xudong Yan; Jun Chen; Taotao Dai; Peiyi Shen; David Julian McClements; Jian Xu; Ruiyun Chen (Food Hydrocolloids, 2026)

The structural and rheological modulations of okra polysaccharides induced by high-speed shear integrated ultrasonic acid extraction - Yang Xu; Hongwei Cao; Qishan Dong; Huimin Li; Chuyan Li; Jinxuan Cao; Yangying Sun; Jun He (Food Hydrocolloids, 2026)

Potential freezing resistance of collagen peptide-fish oil high internal phase emulsion: enhancing freeze-thaw stability of 3D-printed surimi - Yunuo Zhou; Shanshan Lu; Hongyuan Chen; Yuan Xu; Fawen Yin; Bin Zhang; Zhisheng Pei; Longteng Zhang; Dayong Zhou; Chuan Li; Jun Cao (Food Hydrocolloids, 2026)

Tailoring curdlan microgel properties via thermal pretreatment: From gel fracture behavior to fat replacement in low-fat mayonnaise - Jingwen Zhao; Peng Wu; Li Xu; Jian He; Jun Xu; Ying Xu; Yiping Cao; Xiaoyang Li; Yiguo Zhao; Yapeng Fang (Food Hydrocolloids, 2026)

A new type ammonium ion hybrid micro-supercapacitor with wide voltage for flexible wearable electronic devices - Xingxing Li; Zilong Wang; Guosheng Li; Mengdi Guo; Jun Cao; Shuhao Shi; Fukang Liu (Chemical Engineering Journal, 2026)

Using 3D Seismic to Estimate the In Situ Stress Model for the 3D Drilling Mud Weight Window - Jun Li; Yang Zhao; Chenggang Xian; Lele Zhang; Zhaozhou Chen; Shichang Li; Huan Cao; Lu Liu; Jidong Yang (Rock Mechanics and Rock Engineering, 2026)

Hexavalent chromium induced autophagy-dependent mTOR expression mediated by upregulation of HMGA2 - Li Li; Meng Dan; Shengnan Li; Xiaojing Cui; Shibo Bao; Shengxiang Luo; Jun Cao (Toxicology, 2026)

Organic amendment increases soil carbon sequestration by altering carbon stabilization pathways within soil aggregates - Shihao Ma; Yudong Cao; Jianwei Lu; Zhifeng Lu; Jun Zhu; Wenjun Zhang; Xiaokun Li (Soil and Tillage Research, 2026)

Recyclable Na-Mn-O nanocomposite for dual-modal photothermal/ROS antibacterial therapy against multidrug-resistant bacteria in pathogen-laden wastewater - Zhi-ru Tao; Shu-xian Hou; Yi-mei Wang; Xue-chao Shi; Xin-xin Liu; Jun Ge; Yu-han Ji; Ya-qi Cheng; Zi-yi Leng; Xin-yv Cao; Rong-rong Li; Jin-nan Xuan; et al. (Journal of Water Process Engineering, 2026)

Thermal decomposition behavior of branched and linear perfluoropolyether lubricants - Shizhao Yang; Jun Ma; Xin Xu; Jianqiang Hu; Li Guo; Jingpei Cao; Teng Chen (Journal of Fluorine Chemistry, 2026)

Hollow core-shell nanotube of NiO/CdS/Ti3+-CaTiO3 perovskite ternary junction towards overall water splitting via HER/OER synergism - Hu Yang; Wenhui Yang; Xinyan Li; Qiying Peng; Jun Cao; Yingying Zheng; Jingjing Wang; Jiaqi Pan; Mei Zhu; Chaorong Li (Journal of Environmental Chemical Engineering, 2026)

Origin and forming mechanism of coking substance in ester aviation lubricating oil - Teng Chen; Huashuai Gao; Ping Qi; Shizhao Yang; Xin Xu; Jun Ma; Li Guo; Jingpei Cao; Jianqiang Hu (Fuel, 2026)

Exploring the regulatory mechanism of carboxymethyl chitosan on porcine myofibrillar protein gel properties, molecular interactions and digestive properties - Hongwei Cao; Yang Xu; Qishan Dong; Huimin Li; Chuyan Li; Jinxuan Cao; Yangying Sun; Jun He (Food Chemistry, 2026)

Cottonseed protein fibrils: A plant-based foaming agent outperforming egg white - Shuangjian Li; Sai'erdar Abulimit; Xuezhi Bai; Rulin Jin; Jun He; Xiaoyang Li; Wei Lu; Yiguo Zhao; Cuixia Sun; Yapeng Fang; Yiping Cao (Food Chemistry, 2026)

Probabilistic characterization of 3D geotechnical variability by fusion of multi-fidelity measurements using Gaussian Process Regression - Tengyuan Zhao; Yatong Qi; Zi-Jun Cao; Ling Xu; Dong Wang; Wei Li (Engineering Geology, 2026)

Dual-phase anion engineering for boosting lithium capture by Li/Al-LDHs - Yujiao Cao; Chenghao Qiu; Jipeng Li; Jun Chen; Jianguo Yu; Sen Lin (Desalination, 2026)

Tunable synthesis of tailored high-energy-density fuels from coal-based fluorene - Bing-Wei Chen; Hua-Jun Zhai; Yan-Cheng Hu; Yan-Hong Tan; Jia Li; Zhilian Wu; Lin Shao; Jing-Pei Cao (Chemical Engineering Journal, 2026)

The influence of Fe/Mn ratios on the properties of Na2Fe1-xMnxPO4F cathode materials for sodium-ion batteries - Wen Ren; Mengrui Li; Shiqiang Zhou; Zhitao Cao; Lukuan Cheng; Wenzheng Li; Chuangzhou Long; Suzhu Yu; Xinxin Cao; Jun Wei (Chemical Engineering Journal, 2026)

Synergistic engineering of a whole-cell catalyst immobilized on bimetallic CaZn-MOF for efficient PET Depolymerization - Yun-kang Chang; Xiao-huan Liu; Nan-Li; Jun-li Jin; Hai-tong Sun; Shuo Li; Fei-fei Zhang; Yu-xuan Song; Xin-hong Yu; Qi-zhi Cao; Fei Liu; Na Xu; et al. (Chemical Engineering Journal, 2026)

Enhancing short-term PWV prediction through GNSS and ERA5 data fusion - Yuxuan Cao; Jun Tang; Hetu Li; Yibin Yao; Liang Zhang; Chaoqian Xu (Atmospheric Research, 2026)

Identification of low-toxicity DNA topoisomerase I inhibitors with potential blood–brain barrier penetrability for glioblastoma therapy: structure-based virtual screening reveals promising novel Scaffolds - Ya-Lin Li; Jun Mao; Zhong Cheng; Xin-Yu Zhou; Duan-Na Zhang; Yu-Zhi Li; Zhi-Xing Cao; Ji-Xia Ren (Molecular Diversity, 2026)

Comprehensive micellar / reversed-phase two-dimensional liquid chromatography for separation and identification of phenolic compounds in herbal tea by multivariate statistical analysis - Qian-Xue Shen; Yi-Wen Wu; Xin-Ran Ma; Jun Cao; Li-Hong Ye (Analytica Chimica Acta, 2026)

Exploring the impacts of flavonoid compounds on escitalopram metabolism: a combined in vitro and in vivo study - Hailun Xia; Jun Wu; Haoxin Fu; Peiqi Wang; Ruibin Li; Lu Cao; Ya-nan Liu; Lu Shi; Ren-ai Xu (Molecular Diversity, 2026)

Pooled data from phase 3 clinical trials comparing the clinical activity of ceftolozane/tazobactam versus meropenem for the treatment of complicated intra-abdominal infections - Zhiqiang Li; Yue Kang; Hongqiang Gao; Yingpeng Zhao; Ding Luo; Dongdong Wang; Xiang Zhang; Jieqi Yu; Guang Chu; Jun Cao; Fan Wang; Xiongqi Zhao; et al. (Infectious Diseases, 2026)

Enhanced T-cell activation and effector functions contribute to disease resistance in Streptococcus agalactiae-resistant tilapia - Ming Geng; Jingfeng Ding; Jun Xiao; Liting Chen; Jiansong Zhang; Kang Li; Jie Cheng; Yi Cao; Jialong Yang; Xiumei Wei (Aquaculture, 2026)

Assessment of provincial PV recycling potential: Integrating product lifetime distribution and scrap capacity - Bao-Jun Tang; Wen Shi; Ru Li; Xi-Lin Cao (Sustainable Production and Consumption, 2026)

Challenges and solutions to seismic amplitude pitfalls in dim-spot sandstone reservoirs: A case study from the Shaximiao formation, the Western Sichuan Depression, China - Feng Tan; Ping Yang; Jun-Xing Cao; Le Li; Zhihua Cui; Qian Ma (Journal of Applied Geophysics, 2026)

Bioamines-sensitive, antioxidant, and sustainable gelatin-based jelly ice cubes doped with carbon dots for simultaneous preservation and monitoring of seafood freshness - Jun Li; Yanli Li; Feng Cao; Linchen Yin; Yimiao Zhang; Houqi Ning; Zhouyu Wang; Xiaoqi Yu (Food Research International, 2026)

Simultaneous total antioxidant capacity assessment and ascorbic acid accurate quantification utilizing a H2O2-independent colorimetric-fluorescent sensor array - Yanli Li; Feng Cao; Xiaoyu Deng; Jun Li; Zhouyu Wang; Xiaoqi Yu (Food Chemistry, 2026)

Green Intelligent Fertilizer derived from yellow phosphorus slag boosts rice yield and mitigate environmental impacts in high-altitude watersheds - Suoqian Kang; Ou Yu; Shuntao Zhang; Yujiao Tan; Rui Wang; Xueli Du; Jun Cao; Zhong Duan; Fei Huang; Rong Li; Changzhou Wei; Jiujiang Xu (Field Crops Research, 2026)

Investigate the in-plane and out-of-plane elastic properties of spiderweb-inspired hierarchical composite honeycombs using forward analytical and inverse numerical approaches - Peng-Xu Lu; Jun Wang; Jin Zhou; Zhou Qiao; Jichuan Cao; Hui Li; Feiping Du; Zhongwei Guan (Engineering Structures, 2026)

β-Cyclodextrin biomimetic organoiridium triggered intracellular transfer hydrogenation cleavage and imaging - Li-Jun Zhao; Qing Zhou; Shixin Zhang; Li-Xiang Wang; Zi-Wen Guo; Chao Shi; Yanhong Li; Feng Luan; Chunyuan Tian; Yue Cao; Peng Xiao; Xuming Zhuang (Chemical Engineering Journal, 2026)

Automatic Image Co-registration of Carotid Angiography and Intravascular Optical Coherence Tomography Based on Machine Learning Method: A Pilot Feasibility Study - Hui Xu; Jia-Nan Li; Yan Xu; Jun-Ren Ma; Kang Zong; Rui Zhu; Yi-Hui Cao; Peng-Fei Yang; Rui Zhao; Jian-Min Liu (Annals of Biomedical Engineering, 2026)

Highly selective electrocatalytic CO2 reduction to formate by a dinuclear nickel complex: cooperative catalysis across diverse conditions - Haitao Lei; Fengwang Li; Chengyu Liu; Jun Li; Yabo Wang; Dae-Hyun Nam; Yanwei Lum; Si-Xuan Guo; Yi Xu; Jie Zhang; Wenzhen Lai; Rui Cao (Science Bulletin, 2025)

Thermal desorption coupled with persulfate oxidation for removing soil organic pollutants: Key role of soil organic matter passivation - Zhicheng Li; Jun Liang; Jingming Li; Xiaoyu Ma; Yi Lang; Hanwen Li; Hao Qiu; Xinde Cao; Ling Zhao (Journal of Hazardous Materials, 2025)

Corrigendum to “Synthesis of an autochthonous microbial community by analyzing the core microorganisms responsible for the critical flavor of bran vinegar” [Food Res. Int. 175 (2024) 113742] - Li Li; Na Li; Junjie Fu; Jun Liu; Xue Ping Wen; Hong Cao; Hongwei Xu; Ying Zhang; Rong Cao (Food Research International, 2025)

High internal phase Pickering emulsions stabilized by arginine-myosin microgel particles for 3D printing low salt surimi - Quanhong Lu; Jun Yang; Yunuo Zhou; Yuan Xu; Fawen Yin; Yanfu He; Hui Ye; Hesham El-Seedi; Longteng Zhang; Qian Li; Jun Cao; Chuan Li (Food Chemistry, 2025)

Non-ionic microemulsion extraction and in situ cloud point liquid-liquid microextraction of flavonoids and carotenoids from functional food - Qian-Xue Shen; Yan-Hua Jiao; Ting-Hong Fei; Jun Cao; Li-Hong Ye (Food Chemistry, 2025)

Surface engineering strategies for efficient photocatalytic nitrate reduction in wastewater purification - Yizhen Zhang; Shujun Meng; Penghui Li; Xumiao Hou; Jie Mao; Xiaoqiang Cao; Xiang Cai; Jun Zhang; Michael K.H. Leung (Environmental Research, 2025)

Cellular indexing of transcriptomes and epitopes by sequencing unveils coordinated RNA and protein landscape in ovary at single-cell resolution - Yujuan Qi; Yuxuan Feng; Xiaoyan Liu; Jiaxin Li; Qiuru Huang; Zhenbei Li; Sen Zheng; Ning Chen; Jie Cheng; Xinhui Yang; Wei Tao; Xiangnan Cao; et al. (Chemical Engineering Journal, 2025)

Innovative self-evolution manipulation for constructing ultra-uniform rich copper vacancies Cu31S16/GeS2 heterojunction towards exceptional sodium storage - Liang Cao; Jun Zhao; Yushen Liu; Yiwei Xue; Yafu Wang; Hongbo Geng; Xing Ou; Qingyu Li (Chemical Engineering Journal, 2025)

Phase boundary mapping boosts thermoelectric performance in p-type FeSb3-based skutterudites - Xiaofang Li; Honghao Yao; Baopeng Ma; Yunzi Ren; Li Yin; Xiaodong Wang; Feng Cao; Chen Chen; Jun Mao; Qian Zhang (Chemical Engineering Journal, 2025)

Understanding the formation of starch structure during grain development in two wheat cultivars with different filling rate - Faji Li; Cong Zhao; Dengan Xu; Dungong Cheng; Aifeng Liu; Shengnan Zhai; Jun Guo; Yan Zi; Xinyou Cao; Cheng Liu; Jianmin Song; Haosheng Li; et al. (Carbohydrate Polymers, 2025)

Novel compound bacterial agent effects on pig farm wastewater denitrification and nitrogen transformation - Rong Gao; Zhuangzhuang Liu; Weikun Li; Liu Lou; Tong Xu; Lin Shi; Jie Cao; Jun Fang; Gang Liu (Bioresource Technology, 2025)

CFD–DEM and Experimental Investigation of Seepage Behavior at Soil–Structure Interfaces - Xue-min Yang; Zeng-guang Xu; Jun-rui Chai; Cheng Cao; Chao-wei Sun; Gang Li (Geotechnical and Geological Engineering, 2025)

Transcriptomic profiling reveals mechanism, therapeutic potential, and prognostic value of cancer stemness characteristic in nasopharyngeal carcinoma - Jin-Wei Chen; Run-Nan Shen; Jiang-Quan Zhu; Ying-Hang Wang; Liang-Min Fu; Yu-Hang Chen; Jia-Zheng Cao; Jin-Huan Wei; Jun-Hang Luo; Jia-Ying Li; Cheng-Peng Gui (Functional & Integrative Genomics, 2025)

Knockout of the Agrobacterium ILVC gene generates a valine-isoleucine auxotrophic strain for plant transformation - Yanhui Yang; Jun Lu; Tianrui Xue; Zhenli Cao; Mingjie Li; Zhongyi Zhang; Rong Wang; Tongyu Wu (Transgenic Research, 2025)

Quantitative Evaluation of Gas Injection Contribution Using Fluid Inclusion Data: A Case Study of the Condensate Gas Reservoirs of the Eastern Shunbei Area in the Tarim Basin - Zicheng Cao; Lu Yun; Hongwei Ping; Haiying Li; Feng Geng; Jun Han; Cheng Huang; Xin Yang; Honghan Chen (Journal of Earth Science, 2025)

A neutron transport calculation approach via the coupling of 2D/1D and 3D SN nodal methods - Hongchun Wu; Shuaizheng Li; Jun Chen; Guangwen Bi; Zhouyu Liu; Sifan Zhang; Xinyu Zhou; Liangzhi Cao (Annals of Nuclear Energy, 2025)

Characteristics and distribution patterns of volcanic fractures in the Chaganhua Subsag of the Songliao Basin, China - Ning Li; Xuan-long Shan; Jian Yi; Zhong-bo Li; Kai-fang Cao; Jun Tian; Yun-qian Shi; Qing-lei Leng (Applied Geophysics, 2025)

Identifying urban river pollution sources from wet-weather discharges using an integrated deep learning and data assimilation approach - Hongzhe Pan; Yiping Li; Jiangjiang Zhang; Chenglong Cao; Yu Cheng; Yuxuan Zhou; Yaning Wang; Song Bai; Jun Liu; Qiaoyi Jin; Carlo Gualtieri (Journal of Hydrology, 2025)

Multi-omics integration deciphered microbial and metabolite dynamics during flavor development of rapidly fermented golden pompano - Xin Zhang; Fanghui Shao; Jun Cao; Yanfu He; Longteng Zhang; Bin Zhang; Soojin Jun; Andi Febrisiantosa; Aiguo Feng; Jun Yang; Lulu Zhu; Chuan Li (Food Bioscience, 2025)

A novel high selectivity, strong acid resistance and antifouling polyamide thin film composite nanofiltration membrane fabricated with 3,3′-diamine-Tröger's base - Liu-Yang Gong; Nian Zhang; Jun-Yan Yu; Yan-Nan Wu; Chen-Jie Wei; He-Lin Zhu; Xue-Li Cao; Li-Fen Liu (Desalination, 2025)

Enhancing E. coli removal in mesophilic anaerobic digestion: New insights from inoculum comparison and metagenomic analysis - Haipeng Wang; Zetang Chai; Jianrui Li; Hao Sun; Hong-Yu Ren; Guangli Cao; Guo-Jun Xie; Defeng Xing; Nan-Qi Ren; Bing-Feng Liu (Bioresource Technology, 2025)

Livestock manure-based organic fertilization facilitates the transmission of antibiotic resistance genes across the soil-onion continuum: A significant contribution from root exudates - Zixuan Zhao; Bin Luo; Tao Cao; Tongtong Bai; Yifan Sun; Hengrui Liu; Li Zhang; Jun Xie; Jun Wang; Huakang Li; Zichen Duan; Zixuan Gao; et al. (Soil Biology and Biochemistry, 2025)

Rice straw returning under winter green manuring enhances soil carbon pool via stoichiometric regulation of extracellular enzymes - Shun Li; Guodong Zhou; Guopeng Zhou; Jun Nie; Jianglin Zhang; Songjuan Gao; Weidong Cao (Soil and Tillage Research, 2025)

Ichnology across the Permian–Triassic transition at the Meishan section, with implications for palaeoceanic redox evolution in South China - Yi Ding; Li-Jun Zhang; Chang-Qun Cao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Quantifying the impact of thermal maturity on carbon isotope variations of marine oils from the Shunbei ultra-deep petroleum system, Tarim Basin - Zhongdeng Lu; Hongwei Ping; Zicheng Cao; Lu Yun; Haiying Li; Feng Geng; Jun Han; Cheng Huang; Honghan Chen (Organic Geochemistry, 2025)

Genotoxicity mode of action exploration of polyethylene glycol terephthalate (PET) acetic acid migration solution under repeated-dose exposure in rats - Liang Wang; Li Cao; Xiaoya Wang; Yufei Liu; Weiwei Zhang; Yurui Gou; Jun He; Jiao Huo; Xiaomeng Li; Jinyao Chen (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2025)

Oxygenated aromatic compounds as dominant contributors to the oxidative potential of PM2.5 emitted from biomass burning and coal combustion - Feiyan Cao; Xinxin Feng; Yingjun Chen; Hongxing Jiang; Yong Han; Tian Chen; Yu Shang; Dan Li; Qianyu Zhang; Huimin Ma; Jun Li; Gan Zhang (Journal of Hazardous Materials, 2025)

The ultrathin hollow core-shell heterojunction in Co3O4/Ti3 + -TiO2/Cd0.8Zn0.2S towards enhanced overall water splitting and photodegradation via synergism of HER/OER matching and Ti3+/Ov-bimetallic affect - Wenhui Yang; Qiying Peng; Xinyan Li; Jingjing Wang; Yingying Zheng; Jun Cao; Jiaqi Pan; Mei Zhu; Chaorong Li (Journal of Environmental Chemical Engineering, 2025)

Enhanced acidic hydrogen evolution stability and activity in CoP through S doping for proton exchange membrane electrolyzers - Shiqing Zhang; Shaokai Ma; Zihao Wang; Zihang Cao; Fang Liu; Ying Li; Xuewen Xu; Yuanhui Ma; Yanming Xue; Chengchun Tang; Jun Zhang (Fuel, 2025)

Antibacterial mechanism of non-thermal treatments against Pseudomonas putida and their application in tilapia fillets - Dongyin Liu; Zhiliang Huang; Yuan Xu; Xin Zhang; Hui Ye; Xiaoshuan Zhang; Longteng Zhang; Yanfu He; Jun Cao; Jiamei Wang; Jun Yang; Chuan Li (Food Research International, 2025)

Dietary valine modulates hepatic immune responses in largemouth bass (Micropterus salmoides) against Aeromonas veronii infection: Integrated regulation of antioxidant defense, ER stress and autophagy - Ju Zhao; Xiaoqing Li; Tianran Zhang; Haifeng Liu; Quanquan Cao; Jun Jiang (Fish & Shellfish Immunology, 2025)

Hydrogen spillover by boron carbon nitride support for efficient acidic hydrogen evolution reaction - Fang Liu; Shiqing Zhang; Shaokai Ma; Zihang Cao; Ying Li; Yuanhui Ma; Xuewen Xu; Jun Zhang; Yanming Xue; Chengchun Tang (Chemical Engineering Journal, 2025)

Direct electron transfer from electron-reservoir sandwich-type polyoxometalate to Co2Ni2-cluster via water-assisted proton channels and tandem effects for efficient nitrate-to-ammonia electrocatalysis - Jiaxing Li; Mengle Yang; Aixiang Tian; Xixian Cao; Jun Ying; Xiuli Wang (Chemical Engineering Journal, 2025)

Mechanically robust lignin-cellulose films with triple barrier functions for antagonistic food preservation - Ningkang Deng; Yue Ma; Pengfei Li; Jinsong Zeng; Zhiqiang Gong; Jianqiao Su; Jinpeng Li; Daxian Cao; Bin Wang; Jun Xu; Kefu Chen (Chemical Engineering Journal, 2025)

Efficient degradation and deiodination of iopamidol by synergistic •OH and SO4•− oxidation in O3/PMS system - Xing Wang; Guanqi Liu; Ying Cao; Xinglin Lu; Chaoting Guan; Juan Li; Jun Ma; Jin Jiang; Yi Yang (Chemical Engineering Journal, 2025)

Innovative approaches to sodium reduction in pickled foods: A review of recent developments - Yi Cui; Wei Lu; Przemyslaw Zalewski; Jun He; Xiaoyang Li; Yiping Cao; Yiguo Zhao; Cuixia Sun; Jinhong Wu; Huiyun Chen; Yapeng Fang (Trends in Food Science & Technology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Aggregation pheromones of Bostrichidae: A review - Li Yu; Xiao-Lu Cao; Wei Zheng; Jun Li; Fa-Yang Xie; Xia-Lin Zheng (Journal of Stored Products Research, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

Investigating the performance of biochar modified cementitious material for solidification/stabilization of long-term stored sludge from wastewater treatment plants - Chuanbo Sun; Xin Chen; Jun Wang; Feng Zhong; Haitao Cao; Jiang-shan Li (Journal of Cleaner Production, 2025)

Geochemical mapping and distribution patterns of critical elements resources in Chinese coal-bearing strata - Ruiwen Yan; Jun Zhu; Qingyi Cao; Gang Lin; Xiang Li; Furui Xi (International Journal of Coal Geology, 2025)

Corrigendum to “Effect and mechanism of functional compound fruit drink on gut microbiota in constipation mice” [Food Chem. 401 (2023) 134210] - Yali Shi; Fei Chen; Ziqi Wang; Jun Cao; Chuan Li (Food Chemistry, 2025)

Effect of cation type on the formation, structure and functional properties of enzyme-crosslinked pea protein gels and emulsion gels - Xiaoxuan Yan; Shangdong Yan; Yi Cao; Yinxin Fu; Jun Chen; Taotao Dai; David Julian McClements; Qian Li (Food Chemistry, 2025)

Converting pig manure into biochar mitigates the antibiotic resistance of vegetable endophytes - Xue Zhou; Jun Ma; Min Qiao; Yin Wang; Zhi-Hong Cao; Jian-Qiang Su; Wan-Ying Xie; Patrick O'Connor; Gang Li (Environmental Pollution, 2025)

The in situ Mg/Ca ratios of planktonic foraminifera shells in the northeastern South China Sea: an attempt to get efficient and reliable proxies - Guanglu Zhang; Yanyan Zhao; Jun Yang; Sheng Liu; Zhishun Zhang; Xiaoqiang Guo; Guangyao Cao; Lei Yang; Sanzhong Li; Li Zou (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Ultrastable interfacial configuration enabled by multiple NaGe/Na2S interphases for long-cycling life sodium metal batteries - Zhefei Wang; Kang Xu; Jun Yang; Yue Li; Jia Guo; Chencheng Sun; Liang Cao; Hongbo Geng (Chemical Engineering Journal, 2025)

Unlocking bio-H2 production potential from straw–sludge co-substrates: The role of Fe/Mn-biochar in alleviating carbon catabolite repression - Ji-wen Wu; Shi-jie You; Chun-shuang Zhou; Qi Xi; Jia-ning Fan; Jun Ma; Guang-li Cao (Chemical Engineering Journal, 2025)

Enhancing the mechanical and barrier properties of starch-based green packaging films via acetalization reaction and hydrogen bond dual crosslinking - Bin Wang; Xuezhou Wang; Hongxia Ma; Jinpeng Li; Daxian Cao; Jun Xu; Jinsong Zeng; Wenhua Gao; Kefu Chen (Carbohydrate Polymers, 2025)

Short-term exposure to banana starch induces low-grade colonic inflammation in healthy mice - Bing Jiang; Chenglu Peng; Przemyslaw Zalewski; Jun He; Xiaoyang Li; Yiguo Zhao; Cuixia Sun; Yiping Cao; Wei Lu; Yapeng Fang (Carbohydrate Polymers, 2025)

Genetic mapping and isolation of Rht28, a locus on wheat chromosome arm 2AL affecting plant height, grain size, and grain weight - Zhuo Liu; Jiaojiao Zhu; Qiuyue Zhao; Yiwen Cao; Qiuhong Wu; Junru Zhang; Yongxing Chen; Qingpeng Sun; Runzhi Li; Heng Tang; Zhiyong Liu; Jun Han (Theoretical and Applied Genetics, 2025)

Developing and validating an explainable clinlabomics-based machine-learning model for screening primary angle-closure glaucoma in the context of PPPM - Zhuqing Li; Jun Ren; Jianing Wu; Yingzhu Li; Yunxiao Song; Mengyu Zhang; Shengjie Li; Wenjun Cao (EPMA Journal, 2025)

New anti-inflammatory limonoids from the fruits of Melia azedarach - Fan Cao; Jin-Huang Shen; Zhi-Jun Li; Wen-Lu Wang; Zhen-Wei Chen; Yong-Hong Zhang; Xin-Hua Ma (Natural Product Research, 2025)

Rubber-derived chemicals in urban sewer networks and receiving waters: Fingerprints, driving factors and ecological impacts - Shaopeng Xu; Kai Zhang; Jia-Yong Lao; Qi Wang; Yan Jiang; Chen Li; Jun Kin Kwok; Guodong Cao; Chong Chen; Yue Deng; Kenneth M.Y. Leung (Water Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Spatio-temporal net primary productivity prediction in western Sanjiangyuan region using deep learning with spatial aggregation model and non-local attention mechanism - Fujiang Liu; Zhe Zhu; Weihua Lin; Yan Guo; Bo Li; Kurelijiang Aymer; Ziheng Cao; Jun Zheng (Remote Sensing Applications: Society and Environment, 2025)

A symbiotic bacterium regulates the detoxification metabolism of deltamethrin in Aedes albopictus - Si-jia Deng; Lei Tu; Lin Li; Ju-ping Hu; Ju-lin Li; Jian-xia Tang; Mei-chun Zhang; Guo-ding Zhu; Jun Cao (Pesticide Biochemistry and Physiology, 2025)

Corrigendum to “Influence of gluten and starch granules interactions on dough mixing properties in wheat (Triticum aestivum L.)” [Food Hydrocolloids 106 (2020) 105885] - Xin Gao; Jingyang Tong; Lei Guo; Liwei Yu; Shaopeng Li; Bingpeng Yang; Libin Wang; Yang Liu; Faji Li; Jun Guo; Shengnan Zhai; Cheng Liu; et al. (Food Hydrocolloids, 2025)

Cr (VI) induces lactate utilization through HIF-1α/MCT1 dependent on p53 protein level - Shengnan Li; Yajing Guo; Xiaojing Cui; Li Li; Jianhui Fan; Jun Cao (Food and Chemical Toxicology, 2025)

Engineering ultrasmall red fluorescent carbon dots for targeted blood-brain barrier crossing, oxidative stress alleviation and mitochondrial repair in cerebral ischemia-reperfusion injury treatment - Jiacheng Xu; Xidong Wu; Xinyue Cao; Shuoxun Chen; Maohua Chen; Zhiwei Li; Hui Hu; Liang Chen; Lipeng Gao; Yu Chen; Jun Sun (Chemical Engineering Journal, 2025)

Excellently stable Camellia oleifera oil Pickering emulsion fabricated based on high carboxyl content cellulose nanofibrils - Jinglin Wu; Xingmei Tang; Wenhua Gao; Jing Li; Jinpeng Li; Daxian Cao; Jinsong Zeng; Bin Wang; Jun Xu; Kefu Chen (Carbohydrate Polymers, 2025)

SIRT1 Attenuates Neuropathic Pain via CDK5-Kalirin-7 Signaling Pathway in Type 2 Diabetic Rats - Cishan Xie; Yannan Cao; Yujing Shen; Shishu Wu; Junwu Wang; Xiuying Ye; Ning Wei; Hong Cao; Jun Li (Molecular Neurobiology, 2025)

Black Soldier Fly Larvae Meal as a Sustainable Fishmeal Substitute for Juvenile Hybrid Grouper: Impacts on Growth, Immunity, and Gut Health - Yan Chen; Wenfeng Li; Minyi Zhong; Jun Ma; Bing Chen; Junming Cao; Jiun-Yan Loh; Hai Huang (Fishes, 2025)
Background: Aquaculture increasingly seeks sustainable alternatives to fishmeal, a key protein source in fish diets. Black Soldier Fly Larvae (BSFL) meal is a promising substitute, but its effects on fish growth, immunity, and gut health need further investigation. This study aimed to evaluate the impact of varying BSFL inclusion levels on juvenile hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂), a widely farmed species in tropical aquaculture. Methods: Juvenile hybrid grouper were fed diets with four levels of BSFL substitution (0%, 10%, 30%, and 50%) over 56 days. Key metrics such as growth performance, immune function, antioxidant capacity, and gut transcriptome were analyzed. Results: Replacing fish meal with BSFL meal had no significant effect on the survival rate of hybrid grouper (p > 0.05) but significantly affected growth performance, immune function, and antioxidant capacity (p

Health risk assessment of source-specific elemental carbon (using dual carbon isotopes) and heavy metals in the Tibetan Plateau - Ju-Lian Shi; Chong-Shu Zhu; Yao Qu; Yue Zhou; Nan Wang; Lu-Yao Wang; Qian Li; Qi-Yuan Wang; Sui-Xin Liu; Jun-Ji Cao (Journal of Hazardous Materials, 2025)

Key toxicity enhancement effect of aqueous-phase secondary formation: Insights from hourly measurements during haze events - Feiyan Cao; Yingjun Chen; Yong Han; Tian Chen; Xinxin Feng; Hongxing Jiang; Qianyu Zhang; Huimin Ma; Jun Li; Gan Zhang (Journal of Hazardous Materials, 2025)

A potent fluorescent probe for HOCl with dual NIR emissions: Achieving the early diagnosis of polystyrene microplastics-induced liver injury involved in ferroptosis - Jianwei Cui; Jiaji Teng; Peini Xiang; Fuyang Liu; Zhixing Cao; Jun Lu; Yun Deng; Yuzhi Li; Cheng Peng; Wim Dehaen; Yuyu Fang (Journal of Hazardous Materials, 2025)

Companion animals as sources of hazardous critically important antimicrobial-resistant Escherichia coli: Genomic surveillance in Shanghai - Yiwen Chen; Min Li; Bingqing Sun; Luming Xia; Yifei Zhang; Jun Feng; Min Chen; Zile Cheng; Chao Lv; Weiye Chen; Jiewen Huang; Qingtian Li; et al. (Journal of Hazardous Materials, 2025)

Emerging contaminants in Taihu lake Basin: Multi-dimensional prioritization, colloidal adsorption, and trophic-level disruptions - Huijin Cao; Jianchao Liu; Wei You; Guanghua Lu; Yiping Li; Jun Hou; Peng Gao (Journal of Environmental Management, 2025)

Targeted modulation of dual-metal ion homeostasis to induce ER stress and cuproptosis for synergistic breast tumor suppression - Xiaoxian Zhang; Xuequan Zhang; Jiahui Zhu; Tinghua Li; Lianyi Yang; Lei Lei; Fang Wu; Bin He; Jun Cao (Chemical Engineering Journal, 2025)

Construction of a shortened autographa californica multiple nucleopolyhedrovirus genome as protein expression vector - Ziqian Cao; Xinyu Liu; Jianchao Li; Yu Zheng; Jun Yin; Hongyu Wang; Xiaoyue Zhang; Hongying Chen (Archives of Virology, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Mangiferin promotes porcine oocyte maturation and delays the postovulatory aging process by up-regulating NRF2 levels - Xiuwen Yuan; Hewei Ji; Yuhao Zhang; Huilin Peng; Neng-hao Cao; Jia-jun Ren; Xue-rui Yao; Xingwei Liang; Nam-hyung Kim; Yong-nan Xu; Ying-hua Li (Theriogenology, 2025)

Reconciling redox proxy contradiction with active Fe Mn shuttle in the Cryogenian Nanhua Basin of South China - Meng Cheng; Zihu Zhang; Jun Hu; Haiyang Wang; Mengchun Cao; Chao Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

Ionic liquid introduced NH2-MIL-53(Al) mixed matrix membrane coupled with UPLC-MS/MS for the simultaneous determination of neonicotinoid insecticides and their metabolites in different samples - Qitong Xu; Huawei Wang; Ding Chen; Meng Yu; Jun Li; Chang Xie; Yan Cao; Lipan Wang; Surong Mei (Food Chemistry, 2025)

Atomevo-odor: A database for understanding olfactory receptor-odorant pairs with multi-artificial intelligence methods - Heng-Yun Zhao; Si-Min Xu; Si-Nuo Xie; Wan-Lin Ye; Jian Li; Lang-Hong Wang; Shi-Lin Cao; Jun-Hu Cheng; Xin-An Zeng; Ji Ma (Food Chemistry, 2025)

LC-MS/MS-based metabolomics and multivariate statistical analysis reveal the mechanism of yeast extracellular proteases on myofibrillar protein degradation, metabolite development and sensory characteristics improvement - Danni Li; Yiqi Liang; Qiang Xia; Daodong Pan; Lihui Du; Jun He; Yangying Sun; Ying Wang; Wei Wang; Jinxuan Cao; Changyu Zhou (Food Microbiology, 2025)

Probabilistic inversion of shear wave velocity profile based on the dispersion curve from multichannel analysis of surface waves and inequality constraints on layer thicknesses - Xuan-Hao Wang; Zi-Jun Cao; Tengfei Wu; Wenqi Du; Dian-Qing Li (Engineering Geology, 2025)

Multilayered cellulose nanofiber/MXene-based dual-mode sensor for monitoring sleep quality and respiratory disorders - Ao Li; Jun Xu; Dezhong Xu; Zhaohui Zhang; Ziji Deng; Daxian Cao; Jun Li; Wei Zhang; Fengshan Zhang (Chemical Engineering Journal, 2025)

In situ reconstructed dual-functional interfacial layer induced by spontaneous vanadium fluoride reaction for highly stable sodium metal batteries - Yue Li; Kang Xu; Weijiang Hu; Ziling Huang; Qing Li; Liang Cao; Minjie Shi; Zhefei Wang; Huaixin Wei; Jun Yang (Chemical Engineering Journal, 2025)

Mendelian randomization and multi-omics analysis identify C4A as a critical protective biomolecule in head and neck squamous cell carcinoma - Ziqing Yang; Xinhui Qiu; Anquan Ma; Chenyang Wu; Xiaoyang Zong; Yifei Nie; Simin Zhan; Haoran Yang; Chengyuan Zhang; Huilu Song; Xu Wang; Zhihong Zhang; et al. (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

70 Years of Development in China’s Operational Numerical Weather Prediction - Weimin Zhang; Xueshun Shen; Xiaoqun Cao; Jian Sun; Jianping Wu; Jun Peng; Junqiang Song; Xiaoqian Zhu; Jianjie Wang; Zechun Li; Dehui Chen; Jiandong Gong; et al. (Journal of Meteorological Research, 2025)

Ecological security and structural optimization of land space in the Pearl River Delta Urban Agglomeration: an approach based on the footprint family - Cong Huang; Jun Liu; Hanyu Yin; Zhonghao Zhang; Wei Cao; Wenfang Tan; Xufeng Fei; Chen Xu; Lumeng Liu; Jiali Chen; Kai Li; Rui Xiao (Environment, Development and Sustainability, 2025)

Comparative spatial transcriptomics reveals root dryland adaptation mechanism in rice and HMGB1 as a key regulator - Liyuan Zhong; Leping Geng; Yimeng Xiang; Xuanmin Guang; Le Cao; Jiawei Shi; Weikun Li; Jianglin Wang; Weiming He; Liyu Huang; Feng Yang; Yi-Xuan Bai; et al. (Molecular Plant, 2025)

Mechanical properties and heavy metals immobilization of lithium slag stabilized by magnesium slag as road subbase material - Xuanhao Cao; Bowen Guan; Jincheng Yu; Jun Li; Wenbo Liu; Hua Zhao; Juanni Nian; Li Dai; Zheng Huang (Journal of Cleaner Production, 2025)

Optimization strategy for Cr(VI) removal in coke-based modular constructed wetlands: A comprehensive analysis of purification efficiency, removal mechanisms, and practical feasibility - Xinlu Xiao; Xuhao Li; Xiangling Zhang; Chen Wang; Xiaoting Liu; Jing Bai; Rong Zhang; Shilong Cao; Jiezhou Hu; Zhenchao Liu; Jun Shen (Journal of Environmental Management, 2025)

ZnCo2O4/LaAlO3 transparent pn junction towards enhanced photoelectric response and stability via interfacial homogeneous high entropy oxide perovskite La(Cu0.2Co0.2Ni0.2Fe0.2Mn0.2)O3 QDs - Bo He; Yujia Huang; Rui Wang; Dingwei Wang; Chengyu Jia; Jun Cao; Lei Shi; Jiaqi Pan; Zhiguo Zhao; Chaorong Li (Chemical Engineering Journal, 2025)

Fully recyclable flame-retardant PLA composites with balanced performance based on a phosphorus/nitrogen-containing zwitterion - Qiang Zhang; Xing Cao; Yan-Peng Ni; Li-Ping Zhang; Zhao Ding; Ying-Jun Xu; Yu-Zhong Wang (Chemical Engineering Journal, 2025)

Anterior Cingulate Cortex Contributes to the Hyperlocomotion under Nitrogen Narcosis - Bin Peng; Xiao-Bo Wu; Zhi-Jun Zhang; De-li Cao; Lin-Xia Zhao; Hao Wu; Yong-Jing Gao (Neuroscience Bulletin, 2025)

Folic Acid-Functionalized Water-Soluble Calixarene for Accurate Identification of Human Breast Cancer Cells - Yafei Zhang; Jianwu Xiao; Jun Cao; Jiaqi Pan; Chaorong Li; Yingying Zheng (Journal of Fluorescence, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Denitrification enhancement, kinetic simulation and microbial assessment in the sponge iron-mediated anammox process: A method for low-strength nitrogen wastewater treatment - Miao Zhang; Zhongkuo Guan; Biao Li; Yufei You; Guihua Cao; Yajun Fan; Jun Wu; Junjie Ji (Journal of Water Process Engineering, 2025)

Nitrogen and phosphorus in water-sediment system of eutrophic lake amended with biochar-supported Effective Microorganisms: Temporal variation and remediation - Siqun Tang; Jilai Gong; Juan Li; Biao Song; Weicheng Cao; Jun Zhao (Journal of Environmental Management, 2025)

Construction of ultra-light and flexible aerogels with superior high oil sorption capacity by controlling the mechanical property of SiO2 nanofibers - Meng-Jie Chang; Ge Bai; Jun Liu; Xin Li; Hui Wang; Shu-Yi Hu; Qiu-Yu Hu; Shi-Shun Cao; Jie Yang (Journal of Environmental Chemical Engineering, 2025)

Effects of spatial distribution of tar-rich coal and oil shale and primary factors on product characteristics during microwave co-pyrolysis - Yan Zhu; Changcong Li; Husheng Cao; Lei Wu; Fu Yang; Shigen Fu; Jun Zhou (Fuel, 2025)

Distribution of different forms of metal ions in Antarctic krill (Euphausia superba) oil: A mechanism of their pro-oxidant effects relating to association colloids - Xinmiao Wang; Dayong Zhou; Fujun Liu; Qian Wang; Chuan Li; Xu Guo; Peiyong Tong; Fawen Yin; Xiaoyang Liu; Jun Cao (Food Chemistry, 2025)

Morphological characteristics and distribution of antennal sensilla of Spodoptera litura (Lepidoptera: Noctuidae) using scanning electron microscopy - Yong-Ping Li; Hai-Yan Zhou; Hui Ye; Robert A. Haack; Yuan Yang; Qiu-Lian Hu; Ming-Min Jiang; Jun Cao (Zoomorphology, 2025)

Sand Production and Critical Rate in Stress-Sensitive Unconsolidated Sandstone: An Experimental Study - Xiao-Hua Tan; Rui Wang; Xiao-Jun Zhou; Yao Zhu; Cai-Shen Li; Bo Cao; Zhi Yang; Hao Chen; Bao-Quan Wen; Liu Tang; Huan-Yu Ran (Geotechnical and Geological Engineering, 2025)

Monthly variations in nutrient utilization along 45°E transect in the Cosmonaut Sea, East Antarctica during austral summer - Xufeng Yang; Dong Li; Jun Zhao; Cai Zhang; Changfeng Zhu; Shunan Cao; Guangfu Luo; Gaojing Fan; Yongming Sun; Ji Hu; Haifeng Zhang; Peisong Yu; et al. (Acta Oceanologica Sinica, 2025)

Influence of austral summer sea ice melting timing on particle fluxes and composition in Prydz Bay, East Antarctica - Changfeng Zhu; Yufei Ding; Wenhao Huang; Jun Zhao; Dong Li; Haifeng Zhang; Yanhong Xu; Cai Zhang; Ji Hu; Shunan Cao; Guangfu Luo; Yongming Sun; et al. (Acta Oceanologica Sinica, 2025)

Paddy fields can gain high productivity with low net global warming potential by utilizing green manure - Shun Li; Jun Nie; Hai Liang; Guopeng Zhou; Jianglin Zhang; Yulin Liao; Yanhong Lu; Yueyue Tao; Songjuan Gao; Weidong Cao (Journal of Environmental Management, 2025)

Ultrasonic-assisted alkali extraction of quinoa polysaccharides: Yield and structural characterization - Huimin Li; Chuyan Li; Yang Xu; Hongwei Cao; Xiangyu Wang; Jun He (Journal of Cereal Science, 2025)

Preparation and antibacterial activity of p-coumaric acid-β-cyclodextrin complex against Alicyclobacillus acidoterrestris in apple juice - Xuemei Meng; Tong Zhang; Jun Li; Xiya Cao; Linan Duan; Haitian Fang; Junnan Xu (Innovative Food Science & Emerging Technologies, 2025)

Saltiness perception enhancement of myofibrillar protein gel via microwave treatment: Microwave promotes protein aggregation - Na Luo; Jun Xiang; Bimal Chitrakar; Die Li; Yuxia Jin; Chaofan Guo; Xingwei Wang; Jianxin Cao; Xuejiao Wang (Innovative Food Science & Emerging Technologies, 2025)

Preparation and characterization of lauric acid-rich wax oleogel chocolates: Insights into crystallization behavior, storage stability, and bloom resistance - Yuting Fu; Yu Chen; Pengyan Li; Chuan Li; Zhiguo Wang; Jun Cao (Food Research International, 2025)

Defective Zn1-xCuxS nanosheet as efficient and durable cathode catalyst for photo-assisted Li-O2 batteries - Cong-Cong Dang; Yi-Ping Liu; Yu-Xin Huang; Xin-Yi Zhang; Zhen-Yi Gu; Jun-Ming Cao; Jin-Zhi Guo; Li-Ming Gao; Xing-Long Wu; Yi-Chun Liu (Chemical Engineering Journal, 2025)

Macrophage-targeted, ROS-removing and H2S-releasing nanomicelle encapsulated in hydrogel microspheres for the treatment of osteoarthritis - Jun Tao; Hui Deng; Zhengnan Li; Liping Cao; Yanfei Rao; Zhanhai Yin (Chemical Engineering Journal, 2025)

Establishing age-group specific reference intervals of human salivary proteome and its preliminary application for epilepsy diagnosis - Nianci Xue; Xia Xia; Yini Wang; Xianju Li; Nairen Zheng; Yi Wang; Baoying Gong; Bin Zhang; Yanjia Chen; Yue Chen; Yanjuan Li; Hong Cao; et al. (Science China Life Sciences, 2025)

Effect of some feed additives on osmoregulation in aquatic animals - Quanquan Cao; Qin Zhang; Shiqi Li; Alkhateib Gaafar; Abdelgayed Metwaly Younes; Khalid Hussain Rind; Haifeng Liu; Jun Jiang (Aquaculture, 2025)

Gypenoside GP5 effectively controls Colletotrichum gloeosporioides, an anthracnose fungus, by activating autophagy - Yujie Liu; Xinyv Li; Chu Gong; Yonghong Cao; Jun Wang; Min Han; Jun-Li Yang (Postharvest Biology and Technology, 2025)

High-performance, breathable, and degradable fully cellulose-based sensor for multifunctional human activity monitoring - Ao Li; Jun Xu; Dezhong Xu; Zhaohui Zhang; Daxian Cao; Jun Li; Wei Zhang; Fengshan Zhang (Chemical Engineering Journal, 2025)

Innovative microbial activators for enhanced bioremediation of oil-contaminated soils: mechanistic insights - Yating Deng; Wujuan Sun; Yongbin Li; Jun Wei; Ruirui Rao; Qiongyu Cao; Sichang Wang; Qunzheng Zhang; Congyu Ke (World Journal of Microbiology and Biotechnology, 2025)

Long-term effects of nitrogen fertilization and Bradyrhizobium inoculation on diazotrophic community structure and diversity in soybean cultivation - Wanling Wei; Mingchao Ma; Xin Jiang; Fenliang Fan; Fangang Meng; Fengming Cao; Huijun Chen; Dawei Guan; Li Li; Jun Li (Applied Soil Ecology, 2025)

Evaluation on the antibacterial activity of glycyrrhizin against Pseudomonas plecoglossicida in ayu fish (Plecoglossus altivelis) - Fan Tao; Jia-Feng Cao; Yan-Jun Liu; Ru-Yi Chen; Jin-Jin Shi; Chang-Yun Li; Jian-Fei Lu; Guan-Jun Yang; Jiong Chen (Aquaculture, 2025)

Crystallinity and dissolution-recrystallization mechanism controlled As(V) retention by calcium phosphate - Yao Yan; Xun Cao; Jun Li; Hanxiao Zhang; Yongqiang Yang; Fanrong Chen; Runliang Zhu; Dong Liu; Tim White; Shijun Wu (Journal of Hazardous Materials, 2025)

Prospective LCA towards achieving carbon neutrality goals: Framework application and challenges - Ya-Xi Fang; Pei-Ze Wu; Sha Chen; Yu Li; Shu-Fen Cui; Jin-Xing Zhu; Hai-Zhou Cao; Ke-Jun Jiang; Ling Zhong (Environmental Impact Assessment Review, 2025)

Simple and efficient geotechnical reliability-based design based on transformed limit state functions by target reliability-oriented sampling - Bin Li; Yong-kai Shen; Zi-Jun Cao; Qi Wan; Chen-Zhe Ma (Computers and Geotechnics, 2025)

Aromatic Chinese medicine-decorated mesoporous nanoenzyme overcomes multiple biological barriers for solid tumor treatment - Xiaolong Quan; Ben Hu; Yibing Li; Iman Zare; Fengyong Cheng; Huiqi Huang; Jun Liu; Peng Cao; Dan Zhou; Meng Yu (Chemical Engineering Journal, 2025)

One-step customized enzyme treatment catalyzes fiber dissociation and application based on structure of Wikstroemia bark - Jian Chen; Bin Wang; Chengliang Duan; Xinkang Huang; Minghong Kui; Jinpeng Li; Jun Xu; Jinsong Zeng; Daxian Cao; Wenhua Gao; Yonghua Wang; Kefu Chen (Chemical Engineering Journal, 2025)

Factors affecting the different growth rates of PM2.5：Evidence from composition variation, formation mechanisms, and importance analysis of water-soluble inorganic ions with case study in northern China - Huan Li; Ting Zhang; Hui Su; Sui Xin Liu; Ying Qiang Shi; Lu Yao Wang; Dong Dong Xu; Jia Mao Zhou; Zhu Zi Zhao; Qi Yuan Wang; Steven Sai Hang Ho; Yao Qu; et al. (Atmospheric Environment, 2025)

Acute heat stress regulates estradiol synthesis in ovine ovarian granulosa cells through the SREBPs/MVK–LHR pathway - Yinxia Li; Fan Li; Jiaao Shu; Chunhua Meng; Jun Zhang; Jianli Zhang; Yong Qian; Huili Wang; Qiang Ding; Shaoxian Cao (Animal Reproduction Science, 2025)

Morphological evolution of the Qingshuigou subaqueous delta of the Yellow River before and after the operation of the Xiaolangdi Reservoir (1997-2007) - Jiarui Zhang; Qing Wang; Chao Zhan; Zilu Li; Yin Cao; Haojian Wang; Zeyang Liu; Limeng Yu; Qiuyu Song; Yan Li; Teng Su; Jun Zhu; et al. (Frontiers in Marine Science, 2024)
The Modern Yellow River Delta has a rich history of geomorphological transformations shaped by frequent avulsions and rapid progradation. However, the delta entered a phase of altered morphodynamics following the construction of the Xiaolangdi Reservoir, which fundamentally restructured sediment transport regimes and seasonal hydrological patterns. These changes have amplified challenges in predicting long-term deltaic evolution under evolving boundary conditions. The Qingshuigou Subaqueous Delta, as a major depositional zone, provides a compelling lens to examine these morphodynamic processes. However, seasonal variations in riverine sand transport fluxes driven by the water-sand regulation scheme that accompanied the construction of the Xiaolangdi Reservoir and its impact on the evolution of the delta front are particularly understudied. This study developed a simplified long-term morphodynamic model of the Qingshuigou Subaqueous Delta to investigate its response to riverine water and sediment discharges from 1997 to 2007. The findings are as follows: (1) The morphological evolution of the Qingshuigou Subaqueous delta has gradually changed from the pattern of “leading edge deposition and localized near-shore erosion” before the construction of the Xiaolangdi Reservoir to the pattern of “enhanced leading edge deposition and increased near-shore erosion” after the construction. (2) The construction of Xiaolangdi Reservoir has weakened the spatial distribution of the erosion process to a certain extent, changing the spatial distribution dominated by the erosion process (63.8% of area) before the construction to the spatial distribution dominated by the accretion process (More than 50% of area) after the construction. (3) The spatial and temporal variability of the incoming sediments leads to a significant coarsening of the grain size of the tidal flats in the southern part of the abandoned delta, which in turn maintains a relatively steady state of the shoreline variability. In contrast, the abandoned sand spit experiences severe erosion and depositional fluctuations due to intensified wave action. (4) The study emphasizes the importance of considering seasonal variations in unsteady discharge in modeling the long-term evolution of the delta. It provides new insights into the spatial and temporal differentiation of the geomorphic equilibrium of the Yellow River Delta and contributes to a broader understanding of delta evolution.

ATF4/PHGDH mediates the effects of ER stress on cadmium-induced autophagy and glycolysis - Yanqiu Yang; Shengnan Li; Yuanxi Yang; Qiujuan Li; Yong Liu; Jun Cao (Toxicology, 2024)

Upcycling of molybdenum tailings, coal gangue and slag into sustainable repaired composites by geopolymerization technology: Workability, embodied carbon and mechanical-microstructural development - Jun Li; Shuang Cao; Qian Su; Hesong Jin; Chang Cai; Lingkun Chen; Jianxing Liu; Tuan Ngo (Sustainable Chemistry and Pharmacy, 2024)

A green and effective glucoside surfactant assisted micellar electrokinetic chromatography for the separation of phenolic compounds from medicinal plant using response surface methodology - Qian-Xue Shen; Yan-Hua Jiao; Xin-Ran Ma; Jun Cao; Li-Hong Ye (Sustainable Chemistry and Pharmacy, 2024)

Remediation of biochar-supported effective microorganisms and microplastics on multiple forms of nitrogenous and phosphorous in eutrophic lake - Siqun Tang; Jilai Gong; Biao Song; Juan Li; Weicheng Cao; Jun Zhao (Science of The Total Environment, 2024)

A comprehensive genetic variant reference for the Chinese population - Tao Jiang; Hongzhe Guo; Yadong Liu; Gaoyang Li; Zhe Cui; Xinran Cui; Yue Liu; Yang Li; Anqi Zhang; Shuqi Cao; Tianyi Zhao; Liran Juan; et al. (Science Bulletin, 2024)

Polycyclic polyprenylated acylphloroglucinols from the pericarps of Garcinia multiflora champ. ex Benth. with cytotoxic property - Jun Cao; Wen-Yu Lyu; Yujia Zhang; Zhicheng Su; Ting Li; Qingwen Zhang; Lishe Gan; Jin-Jian Lu; Ligen Lin (Phytochemistry, 2024)

Synchrotron-based P K-edge XANES spectroscopy reveals the transition of phosphorus cycling in the early Cambrian ocean - Pengcheng Ju; Zhenfei Wang; Chao Chang; Zhangqin Zheng; Run Li; Wenpeng Xia; Xuyang Cao; Yigui Han; Mingyu Zhao; Chao Li; Xingliang Zhang; Kang-Jun Huang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Fluoride removal from coal mining water using novel polymeric aluminum modified activated carbon prepared through mechanochemical process - Yixiang Bao; Yonghui Qi; Qiao Li; Lei Wang; Zhiguo Cao; Jie Li; Min Wu; Jun Chen; Haiqin Zhang; Qiang Guo; Binbin Jiang; Jinkui Zhong; et al. (Journal of Environmental Sciences, 2024)

Chemical profile and sensory evaluation of Cantonese raw soy sauce to reveal the association between taste characteristics and chemical composition - Linfeng Wen; Lixin Yang; Qixin Kan; Peipei Wang; Jun Li; Guo Liu; Liping He; Jiangyan Fu; Qingrong Huang; Chi-Tang Ho; Yong Cao (Food Bioscience, 2024)

Multifunctional biomass-based solar evaporator with enhanced sterilization performance for solar-driven clean water evaporation - Hongbin Cao; Dong Li; Jingjing Fu; Yuxin Yang; Yanyan Zheng; Yuting Que; Xiu He; Haiyan Wang; Jun Liu; Huang Zhou (Desalination, 2024)

Increase of PCSK9 expression in diabetes promotes VEGFR2 ubiquitination to inhibit endothelial function and skin wound healing - Jian-Jun Gao; Fang-Yuan Wu; Yu-Jia Liu; Le Li; Yi-Jun Lin; Yue-Ting Kang; Yue-Ming Peng; Yi-Fang Liu; Chen Wang; Zhen-Sheng Ma; Yang Cao; Hong-Yu Cao; et al. (Science China Life Sciences, 2024)

Deciphering heart failure: an integrated proteomic and transcriptomic approach with experimental validation - Jun Cao; Zhaohai Su; Bilong Zhang; Jiangyong Yang; Yueting Wang; Ling Huang; Gang Cao; Hui Xie; Xiutong Zhong; Hengqing Zhu; Rengui Jiang; Tian Li; et al. (Functional & Integrative Genomics, 2024)

Host preference and mortality caused by the parasitoid Sclerodermus guani on different cerambycid species - Qun Yu; Shuang Li; Yu-Jun Kong; Zuo-Xiang Sun; Dan-Dan Cao; Jian-Rong Wei (BioControl, 2024)

Comparative karyotype analysis provides cytogenetic evidence for the origin of sweetpotato - Jianying Sun; Qian Zhang; Meiling Xu; Mengxiao Yan; Xingyu Liu; Jian Sun; Qinghe Cao; Hongxia Wang; Jun Yang; Zongyun Li; Yonghua Han (Chromosome Research, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Tectonic deformation and kinematics of fluvial terraces marking the northeastern margin of the Tibetan Plateau - Zijuan Dong; Baotian Pan; Zhenbo Hu; David Bridgland; Jun Wang; Rob Westaway; Menghao Li; Qinhong Mo; Xiaohua Li; Xilin Cao; Meiling Zhong; Renzhe Pan (Quaternary Science Reviews, 2024)

Investigating the temporal evolution of physicochemical attributes and flavorome profiles in Sichuan shai vinegar utilizing diverse aging techniques - Li Li; Cuixin Huang; Zhicheng Li; Yulin Zhao; Jun Liu; Yu Zheng; Rong Cao; Yuting Liao (Food Research International, 2024)

Comparative analysis of T-cell immunity between Streptococcus agalactiae susceptible and resistant tilapia (Oreochromis niloticus) - Jiansong Zhang; Ming Geng; Jun Xiao; Liting Chen; Yi Cao; Kang Li; Jialong Yang; Xiumei Wei (Fish & Shellfish Immunology, 2024)

Inflammatory microenvironment activation-targeted self-delivery nanomedicine for effective rheumatoid arthritis treatment - Xinrui Dong; Haibao Liu; Rui Sun; Shuwen Tan; Gaoyang Li; Xuerou Jin; Xiaoqin Zhang; Zhiyi Xiao; Dingxiang Li; Jun-Li Cao; Xiaoran Deng (Chemical Engineering Journal, 2024)

Enhancing medium-chain fatty acids production via alkyl polyglucose modulation of electron acceptor generation, microbial community and metabolic traits in anaerobic fermentation of waste activated sludge - Chun-shuang Zhou; Guang-li Cao; Bing-feng Liu; Guo-jun Xie; Wan-li Ma; Sheng-qiang Fan; Nan-qi Ren (Chemical Engineering Journal, 2024)

Cooking-related thermal comfort and carbon emissions assessment: Comparison between electric and gas cooking in air-conditioned kitchens - Jiajun Li; Shichen Li; Yingqi Zeng; Xiang Zhou; Lingjie Zeng; Meng Liu; Changsheng Cao; Yunfei Xia; Jun Gao (Building and Environment, 2024)

Trichoderma harzianum promoting chrysanthemum cutting rooting and reshaping microbial communities in endophytic and rhizosphere environments - Ya-Jie Wu; Murad Muhammad; Yu Jiao; Xiu Chen; Hai-Long Wang; Chun-Mei Lu; Xiao-Ming Wang; Guo-Xing Zhu; Kai-Qing Liu; Yue Zhang; Zi-Chao Liu; Zhi-Xing Chen; et al. (Applied Soil Ecology, 2024)

Polyamide and deep eutectic solvent assisted matrix solid-phase dispersion microextraction for strong hydrophobic compounds - Yi-Wen Wu; Xin-Ran Ma; Xin Peng; Xudong Cai; Jun Cao; Li-Hong Ye (Sustainable Chemistry and Pharmacy, 2024)

Sulfate-reducing consortium HQ23 stabilizes metal(loid)s and activates biological N-fixation in mixed heavy metal-contaminated soil - Houquan Liu; Jun Yao; Chunyu Shi; Robert Duran; Jianli Liu; Shun Jiang; Miaomiao Li; Wancheng Pang; Bo Ma; Ying Cao; Geoffrey Sunahara (Science of The Total Environment, 2024)

Gigantic gastropods from the Middle Triassic Qingyan biota of Guizhou - Xin Sun; Li Tian; Chuan-Yuan Liu; Xiao He; Dao-Liang Chu; Xue Miao; Shi-Yan Zhang; Yi-Ran Cao; Pei-Shan Li; Jin-Nan Tong; Hai-Jun Song (Palaeoworld, 2024)

Freshwater microconchids from the Tanzhuang Formation (Middle-Late Triassic) in North China - Hao Yang; Yue Su; Hui-Jun Chen; Yi-Ran Cao; Meng-Yang Zhang; Rui Li; Dao-Liang Chu (Palaeoworld, 2024)

Multicomponent nanoparticles decorating lignin-derived biochar composite for 4-nitrophenol sensing - Tianshuang Bao; Qi Wang; Yuhang Jiang; Xiangchuan Zhao; Yue Cao; Jun Cao; Qiaoling Li; Xingxiang Ji; Weimeng Si (Journal of Environmental Chemical Engineering, 2024)

Sludge-based biochar preparation: pyrolysis and co-pyrolysis methods, improvements, and environmental applications - Jun Cao; Yutong Jiang; Xiao Tan; Lei Li; Songshan Cao; Jiayao Dou; Runqi Chen; Xiaoyun Hu; Zhiheng Qiu; Ming Li; Ziyin Chen; Hualun Zhu (Fuel, 2024)

Dihydroartemisinin regulates the apoptosis and growth of colorectal cancer by suppressing DPYSL2 and increasing TF and ACHE - Xiao Zhang; Jun-Feng Cao; Dunshui Liao; Zengliang Xia; Li Xiong; Mei Wu; Chaochao Wang; Xingyu Yang; Yixin Qiu; Lixin Zhang; Ningbo Chen; Ming Zhang; et al. (Food Bioscience, 2024)

Three-dimensional CNTs boosting the conductive confinement structure of silicon/carbon anodes in lithium-ion batteries - Xingchi Zou; Ming Li; Hao Li; Guiqiang Cao; Qinting Jiang; Ruixian Duan; Huaming Qian; Jun Li; Xiaoli Yang; Yanyan Cao; Jingjing Wang; Haoqi Li; et al. (Chemical Engineering Journal, 2024)

Fluorinated ionic liquid mediated nanostructure with enhanced conductivity and fluorine retention in Na3V2(PO4)2F3 cathode toward high-performance sodium-ion batteries - Yang Yan; Jun-Qing Xu; Jun-Ming Cao; Han-Wei Huang; Sen-Sen Xue; Guang-Lan Li; An-Min Liu; Cheng-Jie Li; Dongmei Dai; Bao Li; Xing-Long Wu (Chemical Engineering Journal, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

High-performance solar water purification enabled by controlled water convection in integrated porous aerogel multistage distiller - Chengcheng Li; Zhen Li; Peng Zhu; Weihua Mao; Yecheng Wang; Shishi Lin; Yang Cao; Jun Liu; Mingxin Zhang; Shuyi Huang; Wei Huang (Chemical Engineering Journal, 2024)

UV light absorption at 370 nm by mineral dust, organic carbon, and elemental carbon in the Himalayas and Tibetan Plateau - Chong-Shu Zhu; Yao Qu; Yue Zhou; Nan Wang; Hong Huang; Ting Zhang; Xiao-Li Su; Jun-Ji Cao (Atmospheric Environment, 2024)

A Framework for Quantifying Stormwater Control Measures’ Hydrologic Performance with Analytical Stochastic Models - Jiachang Wang; Jun Wang; Shengle Cao; Chuanqi Li; Shouhong Zhang; Yiping Guo (Water Resources Management, 2024)

A general climatology of categorized Martian ionospheric irregularities - Xin Wan; Jiahao Zhong; Yongqiang Hao; Chao Xiong; Hui Wang; Yutian Cao; Jun Cui; Yiwen Liu; Qiaoling Li; Jiawei Kuai (Science China Earth Sciences, 2024)

Deciphering the evolutionary development of the “Chinese lantern” within Solanaceae - Lanfeng Wu; Qianqian Liu; Wei Gou; Jun Li; Qianhui Cao; Chaoying He (Planta, 2024)

Applications of multi-omics techniques to unravel the fermentation process and the flavor formation mechanism in fermented foods - Linfeng Wen; Lixin Yang; Cong Chen; Jun Li; Jiangyan Fu; Guo Liu; Qixin Kan; Chi-Tang Ho; Qingrong Huang; Yaqi Lan; Yong Cao (Critical Reviews in Food Science and Nutrition, 2024)

Bi2MoO6/MWCNTs-COOH/GCE electrochemical probe for ultrasensitively and selectively detecting antibiotic norfloxacin - Shuting Shi; Chuanqin Zhou; Aiting Chen; Nana Tang; Kun Wan; Youwei Jiang; Jun Liu; Quanguo He; Li Cao (Chemosphere, 2024)

HMGA2-mediated glutamine metabolism is required for Cd-induced cell growth and cell migration - Yanqiu Yang; Chunpeng Gao; Qiujuan Li; Yong Liu; Jun Cao (Toxicology, 2024)

Climatic-hydrologic influence on redox condition in the Cryogenian interglacial Nanhua Basin: Insights from the Datangpo Formation in the northwestern Yangtze Block, South China - Guangyao Cao; Guanglu Zhang; Yanyan Zhao; Tongshan Wang; Yu Liu; Qiufen Li; Xiaoqiang Guo; Zhishun Zhang; Lei Yang; Sheng Liu; Jun Yang; Haotian Wei (Precambrian Research, 2024)

Impacts of wastewater treatment plant effluents on dissolved inorganic carbon in highly urbanized karst rivers, Southwest China - Guangxi Long; Y. Jun Xu; Xingxing Cao; Pan Wu; Kai Li (Journal of Hydrology, 2024)

A thermal infrared imaging observation system for the measurement of overland flow velocities under controlled laboratory conditions - Haijing Shi; Yan Zhang; YouFu Wu; Xihua Yang; Baoyuan Liu; Minghang Guo; Jun Zhao; Junfeng Shui; Xiaoping Cao; David Paull; Li Li (Journal of Hydrology, 2024)

Natural harmaline acts as novel fluorescent probe for hypochlorous acid and promising therapeutic candidate for rheumatoid arthritis - Dongbin Zheng; Yi Zuo; Longxuan Li; Arlene McDowell; Yuening Cao; Xiaoping Ye; Houcheng Zhou; Cheng Peng; Yun Deng; Jun Lu; Yuyu Fang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Carbonization of bacterial cellulose with structure retention and Nitrogen/Sulfur/Oxygen doping for application in supercapacitors electrode - Yan Wu; Bin Wang; Jinpeng Li; Daxian Cao; Jun Xu; Jinsong Zeng; Wenhua Gao; Xingxiang Ji; Kefu Chen (Chemical Engineering Journal, 2024)

Harnessing bimetallic iMWA nanosensitizer to unleash ferroptosis and calcium overload: Unlocking tumor vulnerability for potentiated iMWA therapy against hepatocellular carcinoma - Guanhua Qiu; Duo Wang; Peihan Xie; Zelun Li; Niqiang Zhou; Xiaoqian Zhang; Xiaobo Wang; Jiali Tang; Jun Cao; Junjie Liu; Danke Su (Chemical Engineering Journal, 2024)

Insights on the degradation mechanism of neotame using UV/periodate: Roles of reactive species, kinetics, and pathways - Junhui Yue; Wei Guo; Yuhan Zhu; Dongyue Li; Shengxu Liang; Ruiyuan Cao; Andong Wang; Jun Li (Chemical Engineering Journal, 2024)

Functional Abnormality of the Reward System in Depressed Adolescents and Young Adults with and without Suicidal Behavior - Haitang Qiu; Jun Cao; Rui Wang; Xinke Li; Li Kuang; Zhubin Ouyang (Brain Topography, 2024)

Influence of climate extremes on long-term changes in cyanobacterial blooms in a eutrophic and shallow lake - Jun Yuan; Zhigang Cao; Jinge Ma; Yimin Li; Yinguo Qiu; Hongtao Duan (Science of The Total Environment, 2024)

Effects of different proportions of fruit tree branches on nicotine content and microbial diversity during composting of tobacco waste - Xiaoping Zhu; Jiali Yuan; Haoli Qu; Fuen Hou; Chunlong Mao; Jun Lei; Xiuli Cao; Lei Li (Journal of Environmental Management, 2024)

Zero-strain Co-doped Na2FeP2O7/carbon delivers superior rate capability and long-cycle stability for sodium ion batteries - Jianhong Gao; Ziwei Chen; Wei Cao; Jiale Chen; Ming Zhang; Feng Lin; Yongsheng Li; Waqar Ahmad; Min Ling; Chengdu Liang; Jun Chen (Chemical Engineering Journal, 2024)

Photoluminescence-Tunable organic phosphine cuprous halides clusters for X-ray scintillators and white light emitting diodes - Jun’an Lai; Chen Li; Zixian Wang; Linfeng Guo; Yijia Wang; Kang An; Sijun Cao; Daofu Wu; Zhengzheng Liu; Zhiping Hu; Yuxin Leng; Juan Du; et al. (Chemical Engineering Journal, 2024)

A novel HMGA2/MPC-1/mTOR signaling pathway promotes cell growth via facilitating Cr (VI)-induced glycolysis - Siyang Zhao; Yahui Zhang; Shibo Bao; Liping Jiang; Qiujuan Li; Ying Kong; Jun Cao (Chemico-Biological Interactions, 2024)

Optimizing biochar addition strategies in combined processes: Comprehensive assessment of earthworm growth, lignocellulose degradation and vermicompost quality - Jun Li; Sheng Liu; Yang Xu; Chao Xu; Bo Deng; Hongliang Cao; Qiaoxia Yuan (Bioresource Technology, 2024)

Exploration of the molecular mechanism of tea polyphenols against pulmonary hypertension by integrative approach of network pharmacology, molecular docking, and experimental verification - Huan Yang; Jun Cao; Jian-Min Li; Cheng Li; Wen-Wu Zhou; Jin-Wen Luo (Molecular Diversity, 2024)

Mechanisms of polyphenols on quality control of aquatic products in storage: A review - Zhiliang Huang; Qi Wang; Jun Cao; Dayong Zhou; Chuan Li (Critical Reviews in Food Science and Nutrition, 2024)

Curcumin-loaded biomimetic nanosponges for osteoarthritis alleviation by synergistically suppressing inflammation and ferroptosis - Huihui Xu; Su Liu; Yihao Wei; Siyang Cao; Jiapeng Deng; Guoqing Li; Weibei Sheng; Tiantian Qi; Peng Zhang; Jianjing Lin; Jian Weng; Fei Yu; et al. (Chemical Engineering Journal, 2024)

Ultrasmall copper nanodots eye drops for microenvironment regulation of diabetes retinopathy by relieving hypoxia and inhibiting HIF-1α/VEGF signaling pathway - Min Tian; Zheng Li; Siyan Liu; Zhiyuan Wang; Bo Deng; Yang Cao; Jinchuan Wu; Zhu Zhu; Jun Jiang; Guang Li; Hongbin Lv (Chemical Engineering Journal, 2024)

Constant static pressure strategy for residential kitchen exhaust system: Deducing control parameters from required exhaust rate and non-distributed data transmission - Qianwei Liang; Yanlei Yu; Changsheng Cao; Yumei Hou; Jiaying Zhou; Jun Gao; Bin Li; Jiahua Wang (Building and Environment, 2024)

Coupled processes involving ammonium inputs, microbial nitrification, and calcite dissolution control riverine nitrate pollution in the piedmont zone (Qingshui River, China) - Jun Li; Haoyang Liu; Hongwei Pei; Wei Liu; Guoli Yang; Yincai Xie; Shengwei Cao; Jiawei Wang; Lishan Ma; Hengxing Zhang (Science of The Total Environment, 2024)

Insights into anthropogenic impact on atmospheric inorganic aerosols in the largest city of the Tibetan Plateau through multidimensional isotope analysis - Xueqin Zheng; Junwen Liu; Bingqian Zhong; Yujing Wang; Zeyan Wu; Nima Chuduo; Bian Ba; Xin Yuan; Meiyi Fan; Fang Cao; Yanlin Zhang; Weihua Chen; et al. (Science of The Total Environment, 2024)

Preparation of slag-based foam concrete and its carbon dioxide sequestration performance - Jing Zhao; Yu-qing Li; Jing-jing Yang; Xiao-qiang Cao; Jun-xiang Wang; Gang Wang; Lu-lu Sun; Qi-ming Huang; Wei-min Cheng; Zhi-wen Lyu (International Journal of Greenhouse Gas Control, 2024)

Targeted preparation of six rare ginsenosides using two β-glucosidases from Bifidobacterium adolescentis - Yanbo Hu; Yiming Li; Yuzhu Shen; Baochun Zhang; Jiaxin Liu; Yi Cao; Jun Zhao (Food Bioscience, 2024)

Altered individual gray matter structural covariance networks in early abstinence patients with alcohol dependence - Hai-ling Cao; Ya-jing Meng; Wei Wei; Tao Li; Ming-li Li; Wan-jun Guo (Brain Imaging and Behavior, 2024)

Biotransformation of Pb and As from sewage sludge and food waste by black soldier fly larvae: Migration mechanism of bacterial community and metalloregulatory protein scales - Bo Deng; Junlong Luo; Chao Xu; Xin Zhang; Jun Li; Qiaoxia Yuan; Hongliang Cao (Water Research, 2024)

The formation mechanism, analysis strategies and regulation measures of cereal aroma: A review - Yao Feng; Hongwei Cao; Hongdong Song; Kai Huang; Yu Zhang; Ying Zhang; Sen Li; Yingjie Li; Jun Lu; Xiao Guan (Trends in Food Science & Technology, 2024)

Co-influence of biochar-supported effective microorganisms and seasonal changes on dissolved organic matter and microbial activity in eutrophic lake - Siqun Tang; Jilai Gong; Biao Song; Juan Li; Weicheng Cao; Jun Zhao (Science of The Total Environment, 2024)

PcPME63 is involved in fruit softening during post-cold storage process of European pear (Pyrus communis L.) - Beibei Cao; Rongxiang Zhu; Manyi Sun; Bobo Song; Jun Wu; Jiaming Li (Postharvest Biology and Technology, 2024)

The bZIP transcription factor MpbZIP9 regulates anthocyanin biosynthesis in Malus ‘Pinkspire’ fruit - Mingkun Chen; Xiaoyun Cao; Yuanxing Huang; Wenting Zou; Xiaolong Liang; Yue Yang; Yu Wang; Jun Wei; Houhua Li (Plant Science, 2024)

Role of bipyridyl in enhancing ferrate oxidation toward micropollutants - Juan Li; Jiachun Cao; Maoju Jiang; Linqian An; Ge Zeng; Jiamin Mai; Peng Su; Binghua Jing; Mingbao Feng; Zhimin Ao; Jun Ma; Tao Yang (Journal of Hazardous Materials, 2024)

Mitochondria immobilized carbonized polymer dots for ratio-metric tracking mitophagy - Xueting Luo; Wentao Xiang; Yi Lu; Erjing Wang; Jun You; Cao Li; Ziqiang Xu (Chemical Engineering Journal, 2024)

Self-cleaning transparent pn junction in CuAlO2/WO3 via high entropy perovskite oxide La(Cu0.2Cr0.2Ni0.2Fe0.2Co0.2)O3 transition layer for enhanced photovoltaic conversion - Pengjie Zhang; Yiwei shi; Yujie Zhang; Shouzhe Feng; Lei Shi; Jiaqi Pan; Jun Cao; Chaorong Li (Chemical Engineering Journal, 2024)

Inhibition of human UDP-glucuronosyltransferase enzyme by entrectinib: Implications for drug-drug interactions - Hang Yin; Zhe Wang; Xin Lv; Zhen Wang; Ying Wang; Wenxuan Fan; Shuang Li; Lili Jiang; Jun Cao; Yong Liu (Chemico-Biological Interactions, 2024)

Testing for adaptive changes linked to range expansion following a single introduction of the fall webworm - Jin‐Xu Dai; Li‐Jun Cao; Jin‐Cui Chen; Fangyuan Yang; Xiu‐Jing Shen; Li‐Jun Ma; Ary Anthony Hoffmann; Min Chen; Shu‐Jun Wei (Molecular Ecology, 2024)
Adaptive evolution following colonization can affect the impact of invasive species. The fall webworm (FWW) invaded China 40 years ago through a single introduction event involving a severe bottleneck and subsequently diverged into two genetic groups. The well‐recorded invasion history of FWW, coupled with a clear pattern of genetic divergence, provides an opportunity to investigate whether there is any sign of adaptive evolution following the invasion. Based on genome‐wide SNPs, we identified genetically separated western and eastern groups of FWW and correlated spatial variation in SNPs with geographical and climatic factors. Geographical factors explained a similar proportion of the genetic variation across all populations compared with climatic factors. However, when the two population groups were analysed separately, environmental factors explained more variation than geographical factors. SNP outliers in populations of the western group had relatively stronger response to precipitation than temperature‐related variables. Functional annotation of SNP outliers identified genes associated with insect cuticle protein potentially related to desiccation adaptation in the western group and genes associated with lipase biosynthesis potentially related to temperature adaptation in the eastern group. Our study suggests that invasive species may maintain the evolutionary potential to adapt to heterogeneous environments despite a single invasion event. The molecular data suggest that quantitative trait comparisons across environments would be worthwhile.

Two gene clusters and their positive regulator SlMYB13 that have undergone domestication-associated negative selection control phenolamide accumulation and drought tolerance in tomato - Peng Cao; Jun Yang; Linghao Xia; Zhonghui Zhang; Zeyong Wu; Yingchen Hao; Penghui Liu; Chao Wang; Chun Li; Jie Yang; Jun Lai; Xianggui Li; et al. (Molecular Plant, 2024)

Phylogenomic analyses sheds new light on the phylogeny and diversification of Corydalis DC. in Himalaya–Hengduan Mountains and adjacent regions - Yan-Yan Liu; Jia-Liang Cao; Sheng-Long Kan; Peng-Hang Wang; Jun-Li Wang; Ya-Nan Cao; Hong-Wei Wang; Jia-Mei Li (Molecular Phylogenetics and Evolution, 2024)

Unraveling the generation mechanism of singlet oxygen in Bi2WxMo1-xO6 solid solution and roles in photocatalytic degradation of gaseous toluene under visible-light irradiation - Shaobo Cao; Lei Wu; Jun Li; Yang Li; Kang Da; Wenting Chen; Ruiting Xue; Jian Yang; Ximei Fan (Journal of Environmental Chemical Engineering, 2024)

Metagenomics and untargeted metabolomics analyses to unravel the formation mechanism of characteristic metabolites in Cantonese soy sauce during different fermentation stages - Linfeng Wen; Jianping Lei; Lixin Yang; Qixin Kan; Peipei Wang; Jun Li; Cong Chen; Liping He; Jiangyan Fu; Chi-Tang Ho; Qingrong Huang; Yong Cao. (Food Research International, 2024)

Comparative analysis of DHA positional distribution and triacylglycerol molecular species in algal oil (Schizochytrium sp.) from different oil processing - Lingzhi Shen; Feng Li; Chenyu Jiang; Xi Cao; Jun Jin; Xingguo Wang; Wei Wei (Food Bioscience, 2024)

Integration of genome-wide association and genomic prediction for dissecting seed protein and amino acid in foxtail millet - Xiongwei Zhao; Yanhua Cao; Litao Shao; Jie Zhang; Jian Cui; Jun Shu; Juanling Wang; Mingjing Huang; Jianhua Gao; Xingchun Wang; Xukai Li; Guofang Xing; et al. (Field Crops Research, 2024)

Tailor-Made Homo/Heterojunction engineering of CdS@Prussian blue via One-Pot kinetic regulation for photoreduction of uranium (VI) from radioactive wastewater - Hao Ye; Rou-Ming Wen; Ming-Bang Wu; Zi-Hao Yuan; Jun Cao; Chaorong Li; Juming Yao (Chemical Engineering Journal, 2024)

Effects of different ecological restoration methods on the soil bacterial community structure of a light rare earth tailings pond - Tianyu Chen; Ning Qu; Jinxiao Wang; Yaochen Liu; Jiao Feng; Shilei Zhang; Chunying Xu; Zhiquan Cao; Jun Pan; Chunlin Li (Plant and Soil, 2024)

Effects of lianas on forest biogeochemistry during their lives and afterlives - Gbadamassi G. O. Dossa; Hong‐Lin Li; Bo Pan; Tial C. Ling; Douglas A. Schaefer; Mareike Roeder; Denis M. Njoroge; Juan Zuo; Liang Song; Bismark Ofosu‐Bamfo; Stefan A. Schnitzer; Rhett D. Harrison; et al. (Global Change Biology, 2024)
Climate change and other anthropogenic disturbances are increasing liana abundance and biomass in many tropical and subtropical forests. While the effects of living lianas on species diversity, ecosystem carbon, and nutrient dynamics are receiving increasing attention, the role of dead lianas in forest ecosystems has been little studied and is poorly understood. Trees and lianas coexist as the major woody components of forests worldwide, but they have very different ecological strategies, with lianas relying on trees for mechanical support. Consequently, trees and lianas have evolved highly divergent stem, leaf, and root traits. Here we show that this trait divergence is likely to persist after death, into the afterlives of these organs, leading to divergent effects on forest biogeochemistry. We introduce a conceptual framework combining horizontal, vertical, and time dimensions for the effects of liana proliferation and liana tissue decomposition on ecosystem carbon and nutrient cycling. We propose a series of empirical studies comparing traits between lianas and trees to answer questions concerning the influence of trait afterlives on the decomposability of liana and tree organs. Such studies will increase our understanding of the contribution of lianas to terrestrial biogeochemical cycling, and help predict the effects of their increasing abundance.

Induced Mesenchymal Stem Cells-Small Extracellular Vesicles Alleviate Post-stroke Cognitive Impairment by Rejuvenating Senescence of Neural Stem Cells - Jiayuan Liu; Li Peng; Lingwei He; Tianyue Yin; Yuhao Du; Mengmeng Yang; Ping Wu; Jun Li; Jiangbing Cao; Hongrui Zhu; Sheng Wang (Journal of Molecular Neuroscience, 2024)

Glyphosate exposure affected longevity-related pathways and reduced survival in asian honey bees (Apis cerana) - Dong Zhi-Xiang; Li Wan-Li; LI Xi-Jie; Li Jia-Li; Zhang Jun; Zhao Chong-Hui; Huang Qi; Cao Zhe; Chen Yuan; Zhao Hong-Mu; Guo Jun; Tian Wen-Li (Chemosphere, 2024)

Deciphering the biotic and abiotic drivers of coalescence asymmetry between soil and manure microbiomes - Chunkai Li; Xianping Li; Sana Romdhane; Yanhong Cheng; Gen Li; Rui Cao; Peng Li; Jingjing Xu; Yexin Zhao; Yang Yang; Jiaguo Jiao; Feng Hu; et al. (Science of The Total Environment, 2024)

Knockdown of TXNIP alleviates gestational diabetes mellitus by activating autophagy to regulate cell proliferation and apoptosis in high glucose-treated trophoblasts - Ying Gu; Minkai Cao; Yu Chen; Jingyang Li; Lingli Hu; Xiao-Jun Yang (Reproductive Biology, 2024)

Design and analysis of a novel oscillating flow generator connected to an offshore wind turbine tower - Wei Jun Zhu; Shu Qing Zhuang; Zhen Ye Sun; Ye Li; Jiu Fa Cao; Wen Zhong Shen (Ocean Engineering, 2024)

Contrasting response strategies of sulfate-reducing bacteria in a microbial consortium to As3+ stress under anaerobic and aerobic environments - Miaomiao Li; Jun Yao; Yating Wang; Geoffrey Sunahara; Robert Duran; Jianli Liu; Bang Liu; Houquan Liu; Bo Ma; Hao Li; Wancheng Pang; Ying Cao (Journal of Hazardous Materials, 2024)

Enzymatic hydrolysis of oat core flour improves physiochemical and sensory behaviors for oat milk - Min Zhang; Kai Huang; Jun Lu; Anni Lu; Xiao Guan; Yu Zhang; Sen Li; Hongdong Song; Hongwei Cao; Zhu Sun; Zhiquan Yu (Journal of Cereal Science, 2024)

Regulatory effect of trehalose metabolism on chitin synthesis in Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) as determined using RNAi - Yan-qi Yang; Yu-jian Liang; Jun-rui Zhi; Ding-yin Li; Cao Li (Journal of Asia-Pacific Entomology, 2024)

Degradation of typical flotation reagents using lead-zinc smelting slag as mediator for persulfate activation: Effect of gallic acid and Cr(VI) on the removal performance and fate of reactive oxygen species - Wancheng Pang; Jun Yao; Tatjana Šolević Knudsen; Ying Cao; Bo Ma; Hao Li; Miaomiao Li; Bang Liu (Environmental Pollution, 2024)

Impacts of one-time large amounts of leafy vegetable waste incorporated into dryland fields on soil fertility and forage maize production - Yin Ba; De-cao Niu; Jun Lei; Li-yuan Zhao; Dan-dan Liu; Xiao Song; Wei Xue; Feng-Min Li (European Journal of Agronomy, 2024)

Ultrasoft bioadhesive hydrogel as a versatile platform for the delivery of basic fibroblast growth factor to repair traumatic brain injury - Bixin Shen; Junhui Wang; Tao He; Shihao Chen; Xue Wang; Jun Chen; Ruiqing Shi; Jing Wang; Hao Wang; Wenting Huang; Chengkun Cao; Xianxi Tan; et al. (Chemical Engineering Journal, 2024)

Response of soil aggregation and associated organic carbon to organic amendment and its controls: A global meta-analysis - Shihao Ma; Yudong Cao; Jianwei Lu; Tao Ren; Rihuan Cong; Zhifeng Lu; Jun Zhu; Xiaokun Li (CATENA, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Advances in the study of protein folding and endoplasmic reticulum-associated degradation in mammal cells - Hong Cao; Xuchang Zhou; Bowen Xu; Han Hu; Jianming Guo; Yuwei Ma; Miao Wang; Nan Li; Jun Zou (Journal of Zhejiang University-SCIENCE B, 2024)

Advances in the study of mitophagy in osteoarthritis - Hong Cao; Xuchang Zhou; Bowen Xu; Han Hu; Jianming Guo; Miao Wang; Nan Li; Jun Zou (Journal of Zhejiang University-SCIENCE B, 2024)

Effects of different ecological restoration methods on the soil physicochemical properties and vegetation community characteristics of the Baotou light rare earth tailings pond in Inner Mongolia, China - Tianyu Chen; Ning Qu; Jinxiao Wang; Yaochen Liu; Jiao Feng; Shilei Zhang; Chunying Xu; Zhiquan Cao; Jun Pan; Chunlin Li (Environmental Science and Pollution Research, 2024)

Treatment of volatile organic compounds and other waste gases using membrane biofilm reactors: A review on recent advancements and challenges. - Ziqing Wu; Xiwei Cao; Ming Li; Jun Liu; Baoan Li (Chemosphere, 2024)

Stepwise extraction and utilization of silica and alumina from coal fly ash by mild hydrothermal process - Lang Xing; Xinran Li; Pengxu Cao; Jun Luo; Hao Jiang (Process Safety and Environmental Protection, 2024)

Black shale LA-ICP-MS Rb-Sr and monazite SIMS U-Pb geochronology from the Cryogenian successions in the northern Yangtze Block - Zhongwu Lan; Kyle Larson; Rong Cao; Qin Ye; Jun Hu; Guoqiang Tang; Jiao Li; Jinnan Tong (Precambrian Research, 2024)

Shale oil potential and mobility in low- to medium-maturity lacustrine shales: A case study of the Yanchang Formation shale in southeast Ordos Basin, China - Huairen Cao; Jun Shi; Zhao-Wen Zhan; Hao Wu; Xiaoyu Wang; Xin Cheng; Haolin Li; Yan-Rong Zou; Ping'an Peng (International Journal of Coal Geology, 2024)

Direct conversion of carbon dioxide into light olefins over ZnZrOx/ZSM-5@n-ZrO2 tandem catalyst - Ying Wang; Shike Liu; Jiamin Wang; Fei Liu; Jun Ma; Mengqin Yao; Shuo Geng; Jianxin Cao; Ziwei Li (Fuel, 2024)

Facile preparation of biomimetic mineralized COFs based on magnetic silk fibroin and its effective extraction of sulforaphane from cruciferous vegetables - Guangyang Liu; Xuan Zhang; Jian Wang; Lingyun Li; Jiayong Cao; Chen Yin; Yuan Liu; Ge Chen; Jun Lv; Xiaomin Xu; Jing Wang; Xiaodong Huang; et al. (Food Chemistry, 2024)

Effect of variation in basic emulsion structure and polysaccharide content on the physicochemical properties and structure of composite-based emulsion gels as cube fat mimetics - Yuqing Ren; Lai Wei; Jun Hao Yoong; Zhiyue Miao; He Li; Jinnuo Cao; Xinqi Liu (Food Chemistry, 2024)

Unravelling the synergistic effect of incorporation of β-glucan and high intensity ultrasound treatment on the stability of highland barley milk - Hongwei Cao; Ranqing Li; Sen Li; Hongdong Song; Kai Huang; Yu Zhang; Jun Lu; Xiao Guan (Food Hydrocolloids, 2024)

Effects of dietary chitosan oligosaccharide on the growth, intestinal microbiota and immunity of juvenile red claw crayfish (Cherax quadricarinatus) - Ze-Long Zhang; Yan-Lei Cao; Jia-Rui Xu; Xiu-Xia Zhang; Jia-Jun Li; Jun-Tao Li; Pei-Hua Zheng; Jian-An Xian; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Structural elucidation of an active polysaccharide from Radix Puerariae lobatae and its protection against acute alcoholic liver disease - Wen Cao; Jiangping Wu; Xinya Zhao; Zixu Li; Jie Yu; Taili Shao; Xuefeng Hou; Lutan Zhou; Chunfei Wang; Guodong Wang; Jun Han (Carbohydrate Polymers, 2024)

The role of corneal endothelium in macular corneal dystrophy development and recurrence - Bi-Ning Zhang; Benxiang Qi; Chunxiao Dong; Bin Zhang; Jun Cheng; Xin Wang; Suxia Li; Xiaoyun Zhuang; Shijiu Chen; Haoyun Duan; Dewei Li; Sujie Zhu; et al. (Science China Life Sciences, 2024)

Effects of tillage practices on soil organic carbon, microbial community and necromass in a double rice cropping system - Jian-Ying Qi; Xiang-Bin Yao; Xue-Chan Zhang; Mei-Yi Fan; Jian-Fu Xue; Jun-Li Cao; Ahmad Latif Virk; Sheng-Gang Pan; Xiang-Ru Tang (Applied Soil Ecology, 2024)

Development and experimental validation of a machine learning-based disulfidptosis-related ferroptosis score for hepatocellular carcinoma - Cong Zhang; Tiantian Xu; Kun Ji; Shoujin Cao; Jing Ai; Junhan Pan; Yunbo Cao; Yuning Yang; Li Jing; Jun-Hui Sun (Apoptosis, 2024)

Simulating arsenic discharge flux at a relic smelting site in Guangxi Zhuang Autonomous Region, China - Zhenzhong Huang; Fengyan Li; Weihua Cui; Guoliang Cao; Jun Yao (Environmental Science and Pollution Research, 2024)

Vitamin D3 activates the innate immune response and xenophagy against Nocardia seriolae through the VD receptor in liver of largemouth bass (Micropterus salmoides) - Quanquan Cao; Ju Zhao; Mingyao Yan; Zhong Luo; Fu Luo; Lin Feng; Weidan Jiang; Pei Wu; Yan Wang; Debin Li; Haifeng Liu; Jun Jiang (Aquaculture, 2024)

Anisotropic Rayleigh wave tomography revealed lithospheric modification and tectonic deformation mechanisms in Hubei Province, central China - Tengfei Wu; Zi-Jun Cao; Mengkui Li; Shuangxi Zhang; Liping Qin (Tectonophysics, 2024)

Assessment of heavy metals concentrations in five marine organisms from Lianyungang in China and the corresponding health risk - Ya-Qin Zhang; Chun-Hui Gong; Xiang-Hua Qi; Wen-Jun Wang; Peng-Tao Cao; Qiang Li; Peng Wang; Yi Yang (Regional Studies in Marine Science, 2024)

Insights into the mechanism of extracellular proteases from Penicillium on myofibrillar protein hydrolysis and volatile compound evolutions - Zimu Li; Danni Li; Daodong Pan; Qiang Xia; Yangying Sun; Lihui Du; Jun He; Changyu Zhou; Fang Geng; Jinxuan Cao (Food Research International, 2024)

Synthesis of an autochthonous microbial community by analyzing the core microorganisms responsible for the critical flavor of bran vinegar - Li Li; Na Li; Junjie Fu; Jun Liu; Xue Ping Wen; Hong Cao; Hongwei Xu; Ying Zhang; Rong Cao (Food Research International, 2024)

Enhanced immobilization of cadmium in contaminated paddy soil by biochar-supported sulfidized nanoscale zero-valent iron - Yiqun Xu; Shan Cao; Xinyu Chen; Jun Li; Hongdou Liu; Yang Gao; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Wenjing Xue (Journal of Soils and Sediments, 2024)

Biomolecular insights into the inhibition of heavy metals on reductive dechlorination of 2,4,6-trichlorophenol in Pseudomonas sp. CP-1 - Di Cao; Xueqi Chen; Jun Nan; Aijie Wang; Zhiling Li (Water Research, 2023)

Effects of arsenic exposure on trace element levels in the hippocampus and cortex of rats and their gender differences - Xi Yan; Jun Zhang; Junyu Li; Xinglai Zhang; Yi Wang; Xiaolu Chen; Peng Luo; Ting Hu; Xueshan Cao; Hongbin Zhuang; Xiaoxiao Tang; Fang Yao; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

Preparation and antibacterial activity of Ag-loaded tobermorite derived from coal fly ash - Hao Jiang; Xinran Li; Zhilong Liu; Xin Zhang; Pengxu Cao; Jun Luo (Journal of Environmental Chemical Engineering, 2023)

Integrated multifunctional nanoplatform for fluorescence detection and inactivation of Staphylococcus aureus - Jing-bo Jiao; Qing Kang; Jiang-li Cao; Shuai-qi Zhang; Chen-jing Ma; Tong Lin; Ze-hui Xiao; Chu-min Zhao; Ting Du; Xin-jun Du; Shuo Wang (Food Chemistry, 2023)

An acidic heteropolysaccharide rich in galactose and arabinose derived from ginger: Structure and dynamics - Xiao-tong Lin; Bo-xian Xiao; Jun-ping Liu; Ming-yuan Cao; Zhi-ping Yang; Li-yan Zhao; Gui-tang Chen (Food Bioscience, 2023)

Performance and mechanism of the synergistic hexavalent chromium and nitrogen removal in a MABR system - Zhiye Sun; Yi Li; Jun Liu; Ting Li; Xiwei Cao; Baoan Li (Chemical Engineering Journal, 2023)

Blue-ringed Octopus inspired slippery coating with physico-chemical synergistic antifouling properties - Yuyang Zhou; Xinming Cao; Yang Chen; Yun Li; Jun Ma; Jinlong Song; Xin Liu (Chemical Engineering Journal, 2023)

Protocol for Brain Magnetic Resonance Imaging and Extraction of Imaging-Derived Phenotypes from the China Phenobank Project - Chengyan Wang; Zhang Shi; Yan Li; Xueqin Xia; Xutong Kuang; Shufang Qian; Le Xue; Lizhen Lan; Yudan Wu; Na Zhang; Ji Tao; Xumei Hu; et al. (Phenomics, 2023)

The expression of CD86 in CD3+CD56+ NKT cells is associated with the occurrence and prognosis of sepsis-associated encephalopathy in sepsis patients: a prospective observational cohort study - Sheng-long Chen; Xiao-yu Liu; Jun-hong Huang; Lu-hua Xian; Xu-sheng Li; Kang-rong Wang; Jing Li; Tian-cao Zhang; Guo-ge Huang; Xin-qiang Liu; Hong-ke Zeng; Mao-hua Zhou; et al. (Immunologic Research, 2023)

Evolution of tidal flats in the Yellow River Qingshuigou sub-delta: spatiotemporal analysis and mechanistic changes (1996-2021) - Yin Cao; Qing Wang; Chao Zhan; Rui Li; Zhangfan Qian; Longsheng Wang; Xianbin Liu; Jun Zhu; Hongyuan Shi; Yan Li (Frontiers in Marine Science, 2023)
The Yellow River Delta has undergone significant changes, developing a temperate chalk-sand silty coast with expansive and level tidal flats. However, the area is currently facing the threat of erosion due to coastal area construction, decreased river sediment discharge into the sea, and intensified marine hydrodynamic forces. Remote sensing technology has important applications in spatial and temporal monitoring of tidal flats. This study employs tidal data to establish the threshold range for the extraction of tidal flats in the Yellow River Qingshuigou sub-delta, using the water frequency method based on the image element proposed by previous authors. The study successfully identifies and analyzes the range of tidal flats, and further delves into their evolutionary process and underlying mechanisms. The study concludes that the area of tidal flats has shown a decreasing trend and was divided into a “rapid decline phase” and an “overall stabilization phase” with 2006 as the boundary. The spatial and temporal evolution of tidal flats is primarily influenced by three main factors: river sediment discharges, marine hydrodynamic forces, and anthropogenic reclamation activities. Specifically, the river sediment discharges and marine hydrodynamic forces impact the extent of tidal flats by modifying the boundary conditions, primarily at the sea boundary. Reclamation activities have a direct and rapid effect on the extent of tidal flats, primarily at the land boundary. In this study, we determined the contribution of three factors to the spatial and temporal evolution of tidal flats in different periods. During the two phases of the tidal flats’ spatial and temporal evolution in the Yellow River Qingshuigou sub-delta, the driving mechanisms were identified as “reclamation - marine hydrodynamic forces - river sediment discharges” and “marine hydrodynamic forces - river sediment discharges - reclamation”.

Wastewater inputs reduce the CO2 uptake by coastal oceans - Yunxiao Li; Liang Xue; Xufeng Yang; Qinsheng Wei; Ming Xin; Ming Xue; Chenhua Han; Ping Han; Xiangyu Liu; Han Zang; Pengjin Yang; Xiangbin Ran; et al. (Science of The Total Environment, 2023)

Development of a duplex PCR for the simultaneous detection of EHP and IHHNV and analysis of the correlation between these two pathogens - Yang Gao; Cai-Yi Chen; Zheng Cao; Ru-Qing Yuan; Lin-Rui Chang; Ting Li; Ling-Jun Si; Dong-Chun Yan; Fan Li (Journal of Invertebrate Pathology, 2023)

Synergy between fayalite-constituted waste copper smelting slag and hydroxylamine: An efficient combination for construction and application of a surface Fenton system in removal of mining organic pollutants - Ying Cao; Jun Yao; Tatjana Šolević Knudsen; Wancheng Pang; Bo Ma; Hao Li; Chenchen Zhao; Bang Liu; Miaomiao Li (Journal of Cleaner Production, 2023)

BayLUP: A Bayesian framework for conditional random field simulation of the liquefaction-induced settlement considering statistical uncertainty and model error - Cong Miao; Zi-Jun Cao; Te Xiao; Dian-Qing Li; Wenqi Du (Gondwana Research, 2023)

Cumulative and lagged effects of varying-sized particulate matter exposure associates with toddlers’ gut microbiota - Tianlai Qiu; Tianzi Zang; Qingbo Fang; Zhihu Xu; Yanan Cao; Xiaoxiao Fan; Jun Liu; Xueer Zeng; Yanting Li; Yiming Tu; Guoxing Li; Jinbing Bai; et al. (Environmental Pollution, 2023)

Tailoring pore structures in poly(propylene-co-1-butene) membranes: Unlocking versatility for advanced applications - Xian Zhang; Cheng-Ye Zhu; Wangbei Cao; Zhao-Yu Ma; Hao-Nan Li; Hong-Qing Liang; Chuan-Jie Fang; Xiao-Jun Huang; Zhi-Kang Xu (Chemical Engineering Journal, 2023)

Improved sequential production of hydrogen and caproate by addition of biochar prepared from cornstalk residues - Jian Du; Pian-Pian Xu; Hong-Yu Ren; Guang-Li Cao; Guo-Jun Xie; Nan-Qi Ren; Bing-Feng Liu (Bioresource Technology, 2023)

Personalized kitchen air supply for reducing individual thermal discomfort and cooking pollution intake - Yuhang Wu; Jiaying Zhou; Xiang Zhou; Jun Gao; Changsheng Cao; Yingqi Zeng; Jiajun Li (Building and Environment, 2023)

Locating the Scope and Depth of Coal Fires Based on Magnetic and Electrical Data - Zhenlu Shao; Guofu Zhang; Tao Zhou; Jun Wei; Fei Cao; Yong Zhang; Hongsheng Li; Huahai Sun; Shangkun Qing; Teng Chen; Long Chen; Hongwen Shao; et al. (Pure and Applied Geophysics, 2023)

Leopard predation on wild Sichuan snub-nosed monkeys - Bin Yang; James R. Anderson; Ni-Na Gou; Jun Luo; Bo Hong; Wei-Wei Fu; Yong-Feng Chen; Wei-Feng Wang; Bao-Jia Cao; Shi-Yu Chen; Kai-Feng Wang; Bao-Guo Li (Primates, 2023)

Genetic Architecture and Functional Implications of the CSF-Contacting Nucleus - Siyuan Song; Yumin Yuan; Lingling Xu; Jun Jiang; Ying Li; Yao Yan; Qing Li; Fang Zhou; Junli Cao; Licai Zhang (Neuroscience Bulletin, 2023)
We previously identified a unique nucleus, the cerebrospinal fluid (CSF)-contacting nucleus. This study aims to understand its gene architecture and preliminarily suggest its functions. The results showed that there were about 19,666 genes in this nucleus, of which 913 were distinct from the dorsal raphe nucleus (non-CSF contacting). The top 40 highly-expressed genes are mainly related to energy metabolism, protein synthesis, transport, secretion, and hydrolysis. The main neurotransmitter is 5-HT. The receptors of 5-HT and GABA are abundant. The channels for Cl – , Na + , K + , and Ca 2+ are routinely expressed. The signaling molecules associated with the CaMK, JAK, and MAPK pathways were identified accurately. In particular, the channels of transient receptor potential associated with nociceptors and the solute carrier superfamily members associated with cell membrane transport were significantly expressed. The relationship between the main genes of the nucleus and life activities is preliminarily verified.

Immobilization of cadmium in river sediments by different modified nanoscale zero-valent iron: performance, mechanisms, and Fe dissolution - Wenjing Xue; Hongdou Liu; Jun Li; Xinyu Chen; Siqi Wen; Jiaming Guo; Xiaoyu Shi; Shan Cao; Yang Gao; Rongzhong Wang; Yiqun Xu (Environmental Science and Pollution Research, 2023)

Functional-structural decoupling in visual network is associated with cognitive decline in patients with type 2 diabetes mellitus: evidence from a multimodal MRI analysis - Min-Hua Ni; Ying Yu; Yang Yang; Ze-Yang Li; Teng Ma; Hao Xie; Si-Ning Li; Pan Dai; Xin-Yu Cao; Yan-Yan Cui; Jun-Ling Zhu; Guang-Bin Cui; et al. (Brain Imaging and Behavior, 2023)

A Long-Term Operational Scheme for Hybrid Hydro-Photovoltaic (PV) Systems that Considers the Uncertainties in Reservoir Inflow and Solar Radiation Based on Scenario Trees - Han Cao; Jun Qiu; Hui-Min Zuo; Fang-Fang Li (Water Resources Management, 2023)

Spatial redistribution and enantiomeric signatures of hexachlorocyclohexanes in Chinese forest soils: Implications to environmental behavior and influencing factors - Qian Zheng; Yue Xu; Zhen Cao; Shizhen Zhao; Haijian Bing; Jun Li; Chunling Luo; Gan Zhang (Science of The Total Environment, 2023)

Microbial metabolic activity in metal(loid)s contaminated sites impacted by different non-ferrous metal activities - Hao Li; Jun Yao; Ning Min; Geoffrey Sunahara; Jianli Liu; Miaomaio Li; Bang Liu; Wancheng Pang; Ying Cao; Ruofei Li; Robert Duran (Journal of Hazardous Materials, 2023)

Halide-free squaramide–phenolate organocatalyst for the cycloaddition of CO2 into epoxides - Bo Liu; Hui Yu; Zhenjiang Li; Jun He; Yongzhu Hu; Xin Zou; Longlin Lu; Shaoju Cao; Canliang Ma; Kai Guo (Journal of Environmental Chemical Engineering, 2023)

Quantifying the effect of socio-economic-geo drivers on the change of municipal waste disposal in China by an integrated TWFE-PRF-SDM methodology - Peifan Yao; Bin Li; Sen Zhang; Lijie Song; Jun Tai; Jun Zhao; Wei Cao; Xing Zhang; Guangren Qian (Journal of Environmental Management, 2023)

In-situ characterization of the size distribution of lubricant droplets in rotary compressor - Puyuan Wu; Jun Chen; Paul E. Sojka; Yang Li; Hongjun Cao (International Journal of Refrigeration, 2023)

Multifunctional self-shaping ceramics controlled by laser induced graphene - Zhigang Wang; Min Li; Chunjie Yan; Jun Cao; Minghe Du; Heng Deng (Chemical Engineering Journal, 2023)

Biotransformation of nitrogen and tetracycline by counter-diffusion biofilm system: Multiple metabolic pathways, mechanism, and slower resistance genes enrichment - Ting Li; Xiwei Cao; Ziqing Wu; Jun Liu; Boyang Hu; Hao Chen; Baoan Li (Chemical Engineering Journal, 2023)

GABAergic Neurons in the Nucleus Accumbens are Involved in the General Anesthesia Effect of Propofol - Jing Yan; Bei-Ning Hang; Lin-Hui Ma; Jia-Tao Lin; Yue Zhou; Xin-Hao Jiao; Ying-Xuan Yuan; Ke-Jie Shao; Le-Meng Zhang; Qi Xue; Zi-Yi Li; Hong-Xing Zhang; et al. (Molecular Neurobiology, 2023)

Peptide YY inhibits transcription and replication of hepatitis B virus by suppressing promoter/enhancer activity - Xiaolun Xu; Weiping Zhou; Xing Tian; Zhongjia Jiang; Xuanhe Fu; Jun Cao; Ye Sun; Biao Yang; Xueqian Li; Yanting Li; Chunmeng Zhang; Guangyan Liu (Virus Genes, 2023)

Effects of magnetic field direction on O + vertical transport in the Martian ionosphere - Shi-bang Li; Hao-yu Lu; Jin-bin Cao; Jun Cui; Yun Li; Guo-kan Li; Ni-han Chen; Jian-xuan Wang (Advances in Space Research, 2023)

Gut microbiome helps honeybee ( Apis mellifera ) resist the stress of toxic nectar plant ( Bidens pilosa ) exposure: Evidence for survival and immunity - Qihe Tang; Wanli Li; Zhengwei Wang; Zhixiang Dong; Xijie Li; Jiali Li; Qi Huang; Zhe Cao; Wei Gong; Yazhou Zhao; Minzeng Wang; Jun Guo (Environmental Microbiology, 2023)
Honeybee ( Apis mellifera ) ingestion of toxic nectar plants can threaten their health and survival. However, little is known about how to help honeybees mitigate the effects of toxic nectar plant poisoning. We exposed honeybees to different concentrations of Bidens pilosa flower extracts and found that B. pilosa exposure significantly reduced honeybee survival in a dose‐dependent manner. By measuring changes in detoxification and antioxidant enzymes and the gut microbiome, we found that superoxide dismutase, glutathione‐S‐transferase and carboxylesterase activities were significantly activated with increasing concentrations of B. pilosa and that different concentrations of B. pilosa exposure changed the structure of the honeybee gut microbiome, causing a significant reduction in the abundance of Bartonella ( p Lactobacillus . Importantly, by using Germ‐Free bees, we found that colonization by the gut microbes Bartonella apis and Apilactobacillus kunkeei (original classification as Lactobacillus kunkeei ) significantly increased the resistance of honeybees to B. pilosa and significantly upregulated bee‐associated immune genes. These results suggest that honeybee detoxification systems possess a level of resistance to the toxic nectar plant B. pilosa and that the gut microbes B. apis and A. kunkeei may augment resistance to B. pilosa stress by improving host immunity.

Southern China can produce more high-quality rice with less N by green manuring - Songjuan Gao; Guopeng Zhou; Danna Chang; Hao Liang; Jun Nie; Yulin Liao; Yanhong Lu; Changxu Xu; Jia Liu; Ji Wu; Shang Han; Hui Wang; et al. (Resources, Conservation and Recycling, 2023)

From arc accretion to within-plate extension: Geochronology and geochemistry of the Neoproterozoic magmatism on the northern margin of the Yangtze Block - Yu Huang; Xiao-Lei Wang; Jun-Yong Li; Ru-Cao Li; De-Hong Du; Chang-Hong Jiang; Lin-Sen Li; Ning Ding (Precambrian Research, 2023)

Genetic diversity, antibiotic resistance, and virulence characteristics of Staphylococcus aureus from raw milk over 10 years in Shanghai - Jiewen Huang; Wengang Zhang; Bingqing Sun; Qin Jiang; Ying Cao; Jun Shang; Yu Zhang; Xin Gu; Chao Lv; Chaoyi Guo; Min Li; Hui Li; et al. (International Journal of Food Microbiology, 2023)

Molecular characterization and expression of twenty interleukin-17 transcripts in the common Chinese cuttlefish (Sepiella japonica) in response to Vibrio harveyi infection - Xu Zhou; Pei-Xuan Fang; Hui-Min Cao; Jian-Jun Xie; Shuang Li; Chang-Feng Chi (Fish & Shellfish Immunology, 2023)

Auxiliary Bayesian updating of embankment settlement based on finite element model and response surface method - Huaming Tian; Dian-Qing Li; Zi-Jun Cao; Wenqi Du (Engineering Geology, 2023)

Metal-organic framework-derived brain platygyra coral-like porous carbon architectures for real-time monitoring of hydrogen peroxide in biological matrices - Jun Li; Can Shen; Jiao Luo; Ti Pan; Jianlan Deng; Zhong Cao (Chemical Engineering Journal, 2023)

S-scheme Co3(PO4)2/Twinned-Cd0.5Zn0.5S homo-heterojunction for enhanced photocatalytic H2 evolution - Jingzhuo Tian; Xiaofei Cao; Tao Sun; Jun Fan; Hui Miao; Zhong Chen; Dong Li; Enzhou Liu; Yonghong Zhu (Chemical Engineering Journal, 2023)

Overexpression of Taetr1-1 promotes enhanced seed dormancy and ethylene insensitivity in wheat - Jun Wei; Xing-ting Wu; Xiao-ying Li; Wim J. J. Soppe; Hong Cao; Yong-xiu Liu (Planta, 2023)

Isoptericola croceus sp. nov., a novel actinobacterium isolated from saline–alkali soil - Yu-Ting OuYang; Ai-Ping Lv; Lan Liu; Ting-Ting Li; Yi Zhou; Ting-Ting She; Li-Xiang Cao; Jian-Yu Jiao; Shuang Wang; Wen-Jun Li (Antonie van Leeuwenhoek, 2023)

Profiling Genetic Breeding Progress in Bagrid Catfishes - Lishi Huang; Guosong Zhang; Yupeng Zhang; Xinlan Li; Zhong Luo; Wenyu Liu; Fu Luo; Haifeng Liu; Shaowu Yin; Jun Jiang; Xia Liang; Quanquan Cao (Fishes, 2023)
The Bagridae fish family holds significant economic value and enjoys a high demand in the commercial market due to its desirable characteristics, such as delicious meat, fewer muscle spines, and a pleasing flavor. In recent years, the Bagridae has experienced rapid development in the seed industry in response to industry demands. Researchers have conducted extensive studies on genetic breeding in the Bagridae, employing a comprehensive breeding approach that combines conventional breeding techniques with innovative new technologies and cooperative efforts. In this review, we present an overview of the market situation and discuss various breeding processes applied to the Bagridae, including selective breeding, genetic engineering breeding, cell engineering breeding, molecular marker-assisted breeding, and hybrid breeding. Additionally, we focus on introducing the cultivation methods for two new Bagridae varieties. Furthermore, we explore and summarize the breeding conditions, genetic background, heterosis, comprehensive breeding technology, stress resistance, and metabolic nutrition of hybrid Bagridae catfishes. Overall, noticeable heterosis has been observed in the breeding of the hybrid yellow catfish “Huangyou-1”, which exhibits promising market prospects and economic benefits for aquaculture. Our study aims to underscore the importance of harnessing the heterosis of catfish, particularly the Pelteobagrus and Bagridae species. Consequently, this review provides an update on the current available information regarding the seed industry of the Bagridae fish family.

Pyrroloquinoline quinone promotes growth and intestinal health and alleviates tris(1,3-dichloro-2-propyl) phosphate-induced hepatic oxidative stress in zebrafish - Chao-Qun Li; Yong-Jun Cao; Long-Fei Cui; Chun-Yang Zhang; Bei-Li Zhang; Qin-Yuan Ma (Aquaculture, 2023)

Nanographite-assisted matrix solid phase dispersion microextraction of active and toxic compounds from complex food matrices using cyclodextrin aqueous solution as elution solvent - Si-Chen Zhu; Ying Shi; Huang-Fei Jin; Jun Cao; Li-Hong Ye (Food Chemistry, 2023)

Molecular mechanisms of hepatoprotective effect of tectorigenin against ANIT-induced cholestatic liver injury: Role of FXR and Nrf2 pathways - Peng Cao; Jun Gan; Sanlan Wu; Yixin Hu; Bin Xia; Xiaoyue Li; Hongan Zeng; Bingyu Cheng; Huifan Yu; Fei Li; Luqin Si; Jiangeng Huang (Food and Chemical Toxicology, 2023)

Liver fibrosis in fish research: From an immunological perspective - Quanquan Cao; Hongying Shan; Ju Zhao; Jinhe Deng; Man Xu; Hao Kang; Tong Li; Ye Zhao; Haifeng Liu; Jun Jiang (Fish & Shellfish Immunology, 2023)

Pyroptosis in fish research: A promising target for disease management - Quanquan Cao; Jiali Zong; Zhihao Zhang; Wenyu Liu; Tong Li; Ye Zhao; Haifeng Liu; Jun Jiang (Fish & Shellfish Immunology, 2023)

Does PM1 exposure during pregnancy impact the gut microbiota of mothers and neonates? - Yanan Cao; Tianzi Zang; Tianlai Qiu; Zhihu Xu; Xiangxu Chen; Xiaoxiao Fan; Qianping Zhang; Yingjuan Huang; Jun Liu; Ni Wu; Natalie Shen; Jinbing Bai; et al. (Environmental Research, 2023)

The Ni2+-LaNiO3/CdS hollow core–shell heterojunction towards enhanced visible light overall water splitting H2 evolution via HER/OER synergism of Ni2+/Ov - Lixin Que; Lei Lu; Yunlong Xu; Xiaoqing Xu; Mei Zhu; Jiaqi Pan; Jun Cao; Jingjing Wang; Yingying Zheng; Chaorong Li (Chemical Engineering Journal, 2023)

Oxytetracycline-induced oxidative liver damage by disturbed mitochondrial dynamics and impaired enzyme antioxidants in largemouth bass (Micropterus salmoides) - Tong Li; Min Jin; Lishi Huang; Yupeng Zhang; Jiali Zong; Hongying Shan; Hao Kang; Man Xu; Haifeng Liu; Ye Zhao; Quanquan Cao; Jun Jiang (Aquatic Toxicology, 2023)

Population analysis reveals the roles of DNA methylation in tomato domestication and metabolic diversity - Hao Guo; Peng Cao; Chao Wang; Jun Lai; Yuan Deng; Chun Li; Yingchen Hao; Zeyong Wu; Ridong Chen; Qi Qiang; Alisdair R. Fernie; Jun Yang; et al. (Science China Life Sciences, 2023)

Neuroprotective Effects of Oxymatrine via Triggering Autophagy and Inhibiting Apoptosis Following Spinal Cord Injury in Rats - Jian Li; Yang Cao; Lin-Na Li; Xin Chu; Yan-Song Wang; Jia-Jun Cai; Jin Zhao; Song Ma; Gang Li; Zhong-Kai Fan (Molecular Neurobiology, 2023)

Effect of lead, calcium, iron, zinc, copper and magnesium on anemia in children with BLLs ≥ 100 μg/L - Xiaoyu Yu; Liang Xiong; Sha Zhao; Zhengqiu Li; Shiting Xiang; Yuhan Cao; Changci Zhou; Jie Dong; Jun Qiu (Journal of Trace Elements in Medicine and Biology, 2023)

Experimental study of the lubricant-refrigerant flow in a rotary compressor - Puyuan Wu; Jun Chen; Paul E. Sojka; Yang Li; Hongjun Cao (International Journal of Refrigeration, 2023)

Comparison and enrichment of sn-2 palmitoyl triacylglycerols (OPO/OPL) in fish oil for its potential application as human milk fat substitutes - Dongyin Liu; Jingtao Cui; Ruibing Zhou; Chen He; Jun Cao; Chuan Li (Food Research International, 2023)

Identification of the design point based on Monte Carlo simulation - Guo-Hui Gao; Dian-Qing Li; Zi-Jun Cao (Computers and Geotechnics, 2023)

Near unity broadband emissivity and ultralow thermal conductivity from yttrium niobate-based ceramics - Guoliang Chen; Benzhi Min; Haoyang Fu; Siqi Ma; Ke Li; Shuqi Wang; Yaming Wang; Jianyun Cao; Jun Qiu; Yong Shuai; Shuzhou Li; Yongchun Zou; et al. (Chemical Engineering Journal, 2023)

Environmental heterogeneity affecting spatial distribution of phytoplankton community structure and functional groups in a large eutrophic lake, Lake Chaohu, China - Huijuan Cao; Kun Zhang; Daogui Deng; Huiying Qi; Jun Li; Yaqin Cao; Qide Jin; Yajie Zhao; Yeping Wang; Zhou Wu; Xinyue Li; Ying Li (Environmental Science and Pollution Research, 2023)
The growth and development of phytoplankton are influenced by physico-chemical parameters, which can also affect the spatial distribution of phytoplankton community structure. However, it is unclear whether environmental heterogeneity caused by multiple physico-chemical factors can affect the spatial distribution of phytoplankton and its functional groups. In this study, we investigated the seasonal variation and spatial distribution of phytoplankton community structure and its relationships with environmental factors in Lake Chaohu from August 2020 to July 2021. We recorded a total of 190 species from 8 phyla, which were divided into 30 functional groups, including 13 dominating functional groups. The average annual phytoplankton density and biomass were (5.46 ± 7.17) × 10 7 cells/L and 4.80 ± 4.61 mg/L, respectively. The density and biomass of phytoplankton were higher in summer ((14.64 ± 20.34) × 10 7 cells/L, 10.61 ± 13.16 mg/L) and autumn ((6.79 ± 3.97) × 10 7 cells/L, 5.57 ± 2.40 mg/L), with the M and H2 of dominant functional groups. The dominant functional groups were N, C, D, J, MP, H2, and M in spring, whereas functional groups C, N, T, and Y dominated in winter. The distribution of phytoplankton community structure and dominant functional groups exhibited significant spatial heterogeneity in the lake, which was consistent with the environmental heterogeneity of the lake and could be classified into four locations. Location I had higher phytoplankton density and biomass than the other three locations. Additionally, dominant functional groups M, C, and H2 were present throughout the lake, and all 13 dominant functional groups were observed in Location II. Our findings suggest that environmental heterogeneity is a key factor influencing the spatial distribution of phytoplankton functional groups in Lake Chaohu.

One global disseminated 193 kb high-risk hybrid plasmid harboring tet(X4), mcr or blaNDM threatening public health - Min Li; Haoran Zhang; Wengang Zhang; Ying Cao; Bingqing Sun; Qin Jiang; Yu Zhang; Haodong Liu; WenNan Guo; Cheng Chang; Nan Zhou; Chao Lv; et al. (Science of The Total Environment, 2023)

Assembly processes of bacterial and fungal communities in metal(loid)s smelter soil - Miaomiao Li; Jun Yao; Geoffrey Sunahara; Robert Duran; Bang Liu; Ying Cao; Hao Li; Wancheng Pang; Houquan Liu; Shun Jiang; Junjie Zhu; Qinghua Zhang (Journal of Hazardous Materials, 2023)

Effects of Bacillus subtilis BS-Z15 on Intestinal Microbiota Structure and Body Weight Gain in Mice - Jun Yang; Huan-Chen Ning; Qi Zhang; Jun-Qi Yue; Xi-Yuan Cao; Jin-Yu Li; Ling Liu; He-Ping Zhao; Hui-Xin Zhao (Probiotics and Antimicrobial Proteins, 2023)

Temporal decline of genetic differentiation among populations of western flower thrips across an invaded range - Li-Na Sun; Li-Jun Cao; Jin-Cui Chen; Li-Jun Ma; Gui-Fen Zhang; San-An Wu; Ary Anthony Hoffmann; Shu-Jun Wei (Biological Invasions, 2023)

Association of urine phthalate metabolites levels with kidney function in 1610 US adolescents - Shi-ting Xiang; Yuhan Cao; Jie Dong; Chao Li; Yanying Duan; Xun Li; Jun Qiu (Environmental Science and Pollution Research, 2023)

5-epi-ent-Kaurane diterpenoids from the aerial parts of Isodon eriocalyx and their anti-atherosclerotic potential - Long Mu; Tian Li; Peng-Lin Wu; Ling-Qiao Cai; Shu-Ying Li; Zi-Yuan Wang; Yuan-Yuan Liu; Jie Wang; Dong Yan; Zheng-Yun Rao; Chao-Jun Wang; Jian Zhang; et al. (Phytochemistry, 2023)

Effects of different fermentation synergistic chemical treatments on the performance of wheat straw as a nursery substrate - Jun Li; Chao Xu; Xin Zhang; Zhiyun Gu; Hongliang Cao; Qiaoxia Yuan (Journal of Environmental Management, 2023)

Quick and high-throughput quantification of 22 β-agonists residues in animal-derived foods using enzymatic probe sonication - Zhiming Xiao; Jun Wang; Ying Cao; Ting Yao; Shi Wang; Jia Liu; Decheng Suo; Jing Tian; Zheng Jia; Yang Li; Xia Fan (Food Chemistry, 2023)

Polysaccharides from Artocarpus heterophyllus Lam. (jackfruit) pulp alleviate obesity by modulating gut microbiota in high fat diet-induced rats - Shunjiang Zeng; Jun Cao; Chenxi Wei; Yuzi Chen; Qibing Liu; Chuan Li; Yanjun Zhang; Kexue Zhu; Gang Wu; Lehe Tan (Food Hydrocolloids, 2023)

FTO-Nrf2 axis regulates bisphenol F-induced leydig cell toxicity in an m6A-YTHDF2-dependent manner - Shi-meng Zhou; Jing-zhi Li; Hong-qiang Chen; Yong Zeng; Wen-bo Yuan; Yu Shi; Na Wang; Jun Fan; Zhe Zhang; Yuanyuan Xu; Jia Cao; Wen-bin Liu (Environmental Pollution, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Insights on nitrogen and phosphorus removal mechanism in a single-stage Membrane Aeration Biofilm Reactor (MABR) dominated by denitrifying phosphorus removal coupled with anaerobic/aerobic denitrification - Ming Li; Xiwei Cao; Ziqing Wu; Jiaye Li; Ying Cui; Jun Liu; Baoan Li (Journal of Water Process Engineering, 2023)

The potential environmental risk implications of two typical non-ferrous metal smelting slags: contrasting toxic metal(loid)s leaching behavior and geochemical characteristics - Dongyang Men; Jun Yao; Hao Li; Gyozo Jordan; Baojin Zhao; Ying Cao; Bo Ma; Bang Liu; Yuanyuan Sun; Jiaxing Ban (Journal of Soils and Sediments, 2023)

Dynamic performance and damage assessment of a shallow buried tunnel under internal explosion - Zichao Liu; Jun Wu; Chen Cao; Shutao Li; Qiushi Yan (Tunnelling and Underground Space Technology, 2023)

Vertical measurements of stable nitrogen and oxygen isotope composition of fine particulate nitrate aerosol in Guangzhou city: Source apportionment and oxidation pathway - Yujing Wang; Junwen Liu; Fan Jiang; Zixi Chen; Lili Wu; Shengzhen Zhou; Chenglei Pei; Ye Kuang; Fang Cao; Yanlin Zhang; Meiyi Fan; Junyu Zheng; et al. (Science of The Total Environment, 2023)

First evidence of neonicotinoid insecticides in human bile and associated hepatotoxicity risk - Yuanchen Chen; Wenfei Yu; Li Zhang; Linping Cao; Jun Ling; Kaizhen Liao; Guofeng Shen; Wei Du; Kangjie Chen; Meirong Zhao; Jian Wu; Hangbiao Jin (Journal of Hazardous Materials, 2023)

Performance and mechanisms for Cd(II) and As(III) simultaneous adsorption by goethite-loaded montmorillonite in aqueous solution and soil - Chenchen Zhao; Jun Yao; Tatjana Šolević Knudsen; Jianli Liu; Xiaozhe Zhu; Bo Ma; Hao Li; Ying Cao; Bang Liu (Journal of Environmental Management, 2023)

Inhibition of ATF4-mediated elevation of both autophagy and AKT/mTOR was involved in antitumorigenic activity of curcumin - Jie Yang; Hasenbilige; Shibo Bao; Shengxiang Luo; Liping Jiang; Qiujuan Li; Ying Kong; Jun Cao (Food and Chemical Toxicology, 2023)

RNA binding protein YTHDF1 mediates bisphenol S-induced Leydig cell damage by regulating the mitochondrial pathway of BCL2 and the expression of CDK2-CyclinE1 - Jing-zhi Li; Shi-meng Zhou; Wen-bo Yuan; Hong-qiang Chen; Yong Zeng; Jun Fan; Zhe Zhang; Na Wang; Jia Cao; Wen-bin Liu (Environmental Pollution, 2023)

Intrinsic facet-dependent electrochemical activities of BiOBr nanosheets for Br- exchange in electrochemically switched ion exchange process - Jie Wang; Liang Zhang; Yasi Hu; Xiao Du; Xiaogang Hao; Qing Cao; Guoqing Guan; Zhong Liu; Jun Li; Shanxia Luo; Xiaowei An (Chemical Engineering Journal, 2023)

Hydraulic determinants of drought-induced tree mortality and changes in tree abundance between two tropical forests with different water availability - Yong-Qiang Wang; Hui-Qing Song; Ya-Jun Chen; Pei-Li Fu; Jiao-Lin Zhang; Kun-Fang Cao; Shi-Dan Zhu (Agricultural and Forest Meteorology, 2023)

Ions play different roles in virus removal caused by different NOMs in UF process: Removal efficiency and mechanism analysis - Zixiao Ren; Haiyan Cao; Peter Desmond; Bingsheng Liu; Huu Hao Ngo; Xu He; Guibai Li; Jun Ma; An Ding (Chemosphere, 2023)

Assessment of graphene-based polymers for sustainable wastewater treatment: Development of a soft computing approach - Jun Cao; Jialing Li; Hasan Sh Majdi; Binh Nguyen Le; Mohamed Amine Khadimallah; H. Elhosiny Ali; Hamid Assilzadeh (Chemosphere, 2023)

Campylobacter jejuni infection induces dynamic expression of avian host defense peptides in vitro and in vivo - Pengxiang Li; Yifang Cui; Fangfang Guo; Jiahui Guo; Xiaoya Cao; Jun Lin; Baoan Ding; Fuzhou Xu (Veterinary Microbiology, 2023)

Autophagy induces mTOR-dependent glucose uptake and mTOR-independent lactate utilization in cadmium-treated A549 cells - Shibo Bao; Cong Zhang; Shengxiang Luo; Liping Jiang; Qiujuan Li; Ying Kong; Jun Cao (Toxicology in Vitro, 2023)

A 40 % paddy surface soil organic carbon increase after 5-year no-tillage is linked with shifts in soil bacterial composition and functions - Jian-Ying Qi; Xiang-Bin Yao; Jian Lu; Long-Xin He; Jun-Li Cao; Zheng-Rong Kan; Xing Wang; Sheng-Gang Pan; Xiang-Ru Tang (Science of The Total Environment, 2023)

Surprising leopard restoration in fragmented ecosystems reveals connections as the secret to conservation success - Fu Yanwen; Zhao Guojing; Dai Wenqian; Wang Yue; Li Jiawei; Tan Mengyu; Li Yan; Liu Haoran; Xie Bing; Jin Xiao; Fan Enyu; Zhao Lulu; et al. (Science of The Total Environment, 2023)

2000 years of lake-level fluctuations and human adaptation around China's largest freshwater lake - Huanye Wang; Weiguo Liu; Qin Leng; Lin Yang; Hui Zhao; Jun Yang; Yuwei Chen; Shangbin Xiao; Yunning Cao; Jing Hu; Xiaoke Qiang; Peng Cheng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Development of novel hydrogen sulfide depletion aided platform for photodynamic therapy with enhanced anticancer performance - Fang Jia; Xiang Li; Kai Wang; Xin Dong; Tao Liao; Cao Li; Gang Chen; Jun Jiang (Journal of Photochemistry and Photobiology B: Biology, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

Cathode potential regulates the microbiome assembly and function in electrostimulated bio- dechlorination system - Di Cao; Zhi-Ling Li; Ke Shi; Bin Liang; Zhongli Zhu; Wenzong Liu; Jun Nan; Kai Sun; Ai-Jie Wang (Journal of Hazardous Materials, 2023)

Polypropylene microplastics affect the distribution and bioavailability of cadmium by changing soil components during soil aging - Yanxiao Cao; Xianying Ma; Nuo Chen; Tiantian Chen; Mengjie Zhao; Honghu Li; Yongwei Song; Jingcheng Zhou; Jun Yang (Journal of Hazardous Materials, 2023)

Numerical study of the influence of loading rate on fracture mechanism in elastoplastic rock-like materials with a modified phase-field model - Shi-Fan Liu; Wei Wang; Ya-Jun Cao; Hai-Feng Li; Jian-Fu Shao (International Journal of Rock Mechanics and Mining Sciences, 2023)

Comprehensive investigation of the content and the origin of matrine-type alkaloids in Chinese honeys - Zhiying Wang; Tiehong Zu; Xuezhe Huang; Xiaolin Jiang; Guangqun Jia; Jinzhong Xu; Zongyan Cui; Fengmei Zhu; Jinjie Zhang; Jun Li; Yanzhong Cao (Food Chemistry, 2023)

Effect and mechanism of functional compound fruit drink on gut microbiota in constipation mice - Yali Shi; Fei Chen; Ziqi Wang; Jun Cao; Chuan Li (Food Chemistry, 2023)

Extraction and characterization of pectic polysaccharides from Choerospondias axillaris peels: Comparison of hot water and ultrasound-assisted extraction methods - Chao Wang; Jing Li; Yi Cao; Jialu Huang; Hongyi Lin; Tiantian Zhao; Lu Liu; Peiyi Shen; David Julian McClements; Jun Chen; Chengmei Liu; Jiyan Liu; et al. (Food Chemistry, 2023)

Characteristics of groundwater microbial communities’ structure under the impact of elevated nitrate concentrations in north China plain - Bo Zhang; Zhi-Ling Li; Cai-Hua Bai; Jing-Lan Liu; Jun Nan; Di Cao; Li-Wei Li (Environmental Research, 2023)

IFI44L as a novel epigenetic silencing tumor suppressor promotes apoptosis through JAK/STAT1 pathway during lung carcinogenesis - Yong Zeng; Hong-qiang Chen; Zhe Zhang; Jun Fan; Jing-zhi Li; Shi-meng Zhou; Na Wang; Su-peng Yan; Jia Cao; Jin-yi Liu; Zi-yuan Zhou; Wen-bin Liu (Environmental Pollution, 2023)

Repaired surface structural imperfection of tin Wide-Bandgap perovskite films for photovoltaic application - Tian-Yu Teng; Fan Hu; Yan-Hui Lou; Jun-Jie Cao; Chun-Hao Chen; Yi-Ran Shi; Kai-Li Wang; Jing Chen; Zhao-Kui Wang; Liang-Sheng Liao (Chemical Engineering Journal, 2023)

Efficient photocatalytic H2 generation over In2.77S4/NiS2/g-C3N4 S-scheme heterojunction using NiS2 as electron-bridge - Zhuonan Lei; Xiaofei Cao; Jun Fan; Xiaoyun Hu; Jun Hu; Neng Li; Tao Sun; Enzhou Liu (Chemical Engineering Journal, 2023)

Assessment of permafrost disturbances caused by two parallel buried warm-oil pipelines: A case study at a high-latitude wetland site in Northeast China - Fei Wang; Guoyu Li; Wei Ma; Dun Chen; Gang Wu; Yapeng Cao; Yanhu Mu; Yuncheng Mao; Jun Zhang; Kai Gao; Xinbin Wang; Hongyuan Jing; et al. (Cold Regions Science and Technology, 2023)

Multiple essential amino acids regulate mammary metabolism and milk protein synthesis in lactating dairy cows - Jun Zhang; Lu Deng; Xia Zhang; Yangchun Cao; Mengmeng Li; Junhu Yao (Animal Feed Science and Technology, 2023)

Genetic characteristics and growth patterns of the hybrid grouper derived from the hybridization of Epinephelus fuscoguttatus (female) × Epinephelus polyphekadion (male) - Liu Cao; Pan Chen; Xingrong Hou; Jun Ma; Ning Yang; Yanping Xu; Yanjin Zhang; Anqi Zhao; Jiyuan Zhang; Xinyu Li; Hai Huang (Journal of Fish Biology, 2023)
Hybridization is one of the primary methods used to cultivate farmed grouper species. The hybrid grouper derived from crossing Epinephelus fuscoguttatus (♀) and E. polyphekadion (♂) exhibits growth superiority over its parents. The genetic characteristics and growth patterns of the hybrid grouper have not yet been defined. This study confirms the ploidy level of the hybrid grouper (2 n = 48) using chromosome count analysis and flow cytometry. The 5S rDNA family was used to evaluate genetic diversity. Only one 5S class (~400 bp) was detected in the hybrid grouper, which could be used to distinguish between two different types based on nucleotide sequences, likely representing homologous unit classes from the female and male parental species. Growth patterns of 5–8‐month‐old hybrid groupers were also monitored. In this phase, a positive allometric growth pattern in body mass with total length was found. Body height and body mass were significantly correlated based on correlation and path coefficient, suggesting that body height could serve as an excellent index to increase body mass. These results aid our understanding of the genetic evolution of the hybrid grouper and inform the development of improved rearing techniques.

Labile and refractory fractions of sedimentary organic carbon off the Changjiang Estuary and its implications for sedimentary oxygen consumption - Yu Cao; Hong Huang; Xu Zhao; Jun Li; Teng Wang; Jun Lin; Zhuo-Yi Zhu (Frontiers in Marine Science, 2023)
Estuarine and coastal area is dynamic zone for both marine carbon and oxygen cycles. There is limited evaluation of the labile and refractory fraction of sedimentary organic carbon and further a lack of attention to the corresponding potential in dissolved oxygen utilization. In this study, we collected sediment samples from the Changjiang estuary and adjacent coastal areas in the East China Sea in June 2019 to reveal the distribution, main controlling factor, and implications of four operational fractions of sediment organic carbon that range from labile to refraction. In the laboratory, we processed and defined the four operational fractions of sedimentary organic carbon, includes 1) pure water extractable carbon (WEC), 2) salt (K2SO4 solution) extractable carbon (SEC), 3) Microbial biomass carbon (MBC; chloroform extractable carbon), and 4) refractory organic carbon (ROC; the acid-processed fraction). We revealed that off the Changjiang Estuary, the bulk sedimentary organic carbon (SOC), WEC, SEC, MBC, and ROC were 9.43 ± 3.07 g/kg, 0.12 ± 0.10 g/kg, 0.16 ± 0.07 g/kg, 1.58 ± 0.45 g/kg, and 4.38 ± 1.95 g/kg, respectively. Sediment grain size played a vital role in constraining the LOC fractions, and samples from aquaculture areas showed extra-higher levels of LOC when compared to samples from the non-aquaculture area. The LOC and MBC fraction showed clear negative relation with dissolved oxygen (DO) in the near bottom waters under high DO background (DO > 5.5 mg/L), whereas in a low DO background (DO < 3-4 mg/L) no clear relation can be found. Based on our observed LOC content and DO concentration in the near bottom waters, the depth of hypoxia in the near bottom waters, which would be caused by a total decomposition of 4 mm of LOC in the top sediment, ranged between 0.3 m to 4.7 m with an average depth of 2 m. This value (2 m) means that sedimentary oxygen consumption would contribute 10% in the occurrence of hypoxia, with the rest contributing from water column respiration. Overall, we used the LOC fraction of sedimentary organic carbon to address the dissolved oxygen consumption in the near bottom waters and further study is needed to evaluate this approach.

Radical chemistry, degradation mechanism and toxicity evolution of BPA in the UV/chlorine and UV/H2O2 - Ying Cao; Jun Yao; Tatjana Šolević Knudsen; Wancheng Pang; Junjie Zhu; Bang Liu; Hao Li; Miaomiao Li; Jianchao Su (Chemosphere, 2023)

TET1 involved in bisphenol A induced TM3 Leydig cell toxicity by regulating Cav3.3 hydroxymethylation - Shi-meng Zhou; Wen-bo Yuan; Jing-zhi Li; Hong-qiang Chen; Yong Zeng; Na Wang; Jun Fan; Zhe Zhang; Yuanyuan Xu; Jia Cao; Wen-bin Liu (Chemosphere, 2023)

Insights into the influence on 2,4,6-trichlorophenol microbial reductive dechlorination process by exposure to microplastics - Jia-Qi Yang; Zhi-Ling Li; Bin Wu; Ya-Ru Jin; Di Cao; Jun Nan; Xue-Qi Chen; Wen-Zong Liu; Shu-Hong Gao; Ai-Jie Wang (Journal of Hazardous Materials, 2023)

Improving probiotic (Lactobacillus casei) viability by encapsulation in alginate-based microgels: Impact of polymeric and colloidal fillers - Qian Li; Hongyi Lin; Jing Li; Lu Liu; Jialu Huang; Yi Cao; Tiantian Zhao; David Julian McClements; Jun Chen; Chengmei Liu; Jiyan Liu; Peiyi Shen; et al. (Food Hydrocolloids, 2023)

Metagenomic insights into the changes in the rhizosphere microbial community caused by the root-knot nematode Meloidogyne incognita in tobacco - Peng Lu; Heli Shi; Jiemeng Tao; Jingjing Jin; Sujie Wang; Qingxia Zheng; Pingping Liu; Bikun Xiang; Qiansi Chen; Yalong Xu; Zefeng Li; Jun Tan; et al. (Environmental Research, 2023)

Breast adipose metabolites mediates the association of tetrabromobisphenol a with breast cancer: A case-control study in Chinese population - Ai Zhang; Rui Wang; Qianfeng Liu; Zhengjun Yang; Xiaohui Lin; Jing Pang; Xiaoyu Li; Dan Wang; Jiayu He; Jianping Li; Mingyue Zhang; Yue Yu; et al. (Environmental Pollution, 2023)

Directional bioelectrochemical dechlorination of trichloroethene to valuable ethylene by introduction poly-3-hydroxybutyrate as a slow release carbon source - Xueqi Chen; Caihua Bai; Zhiling Li; Di Cao; Yunxia Zu; Zimeng Zhang; Guanshu Zhao; Jun Nan; Hongcheng Wang; Bin Liang; Aijie Wang (Chemical Engineering Journal, 2023)

Degradation of three typical hydroxamic acids collectors via UVA-B activated H2O2 and persulfate: Kinetics, transformation pathway, DFT calculation and toxicity evaluation - Wancheng Pang; Jun Yao; Tatjana Šolević Knudsen; Ying Cao; Bang Liu; Hao Li; Miaomiao Li; Junjie Zhu (Chemical Engineering Journal, 2023)

Chitosan based photothermal scaffold fighting against bone tumor-related complications: Recurrence, infection, and defects - Yao Zhao; Xu Peng; Xiaoyang Xu; Mingzhen Wu; Fan Sun; Qiangwei Xin; Hongbo Zhang; Liangrui Zuo; Yilin Cao; Yuhang Xia; Jun Luo; Chunmei Ding; et al. (Carbohydrate Polymers, 2023)

ER stress-enhanced HMGA2 plays an important role in Cr (VI)-induced glycolysis and inhibited oxidative phosphorylation by targeting the transcription of ATF4 - Shengxiang Luo; Cong Zhang; Zeyun Gao; Liping Jiang; Qiujuan Li; Xiaoxia Shi; Ying Kong; Jun Cao (Chemico-Biological Interactions, 2023)

miR-27a-3p targets NR5A2 to regulate CYP19A1 expression and 17-β estradiol synthesis in ovine granulosa cells - Hongbing Gui; Fan Li; Cheng Chen; Qiuyi Zhu; Chenjian Zhang; Jun Zhang; Chunhua Meng; Yong Qian; Shaoxian Cao; Yinxia Li (Animal Reproduction Science, 2023)

Effects of Dietary Eucommia ulmoides Leaf Extract on Growth, Muscle Composition, Hepatopancreas Histology, Immune Responses and Microcystin-LR Resistance of Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Yao-Peng Lu; Pei-Hua Zheng; Jia-Rui Xu; Yan-Lei Cao; Jun-Tao Li; Chen-Guang Hao; Ze-Long Zhang; Jian-An Xian; Xiu-Xia Zhang; An-Li Wang (Fishes, 2022)
The objective of the present study was to investigate the effects of different doses of dietary Eucommia ulmoides leaf extract (ELE) on juvenile red claw crayfish (Cherax quadricarinatus). A total number of 720 red claw crayfish (initial body weight of 0.24 ± 0.01 g) were randomly assigned to six groups and fed diets containing 0 (Diet 1), 0.5 (Diet 2), 1 (Diet 3), 2 (Diet 4), 4 (Diet 5) and 10 (Diet 6) g dry weight (dw) ELE kg (dw)−1 diets for eight weeks and challenged with microcystin-LR stress. The results indicated that dietary supplementation with 1–2 g dw ELE kg (dw)−1 diet could significantly improve the weight gain rate (WGR) and specific growth rate (SGR) of crayfish. Muscle crude protein contents of crayfish fed Diet 2, Diet 3, and Diet 4 were significantly higher than those of the control group. Compared with the control group, dietary ELE could increase total antioxidant capacity (T-AOC), superoxide dismutase (SOD), glutathione peroxidase (GPx), acid phosphatase (ACP), alkaline phosphatase (AKP), and phenoloxidase (PO) activities and decrease malondialdehyde (MDA) level of crayfish. Dietary ELE significantly increased the relative expression levels of SOD, thioredoxin 1 (TRX1), GPx, selenium-dependent glutathione peroxidase (Se-GPx), cytochrome P450 (CYP450), anti-lipopolysaccharide factor (ALF) and C-type lysozyme (C-LZM) mRNA of crayfish compared with the control group during the feeding experiment. When subjected to MC-LR stress for 48 h, the mRNA expression levels of SOD, GPx, Se-GPx, glutathione-s-transferase 1 (GST1), ALF, hemocyanin (HEM), and C-LZM in the hepatopancreas could be improved to varying degrees compared with the Diet 1. Supplementation of 1–2 g dw ELE kg (dw)−1 diet could improve the survival rate (SR) of crayfish under MC-LR stress. These results indicated that dietary ELE (1–2 g dw ELE kg (dw)−1 diet) could improve the growth performance, muscle protein, and non-specific immune response and increase the SR of crayfish under MC-LR stress by regulating the mRNA expression levels of the immune- and antioxidant-related genes.

Molecular Characterization and Dietary Regulation of Glutaminase 1 (gls1) in Triploid Crucian Carp (Carassius auratus) - Yangbo Xiao; Rong Huang; Shenping Cao; Dafang Zhao; Zhuangwen Mao; Chuchu Xiao; Zhehua Xu; Xiaomei Zhou; Xinran Zhang; Yu Zhang; Jianzhou Tang; Junyan Jin; et al. (Fishes, 2022)
Kidney-type glutaminase, encoded by the gls1 gene, plays a critical role in glutamate production and improvement of meat flavor. In this study, a gls1 gene encoding 595 amino acids was cloned from triploid crucian carp (Carassius auratus) (TCC) and showed a high similarity with the gls1 gene found in Cyprinus carpio, Sinocyclocheilus rhinocerous and Puntigrus tetrazona. Comparing the abundance of gls1 in different tissues, we found its expression level in the brain and liver were significantly higher than that in heart, gut, kidney, spleen and muscle. gls1 expression in the brain reached the highest value. In addition, the expression levels of gls1 also appeared different in diurnal variation, with the highest expression seen at 9:00, while it was low at 3:00, 6:00, 15:00 and 24:00. Furthermore, dietary regulation of gls1 expression was investigated in our study. In each feeding trial, each diet was randomly assigned to triplicate tanks. Fish were fed one of the tested diets up to satiation twice daily. The results showed that gls1 expression increased in 32% protein group and decreased in 35–41% protein group. The results of different protein source experiments showed that the expression of gls1 gene in the mixed protein group (the control group) was significantly higher than that in the fish meal and soybean meal groups. Glutamate treatment revealed that appropriate concentrations (0.10 mg/mL in vivo and 2.00% in vitro) of glutamate remarkably improved the expression of gls1. Besides, diets supplemented with 0.80–1.60% lysine-glutamate dipeptide exhibited a down regulatory impact on gls1 expression. In conclusion, this study demonstrated that the expression of gls1 in TCC was increased by 32% protein diet, mixed protein source diet and diet with 2.00% glutamate concentration, while decreased by 0.80–1.60% lysine-glutamate dipeptide. The findings of this study provide a reference for the regulation of gls1 and have a potential application in the optimization of dietary formula in aquaculture.

Machine Learning-Enabled Determination of Diffuseness of Brain Arteriovenous Malformations from Magnetic Resonance Angiography - Yuming Jiao; Jun-Ze Zhang; Qi Zhao; Jia-Qi Liu; Zhen-Zhou Wu; Yan Li; Hao Li; Wei-Lun Fu; Jian-Cong Weng; Ran Huo; Shao-Zhi Zhao; Shuo Wang; et al. (Translational Stroke Research, 2022)

Oxygen vacancy engineering of photocatalytic nanomaterials for enrichment, activation, and efficient removal of nitrogen oxides with high selectivity: a review - Yanfeng Lu; Meijuan Chen; Liu Jiang; Jun-ji Cao; Haiwei Li; Shun Cheng Lee; Yu Huang (Environmental Chemistry Letters, 2022)

CACNA1C-AS2 inhibits cell proliferation and suppresses cell migration and invasion via targeting FBXO45 and PI3K/AKT/mTOR pathways in glioma - Tong Cao; Yue Cui; Yingying Wang; Linhui Wu; Ke Yu; Kai Chen; Jun Xia; Yuyun Li; Zhiwei Peter Wang; Jia Ma (Apoptosis, 2022)

GDH promotes isoprenaline-induced cardiac hypertrophy by activating mTOR signaling via elevation of α-ketoglutarate level - Zhi-Rong Lin; Zhen-Zhen Li; Yan-Jun Cao; Wen-Jing Yu; Jian-Tao Ye; Pei-Qing Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Expression patterns and correlation analyses of muscle-specific genes in the process of sheep myoblast differentiation - Hejie Wang; Minmin Dou; Jun Li; Peng Cao; Junling Li; Tianyan Guo; Dipeng Zhao; Ajab Khan; Yingliang Li; Baojun Li; Jian Qin; Rong Du (In Vitro Cellular & Developmental Biology - Animal, 2022)

Oceanobacillus saliphilus sp. nov., Isolated from Saline−Alkali Soil in Heilongjiang Province, China - Yu-Ting OuYang; Meng-Meng Li; Ai-Ping Lv; Pin-Jiao Jin; Lan Liu; Ze-Tao Liu; Jian-Yu Jiao; Wen-Jun Li; Li-Xiang Cao; Shuang Wang (Current Microbiology, 2022)

Siccirubricoccus soli sp. nov., a novel bacterial species isolated from Jiaozi Mountain soil - Guo-Xing Zhu; Ya-Jie Wu; Yan-Ru Cao; Bing-Jun Fan; Yu Jiao; Xiu-Li Hou; Zi-Chao Liu; Yue Zhang; Jiang-Bo He; Lian-Ming Liang (Antonie van Leeuwenhoek, 2022)

Genome-wide association study reveals a NAC transcription factor TaNAC074 linked to pre-harvest sprouting tolerance in wheat - Hao Jiang; Yu Fang; Dong Yan; Si-tong Liu; Jun Wei; Fei-long Guo; Xing-ting Wu; Hong Cao; Chang-bin Yin; Fei Lu; Li-feng Gao; Yong-xiu Liu (Theoretical and Applied Genetics, 2022)

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Improving protected area effectiveness through consideration of different human‐pressure baselines - Chun‐Ting Feng; Ming Cao; Fang‐Zheng Liu; Yue Zhou; Jin‐Hong Du; Li‐Bo Zhang; Wen‐Jie Huang; Jian‐Wu Luo; Jun‐Sheng Li; Wei Wang (Conservation Biology, 2022)
Previous assessments of the effectiveness of protected areas (PAs) focused primarily on changes in human pressure over time and did not consider the different human‐pressure baselines of PAs, thereby potentially over‐ or underestimating PA effectiveness. We developed a framework that considers both human‐pressure baseline and change in human pressure over time and assessed the effectiveness of 338 PAs in China from 2010 to 2020. The initial state of human pressure on PAs was taken as the baseline, and changes in human pressure index (HPI) were further analyzed under different baselines. We used the random forest models to identify the management measures that most improved effectiveness in resisting human pressure for the PAs with different baselines. Finally, the relationships between the changes in the HPI and the changes in natural ecosystems in PAs were analyzed with different baselines. Of PAs with low HPI baselines, medium HPI baselines, and high HPI baselines, 76.92% ( n =150), 11.11% ( n =12), and 22.86% ( n =8) , respectively, showed positive effects in resisting human pressure. Overall, ignoring human‐pressure baselines somewhat underestimated the positive effects of PAs, especially for those with low initial human pressure. For PAs with different initial human pressures, different management measures should be taken to improve effectiveness and reduce threats to natural ecosystems. We believe our framework is useful for assessing the effectiveness of PAs globally, and we recommend it be included in the Convention on Biological Diversity Post‐2020 Strategy.

Evaluating the effectiveness of three national marine protected areas in the Yangtze River Delta, China - Xu Zeng; Jun Liang; Jiangning Zeng; Mingyang Chen; Cong Zeng; Makenzie Mazur; Shenghui Li; Zengjie Zhou; Wei Ding; Peng Ding; Ling Cao (Frontiers in Marine Science, 2022)
China’s coastal areas face serious environmental degradation as a consequence of large-scale economic development. To balance environmental sustainability with economic development, China is currently implementing a strategy of ‘eco-civilization’, with marine protected areas (MPAs) expected to be one approach to achieving sustainable marine ecosystems. Since the 1990s, China has established over 270 MPAs, but their effectiveness remains unknown, particularly in the Yangtze River Delta. This study modified pre-existing frameworks to evaluate the effectiveness of three national MPAs in the Yangtze River Delta. The modified framework includes conservation outcomes and their potential drivers. Drivers consist of – attributes species or ecosystems within the MPA, attributes of the MPA, institutional design principles, and participation. Five scenarios were proposed based on score combinations of the four drivers: proactive, well designed, well governed, interactive, and learning. All three MPAs achieved a satisfactory level of outcomes and most of the drivers for all three MPAs achieved a satisfactory level. Two of the MPAs were categorized into the learning scenario, and the third into the well-designed scenario, indicating that there is still room to improve institutional design principles and public participation. We suggest developing cost and benefit indicators to more deeply understand proportionality among stakeholders. In addition, the role of participation should be clarified and promoted. We recommend regular environmental performance monitoring and assessment to identify problems and optimize management.

Identification of a major stable QTL for spikelet number in wheat (Triticum aestivum L.) and its genetic effects analysis on yield-related traits - Mingsu Cao; Jizi Dong; Hao Wang; Yibiao Cai; Tianhang Ma; Xiaohan Zhou; Jingguo Xiao; Shihui Li; Linqu Chen; Huiyuan Xu; Chunhua Zhao; Yongzhen Wu; et al. (Euphytica, 2022)

Two-stage Bayesian experimental design optimization for measuring soil–water characteristic curve - Shao-Lin Ding; Dian-Qing Li; Zi-Jun Cao; Wenqi Du (Bulletin of Engineering Geology and the Environment, 2022)

Transcriptomic and Metabolomic Analyses Provide Insights into the Growth and Development Advantages of Triploid Apostichopus japonicus - Jiahui Xie; Yi Sun; Yue Cao; Lingshu Han; Yuanxin Li; Beichen Ding; Chuang Gao; Pengfei Hao; Xin Jin; Yaqing Chang; Jian Song; Donghong Yin; et al. (Marine Biotechnology, 2022)
Polyploid breeding is widely used in aquaculture as an important area of new research. We have previously grown Apostichopus japonicus triploids with a growth advantage. The body length, body weight, and aestivation time of triploid and diploid A. japonicus were measured in this study, and the transcriptome and metabolome were used to examine the growth advantage of triploids A. japonicus . The results showed that the proportion of triploid A. japonicus with a body length of 6–12 cm and 12–18 cm was significantly higher than that of diploid A. japonicus , and triploid A. japonicus had a shorter aestivation time (39 days) than diploid (63 days). We discovered 3296 differentially expressed genes (DEGs); 13 DEGs (for example, cyclin-dependent kinase 2 ) related to growth advantage, immune regulation, and energy storage were screened as potential candidates. According to Gene Ontology (GO) enrichment analysis, DEGs were significantly enriched in the cytoplasm (cellular component), ATP binding process (molecular function), oxidation–reduction process (biological process), and other pathways. According to the Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment data, DEGs were significantly enriched in ribosome production and other areas. We discovered 414 significant differential metabolites (SDMs), with 11 important SDMs (for example, nocodazole) linked to a growth advantage. SDMs are significantly enriched in metabolic pathways, as well as other pathways, according to the KEGG enrichment results. According to a combined transcriptome and metabolome analysis, 6 DEGs have regulatory relationships with 11 SDMs, which act on 11 metabolic pathways together. Our results further enrich the biological data of triploid A. japonicus and provide useful resources for genetic improvement of this species.

Fruit and vegetable consumption, cardiovascular disease, and all-cause mortality in China - Jun Wang; Fangchao Liu; Jianxin Li; Keyong Huang; Xueli Yang; Jichun Chen; Xiaoqing Liu; Jie Cao; Shufeng Chen; Chong Shen; Ling Yu; Fanghong Lu; et al. (Science China Life Sciences, 2022)

Temperature might increase the hospital admission risk for rheumatoid arthritis patients in Anqing, China: a time-series study - Li-Juan Huang; Jun-Jing Zha; Nv-Wei Cao; Hao-Yue Zhou; Xiu-Jie Chu; Hua Wang; Xian-Bao Li; Bao-Zhu Li (International Journal of Biometeorology, 2022)

The Effects of Limosilactobacillus reuteri LR-99 Supplementation on Body Mass Index, Social Communication, Fine Motor Function, and Gut Microbiome Composition in Individuals with Prader–Willi Syndrome: a Randomized Double-Blinded Placebo-Controlled Trial - Xue-Jun Kong; Kevin Liu; Patrick Zhuang; Ruiyi Tian; Siyu Liu; Cullen Clairmont; Xiaojing Lin; Hannah Sherman; Junli Zhu; Yelan Wang; Michelle Fong; Alice Li; et al. (Probiotics and Antimicrobial Proteins, 2021)
Prader–Willi syndrome (PWS) is a rare genetic disorder associated with developmental delay, obesity, and neuropsychiatric comorbidities. Limosilactobacillus reuteri ( Lactobacillus reuteri , Lact. reuteri ) has demonstrated anti-obesity and anti-inflammatory effects in previous studies. In the present study, we aim to evaluate the effects of Lact. reuteri supplementation on body mass index (BMI), social behaviors, and gut microbiota in individuals with PWS. We conducted a 12-week, randomized, double-blind, placebo-controlled trial in 71 individuals with PWS aged 6 to 264 months (64.4 ± 51.0 months). Participants were randomly assigned to either receive daily Lact. reuteri LR-99 probiotic (6 × 10 10 colony forming units) or a placebo sachet. Groupwise differences were assessed for BMI, ASQ-3, and GARS-3 at baseline, 6 weeks, and 12 weeks into treatment. Gut microbiome data was analyzed with the QIIME2 software package, and predictive functional profiling was conducted with PICRUSt-2. We found a significant reduction in BMI for the probiotic group at both 6 weeks and 12 weeks relative to the baseline ( P < 0.05). Furthermore, we observed a significant improvement in social communication and interaction, fine motor function, and total ASQ-3 score in the probiotics group compared to the placebo group ( P < 0.05). Altered gut microbiota was observed in the probiotic group to favor weight loss and improve gut health. The findings suggest a novel therapeutic potential for Lact. reuteri LR-99 probiotic to modulate BMI, social behaviors, and gut microbiota in Prader–Willi syndrome patients, although further investigation is warranted. Trial registration Chinese Clinical Trial Registry: ChiCTR1900022646

Fine mapping and validation of a major QTL for grain weight on chromosome 5B in bread wheat - Dehui Zhao; Li Yang; Dan Liu; Jianqi Zeng; Shuanghe Cao; Xianchun Xia; Jun Yan; Xiyue Song; Zhonghu He; Yong Zhang (Theoretical and Applied Genetics, 2021)

Cytochalasins from endophytic Diaporthe sp. GDG-118 - Xishan Huang; Dexiong Zhou; Yan Liang; Xiaobo Liu; Fei Cao; Yuyue Qin; Tuxiang Mo; Zhaolong Xu; Jun Li; Ruiyun Yang (Natural Product Research, 2021)

Daily Streamflow Forecasting Based on Flow Pattern Recognition - Fang-Fang Li; Han Cao; Chun-Feng Hao; Jun Qiu (Water Resources Management, 2021)

Expanding the scope of genome editing with SpG and SpRY variants in rice - Jun Ren; Xiangbing Meng; Fengyue Hu; Qing Liu; Yuexuan Cao; Huiying Li; Changjie Yan; Jiayang Li; Kejian Wang; Hong Yu; Chun Wang (Science China Life Sciences, 2021)

Food-grade γ-aminobutyric acid production by immobilized glutamate decarboxylase from Lactobacillus plantarum in rice vinegar and monosodium glutamate system - Li-Li Yao; Jia-Ren Cao; Chang-Jiang Lyu; Fang-Fang Fan; Hong-Peng Wang; Hong-Wei Cao; Jun Huang; Le-He Mei (Biotechnology Letters, 2021)

Geochemistry, geochronology, and zircon Hf isotopic compositions of felsite porphyry in Xiangshan uranium orefield and its geological implication - Mingming Tian; Ziying Li; Jiangtao Nie; Jun Zhong; Jian Wang; Jianhui Cao (Acta Geochimica, 2021)

Descending Modulation of Spinal Itch Transmission by Primary Somatosensory Cortex - Zi-Han Wu; Han-Yu Shao; Yuan-Yuan Fu; Xiao-Bo Wu; De-Li Cao; Sheng-Xiang Yan; Wei-Lin Sha; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)

Diversity of microbial community and its metabolic potential for nitrogen and sulfur cycling in sediments of Phu Quoc island, Gulf of Thailand - Ngoc Tung Quach; Hang Thuy Dam; Dinh Man Tran; Thi Hanh Nguyen Vu; Quoc Viet Nguyen; Kim Thoa Nguyen; Quang Huy Nguyen; Cao Bang Phi; Thanh Ha Le; Hoang Ha Chu; Van Thuoc Doan; Douglas J. H. Shyu; et al. (Brazilian Journal of Microbiology, 2021)

Local climate adaptation and gene flow in the native range of two co‐occurring fruit moths with contrasting invasiveness - Li‐Jun Cao; Bing‐Yan Li; Jin‐Cui Chen; Jia‐Ying Zhu; Ary A. Hoffmann; Shu‐Jun Wei (Molecular Ecology, 2021)
Invasive species pose increasing threats to global biodiversity and ecosystems. While previous studies have characterized successful invaders based on ecological traits, characteristics related to evolutionary processes have rarely been investigated. Here we compared gene flow and local adaptation using demographic analyses and outlier tests in two co‐occurring moth pests across their common native range of China, one of which (the peach fruit moth, Carposina sasakii ) has maintained its native distribution, while the other (the oriental fruit moth, Grapholita molesta ) has expanded its range globally during the past century. We found that both species showed a pattern of genetic differentiation and an evolutionary history consistent with a common southwestern origin and northward expansion in their native range. However, for the noninvasive species, genetic differentiation was closely aligned with the environment, and there was a relatively low level of gene flow, whereas in the invasive species, genetic differentiation was associated with geography. Genome scans indicated stronger patterns of climate‐associated loci in the noninvasive species. While strong local adaptation and reduced gene flow across its native range may have decreased the invasiveness of C . sasakii , this requires further validation with additional comparisons of invasive and noninvasive species across their native range.

Proteomics provides individualized options of precision medicine for patients with gastric cancer - Wenwen Huang; Dongdong Zhan; Yazhuo Li; Nairen Zheng; Xin Wei; Bin Bai; Kecheng Zhang; Mingwei Liu; Xuefei Zhao; Xiaotian Ni; Xia Xia; Jinwen Shi; et al. (Science China Life Sciences, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Altered structural and functional connectivity in CSF1R-related leukoencephalopathy - Fei-Xia Zhan; Ze-Yu Zhu; Qing Liu; Hai-Yan Zhou; Xing-Hua Luan; Xiao-Jun Huang; Xiao-Li Liu; Wo-Tu Tian; Shi-Ge Wang; Xiao-Xuan Song; Guang Chen; Ming-Liang Zhao; et al. (Brain Imaging and Behavior, 2021)

KCNQ Channels in the Mesolimbic Reward Circuit Regulate Nociception in Chronic Pain in Mice - Hao-Ran Wang; Su-Wan Hu; Song Zhang; Yu Song; Xiao-Yi Wang; Lei Wang; Yang-Yang Li; Yu-Mei Yu; He Liu; Di Liu; Hai-Lei Ding; Jun-Li Cao (Neuroscience Bulletin, 2021)
Mesocorticolimbic dopaminergic (DA) neurons have been implicated in regulating nociception in chronic pain, yet the mechanisms are barely understood. Here, we found that chronic constructive injury (CCI) in mice increased the firing activity and decreased the KCNQ channel-mediated M-currents in ventral tegmental area (VTA) DA neurons projecting to the nucleus accumbens (NAc). Chemogenetic inhibition of the VTA-to-NAc DA neurons alleviated CCI-induced thermal nociception. Opposite changes in the firing activity and M-currents were recorded in VTA DA neurons projecting to the medial prefrontal cortex (mPFC) but did not affect nociception. In addition, intra-VTA injection of retigabine, a KCNQ opener, while reversing the changes of the VTA-to-NAc DA neurons, alleviated CCI-induced nociception, and this was abolished by injecting exogenous BDNF into the NAc. Taken together, these findings highlight a vital role of KCNQ channel-mediated modulation of mesolimbic DA activity in regulating thermal nociception in the chronic pain state.

The Association Between Insular Subdivisions Functional Connectivity and Suicide Attempt in Adolescents and Young Adults with Major Depressive Disorder - Lan Hu; Muni Xiao; Jun Cao; Zhaojun Tan; Mengyao Wang; Li Kuang (Brain Topography, 2021)

TLR8 in the Trigeminal Ganglion Contributes to the Maintenance of Trigeminal Neuropathic Pain in Mice - Lin-Xia Zhao; Ming Jiang; Xue-Qiang Bai; De-Li Cao; Xiao-Bo Wu; Jing Zhang; Jian-Shuang Guo; Tong-Tong Chen; Juan Wang; Hao Wu; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)
Trigeminal neuropathic pain (TNP) is a significant health problem but the involved mechanism has not been completely elucidated. Toll-like receptors (TLRs) have recently been demonstrated to be expressed in the dorsal root ganglion and involved in chronic pain. Here, we show that TLR8 was persistently increased in the trigeminal ganglion (TG) neurons in model of TNP induced by partial infraorbital nerve ligation (pIONL). In addition, deletion or knockdown of Tlr8 in the TG attenuated pIONL-induced mechanical allodynia, reduced the activation of ERK and p38-MAPK, and decreased the expression of pro-inflammatory cytokines in the TG. Furthermore, intra-TG injection of the TLR8 agonist VTX-2337 induced pain hypersensitivity. VTX-2337 also increased the intracellular Ca 2+ concentration, induced the activation of ERK and p38, and increased the expression of pro-inflammatory cytokines in the TG. These data indicate that TLR8 contributes to the maintenance of TNP through increasing MAPK-mediated neuroinflammation. Targeting TLR8 signaling may be effective for the treatment of TNP.

Genome-wide linkage mapping for canopy activity related traits using three RIL populations in bread wheat - Faji Li; Weie Wen; Jindong Liu; Shengnan Zhai; Xinyou Cao; Cheng Liu; Dungong Cheng; Jun Guo; Yan Zi; Ran Han; Xiaolu Wang; Aifeng Liu; et al. (Euphytica, 2021)

Down-regulation of MANNANASE7 gene in Brassica napus L. enhances silique dehiscence-resistance - Yu-Long Li; Yan-Kun Yu; Ke-Ming Zhu; Li-Na Ding; Zheng Wang; Yan-Hua Yang; Jun Cao; Li-Zhang Xu; Yao-Ming Li; Xiao-Li Tan (Plant Cell Reports, 2021)

First report of Chaetomella raphigera causing brown spot on Eucalyptus urophylla × E. grandis in China - Xiu-Xiu Cao; Ji-Guang Wei; Jian-Gan Hou; Chun-Li Fan; Ji Luo; Yao-Jun Wu; Xiu-Hao Yang; Ji-Tong Luo; Xiao-Bing Yang (Journal of Plant Pathology, 2021)

Effects of Different Component Contents of Colistin Methanesulfonate on the Pharmacokinetics of Prodrug and Formed Colistin in Human - Ya-Xin Fan; Yuan-Cheng Chen; Yi Li; Ji-Cheng Yu; Xing-Chen Bian; Xin Li; Wan-Zhen Li; Bei-Ning Guo; Hai-Lan Wu; Xiao-Fen Liu; Yu Wang; Xiao-Yong Xu; et al. (Pharmaceutical Research, 2021)

Effect of elevated CO2 on the population development of the invasive species Frankliniella occidentalis and native species Thrips hawaiiensis and activities of their detoxifying enzymes - Yu Cao; Hong Yang; Yulin Gao; Lijuan Wang; Jun Li; Chun Wang; Can Li (Journal of Pest Science, 2021)

Geographical and interspecific variation in susceptibility of three common thrips species to the insecticide, spinetoram - Yong-Fu Gao; Ya-Jun Gong; Li-Jun Cao; Jin-Cui Chen; Yu-Lin Gao; Majid Mirab-balou; Min Chen; Ary A. Hoffmann; Shu-Jun Wei (Journal of Pest Science, 2021)

Allotransplantation of adult spinal cord tissues after complete transected spinal cord injury: Long-term survival and functional recovery in canines - He Shen; Shuyu Wu; Xi Chen; Bai Xu; Dezun Ma; Yannan Zhao; Yan Zhuang; Bing Chen; Xianglin Hou; Jiayin Li; Yudong Cao; Xianyong Fu; et al. (Science China Life Sciences, 2020)

The Beneficial Effects of Aluminum on the Plant Growth in Camellia japonica - Yuanjiao Liu; Jingyu Tao; Jing Cao; Yaping Zeng; Xi Li; Jun Ma; Zhuo Huang; Mingyan Jiang; Lingxia Sun (Journal of Soil Science and Plant Nutrition, 2020)

Identification and validation of genetic loci for tiller angle in bread wheat - Dehui Zhao; Li Yang; Kaijie Xu; Shuanghe Cao; Yubing Tian; Jun Yan; Zhonghu He; Xianchun Xia; Xiyue Song; Yong Zhang (Theoretical and Applied Genetics, 2020)

Biogenic Silica Composition and Storage in the Yellow River Delta Wetland with Implications for the Carbon Preservation - Jun Liu; Zhaoliang Song; Jianbu Wang; Alexander F. Bouwman; Menglu Li; Sen Liu; Lei Cao; Jiaye Zang; Xiangbin Ran (Wetlands, 2020)

Comparative iTRAQ Proteomics Reveals Multiple Effects of Selenium Yeast on Dairy Cows in Parturition - Zhi-hua Ren; Li-peng Bai; Liu-hong Shen; Zheng-zhong Luo; Zi-han Zhou; Zhi-cai Zuo; Xiao-ping Ma; Jun-liang Deng; Ya Wang; Sheng-yu Xu; Yu-heng Luo; Sui-zhong Cao; et al. (Biological Trace Element Research, 2020)

Increased density of endosymbiotic Buchnera related to pesticide resistance in yellow morph of melon aphid - Shao-Kun Guo; Ya-Jun Gong; Jin-Cui Chen; Pan Shi; Li-Jun Cao; Qiong Yang; Ary Anthony Hoffmann; Shu-Jun Wei (Journal of Pest Science, 2020)

Application of confocal laser Raman spectroscopy on marine sediment microplastics - Jing Liu; Xin Zhang; Zengfeng Du; Zhendong Luan; Lianfu Li; Shichuan Xi; Bing Wang; Lei Cao; Jun Yan (Journal of Oceanology and Limnology, 2020)

Ectopic expression of an oat SnRK2 gene, AsSnRK2D, enhances dehydration and salinity tolerance in tobacco by modulating the expression of stress-related genes - Dian-Jun Xiang; Li-Li Man; Shuai Cao; Peng Liu; Zhi-Gang Li; Xiao-Dong Wang (Brazilian Journal of Botany, 2020)

Complete genome sequences of two novel genotypes of Citrus tristeza virus infecting Poncirus trifoliata in China - Jun Wang; Tianyu Zhou; Pan Shen; Song Zhang; Mengji Cao; Yan Zhou; Zhongan Li (Journal of Plant Pathology, 2020)

Genome-wide identification of the NPR1-like gene family in Brassica napus and functional characterization of BnaNPR1 in resistance to Sclerotinia sclerotiorum - Zheng Wang; Lu-Yue Ma; Xiao Li; Feng-Yun Zhao; Rehman Sarwar; Jun Cao; Yu-Long Li; Li-Na Ding; Ke-Ming Zhu; Yan-Hua Yang; Xiao-Li Tan (Plant Cell Reports, 2020)

Effects of High-Fat Diet on Steatosis, Endoplasmic Reticulum Stress and Autophagy in Liver of Tilapia (Oreochromis niloticus) - Rui Jia; Li-Ping Cao; Jin-Liang Du; Qin He; Zheng-Yan Gu; Galina Jeney; Pao Xu; Guo-Jun Yin (Frontiers in Marine Science, 2020)

Climate change impacts on extreme energy consumption of office buildings in different climate zones of China - Mingcai Li; Jun Shi; Jingfu Cao; Xiaoyi Fang; Min Wang; Xin Wang (Theoretical and Applied Climatology, 2020)

NK cell reconstitution following unmanipulated HLA-mismatched/haploidentical transplantation compared with matched sibling transplantation - Li-Juan Hu; Xun-Hong Cao; Xing-Xing Yu; Xue-Fei Liu; Xiao-Su Zhao; Ying-Jun Chang; Xiao-Hui Zhang; Lan-Ping Xu; Yu Wang; Kai-Yan Liu; Xiao-Jun Huang; Xiang-Yu Zhao (Science China Life Sciences, 2020)

Effective Therapeutic Drug Delivery by GALA3, an Endosomal Escape Peptide with Reduced Hydrophobicity - Chen Li; Xue-Wei Cao; Jian Zhao; Fu-Jun Wang (The Journal of Membrane Biology, 2020)

Correction to: AVE0991, a nonpeptide angiotensin-(1–7) mimic, inhibits angiotensin II–induced abdominal aortic aneurysm formation in apolipoprotein E knockout mice - Hui Ma; Yu-Lin Wang; Nai-Hao Hei; Jun-Long Li; Xin-Ran Cao; Bo Dong; Wen-jiang Yan (Journal of Molecular Medicine, 2020)

AVE0991, a nonpeptide angiotensin-(1–7) mimic, inhibits angiotensin II–induced abdominal aortic aneurysm formation in apolipoprotein E knockout mice - Hui Ma; Yu-Lin Wang; Nai-Hao Hei; Jun-Long Li; Xin-Ran Cao; Bo Dong; Wen-jiang Yan (Journal of Molecular Medicine, 2020)

Preparation of Novel ALRCs/nZVI Composite and Its Removal of Cr(VI) from Aqueous - Xuan Zhang; Xiao-qiang Cao; Guang Li; Jijie Yin; Di Zhang; Mingzhen Li; Na Meng; Liang Dong; Xian-jun Lyu; Lin Li; Jun Qiu; Yan Zhang; et al. (International Journal of Environmental Research, 2020)

Optimal water and land resource allocation in pastoral areas based on a water–land forage–livestock balance: a case study of Otog Front Banner, Inner Mongolia, China - Haiyuan Lu; Heping Li; Jun Wang; Hexiang Zheng; Xuesong Cao; Changfu Tong (Environmental Science and Pollution Research, 2020)

microRNA-499a promotes the progression and chemoresistance of cervical cancer cells by targeting SOX6 - Yibing Chen; Yucen Song; Yanjun Mi; Huan Jin; Jun Cao; Haolong Li; Liping Han; Ting Huang; Xiaofei Zhang; Shumin Ren; Qian Ma; Zhengzhi Zou (Apoptosis, 2020)

QTL mapping for grain yield-related traits in bread wheat via SNP-based selective genotyping - Li Yang; Dehui Zhao; Zili Meng; Kaijie Xu; Jun Yan; Xianchun Xia; Shuanghe Cao; Yubing Tian; Zhonghu He; Yong Zhang (Theoretical and Applied Genetics, 2020)

An on-demand construction method of disaster scenes for multilevel users - Weilian Li; Jun Zhu; Yunhao Zhang; Lin Fu; Yuhang Gong; Ya Hu; Yungang Cao (Natural Hazards, 2020)

Identifying common genome-wide risk genes for major psychiatric traits - Sha Liu; Shuquan Rao; Yong Xu; Jun Li; Hailiang Huang; Xu Zhang; Hui Fu; Qiang Wang; Hongbao Cao; Ancha Baranova; Chunhui Jin; Fuquan Zhang (Human Genetics, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

Integrated experiments on field monitoring and hydro-mechanical modeling for determination of a triggering threshold of rainfall-induced shallow landslides. A case study in Ren River catchment, China - Xinsheng Wei; Wen Fan; Yanbo Cao; Xiaoqing Chai; Massimiliano Bordoni; Claudia Meisina; Jun Li (Bulletin of Engineering Geology and the Environment, 2020)

Effect of Dietary Selenium Supplementation on Growth and Reproduction of Silkworm Bombyx mori L. - Li Jiang; Li-Li Peng; Yu-Yao Cao; Kiran Thakur; Fei Hu; Shun-Ming Tang; Zhao-Jun Wei (Biological Trace Element Research, 2020)

CD271 promotes STZ-induced diabetic wound healing and regulates epidermal stem cell survival in the presence of the pTrkA receptor - Min Zhang; Rui Zhang; Xiaohong Li; Yongqian Cao; Kaifeng Huang; Jun Ding; Mengyao Liu; Zhang Feng; Siyuan Yin; Jiaxu Ma; Huayu Zhang; Yibing Wang (Cell and Tissue Research, 2020)

Multi‐model analysis of climate impacts on plant photosynthesis in China during 2000–2015 - Hao Yan; Shao‐Qiang Wang; Jun‐Bang Wang; Yun Cao; Ling‐Ling Xu; Men‐Xin Wu; Lu Cheng; Liu‐Xi Mao; Feng‐Hua Zhao; Xian‐Zhou Zhang; Yun‐Fen Liu; Yan‐Fen Wang; et al. (International Journal of Climatology, 2019)
Differences, arising from differences in gross primary production (GPP) model structures and driving forces, have fuelled arguments concerning interannual changes of GPP in China since 2000. To better investigate the interannual variability of GPP and its covariance with climate factors in China, this study adopted a multi‐model analysis based on three GPP models (i.e., Terrestrial Ecosystem Carbon flux model [TEC], Breathing Earth System Simulator model [BESS], and MOD17 GPP model). The results show that annual GPP in China increased by 0.021–0.057 Pg C year −1 from 2000 to 2015 attributable to atmospheric‐CO 2 fertilization effects and favourable climate change, that is, increasing precipitation ( P r ) and temperature ( T a ). However, northern China and southern China had a large difference in the amplitude of these GPP changes; annual GPP increased by 0.017–0.039 Pg C year −1 in northern China but only 0.001–0.018 Pg C year −1 in southern China. Northern China and southern China occupy contrasting climate zones and this contrast produced different interannual variability of GPP through different mechanisms. Northern China has a dry climate with GPP changes sensitive to P r . As a result, more P r along with higher T a in northern China produced the strong uptrend of GPP from 2000 to 2015. In contrast, southern China has a wet climate with its GPP sensitive to solar radiation and T a . For the interval of 2000–2015, decreasing radiation plus drought exerted a negative influence on GPP in southern China. This study highlights the diverse mechanisms in which climate change affects GPP in dry and wet climate zones. A robust multi‐model analysis is preferred to reduce uncertainties arising from a single GPP model and its driving data.

Insights into transcriptional characteristics and homoeolog expression bias of embryo and de-embryonated kernels in developing grain through RNA-Seq and Iso-Seq - Jun Wei; Hong Cao; Jing-dong Liu; Jing-hong Zuo; Yu Fang; Chih-Ta Lin; Run-ze Sun; Wen-long Li; Yong-xiu Liu (Functional & Integrative Genomics, 2019)

An expanded allometric model for crowns of four co-existing desert shrubs - Xin-Jun Zheng; Yu-Gang Wang; Xue Wu; Wen Ren; Yu Wu; Yan Li; Xun Cao; Jie Ma; Hai Zhou (Trees, 2019)

Effects of dietary protein level on growth performance, digestive enzyme activity, and gene expressions of the TOR signaling pathway in fingerling Pelteobagrus fulvidraco - Qin Qin; Xiu-Fei Cao; Yong-jun Dai; Li-Na Wang; Ding-Dong Zhang; Guang-Zhen Jiang; Wen-Bin Liu (Fish Physiology and Biochemistry, 2019)

Extraction and Physicochemical Characterization of Pepsin Soluble Collagens from Golden Pompano ( Trachinotus blochii ) Skin and Bone - Jun Cao; Qingfei Duan; Xiaoyan Liu; Xuanri Shen; Chuan Li (Journal of Aquatic Food Product Technology, 2019)

Recent Developments in Local Wave Decomposition Methods for Understanding Seismic Data: Application to Seismic Interpretation - Ya-juan Xue; Jun-xing Cao; Xing-jian Wang; Ying-xiang Li; Jiang Du (Surveys in Geophysics, 2019)

An MAP kinase interacts with LHK1 and regulates nodule organogenesis in Lotus japonicus - Jun Yin; Xiaomin Guan; Heng Zhang; Longxiang Wang; Hao Li; Qing Zhang; Tao Chen; Zeyuan Xu; Zonglie Hong; Yangrong Cao; Zhongming Zhang (Science China Life Sciences, 2019)

Advances in plant GDSL lipases: from sequences to functional mechanisms - Li-Na Ding; Ming Li; Wei-Jie Wang; Jun Cao; Zheng Wang; Ke-Ming Zhu; Yan-Hua Yang; Yu-Long Li; Xiao-Li Tan (Acta Physiologiae Plantarum, 2019)

Complete Genome Sequence of Actinosynnema pretiosum X47, An Industrial Strain that Produces the Antibiotic Ansamitocin AP-3 - Chuanqing Zhong; Gongli Zong; Shulan Qian; Meng Liu; Jiafang Fu; Peipei Zhang; Jun Li; Guangxiang Cao (Current Microbiology, 2019)

Isochromanes from Aspergillus fumigatus , an endophytic fungus from Cordyceps sinensis - Xiao-Hua Li; Xue-Hua Han; Ling-Ling Qin; Jun-Lin He; Zhi-Xing Cao; Yu-Cheng Gu; Da-Le Guo; Yun Deng (Natural Product Research, 2019)

Potassium ameliorates iron deficiency by facilitating the remobilization of iron from root cell walls and promoting its translocation from roots to shoots - Yi Quan Ye; Hong Yan Luo; Mao Li; Jia Jun Zhang; Guang Qiu Cao; Kai Min Lin; Si Zu Lin; Shan Shan Xu (Plant and Soil, 2019)

Eremophilane sesquiterpenes from the endophytic fungus Xylaria sp. GDG-102 - Yan Liang; Weifeng Xu; Chengmei Liu; Dexiong Zhou; Xiaobo Liu; Yuyue Qin; Fei Cao; Jun Li; Ruiyun Yang; Jiangke Qin (Natural Product Research, 2019)

Geochronology, geochemistry and Sr-Nd-Pb-Hf isotopes of the Early Paleogene gabbro and granite from Central Lhasa, southern Tibet: petrogenesis and tectonic implications - Yun-hui Zhang; Hua-wen Cao; Steven P. Hollis; Li Tang; Mo Xu; Jun-sheng Jiang; Shun-bao Gao; Yang-shuang Wang (International Geology Review, 2019)

Correction to: First report of citrus tristeza virus trifoliate resistance-breaking (RB) genotype in Citrus grandis in China - Jun Wang; Tianyu Zhou; Mengji Cao; Yan Zhou; Zhongan Li (Journal of Plant Pathology, 2019)

First report of citrus tristeza virus trifoliate resistance-breaking (RB) genotype in Citrus grandis in China - Jun Wang; Tianyu Zhou; Mengji Cao; Yan Zhou; Zhongan Li (Journal of Plant Pathology, 2019)

Field-evolved resistance and cross-resistance of the two-spotted spider mite, Tetranychus urticae, to bifenazate, cyenopyrafen and SYP-9625 - Jin-Cui Chen; Ya-Jun Gong; Pan Shi; Ze-Hua Wang; Li-Jun Cao; Peng Wang; Shu-Jun Wei (Experimental and Applied Acarology, 2019)

Hsc70 Interacts with β4GalT5 to Regulate the Growth of Gliomas - Guan Sun; Ying Cao; Xueliang Dai; Min Li; Jun Guo (NeuroMolecular Medicine, 2019)

Distributions and environmental drivers of archaea and bacteria in paddy soils - Chao-Lei Yuan; Li-Mei Zhang; Jun-Tao Wang; Hang-Wei Hu; Ju-Pei Shen; Peng Cao; Ji-Zheng He (Journal of Soils and Sediments, 2019)

Genetic characteristics of the P1 coding region of Coxsackievirus A16 associated with hand, foot, and mouth disease in China - Li Xu; Dawei Cui; Lei Wang; Jun Cheng; Changgui Sun; Lanjuan Li; Hongcui Cao (Molecular Biology Reports, 2018)

Tsmu solution improves rabbit osteochondral allograft preservation and transplantation outcome - Famin Cao; Jianhong Qi; Hongqiang Song; Di Xie; Lu Zhou; Yunning Han; Hao Li; Qi Wu; Jun Dong; Yanming Zhang (Cell and Tissue Banking, 2018)

A new Tanay virus isolated from mosquitoes in Guangxi, China - Jinglin Wang; Jianming Wu; Nan Li; Yingying Cao; Yuwen He; Jun Lin; Huachun Li (Archives of Virology, 2018)

Preference and performance of the two-spotted spider mite Tetranychus urticae (Acari: Tetranychidae) on strawberry cultivars - Ya-Jun Gong; Jin-Cui Chen; Liang Zhu; Li-Jun Cao; Gui-Hua Jin; Ary A. Hoffmann; Chuan-Fei Zhong; Peng Wang; George Lin; Shu-Jun Wei (Experimental and Applied Acarology, 2018)

Genome-wide linkage mapping of yield-related traits in three Chinese bread wheat populations using high-density SNP markers - Faji Li; Weie Wen; Zhonghu He; Jindong Liu; Hui Jin; Shuanghe Cao; Hongwei Geng; Jun Yan; Pingzhi Zhang; Yingxiu Wan; Xianchun Xia (Theoretical and Applied Genetics, 2018)

Novel alternatively spliced isoforms of MEF2A and their mRNA expression patterns in pigs - Xiao Hong Guo; Qi Zhang; Meng Li; Peng Fei Gao; Guo Qing Cao; Zhi Min Cheng; Ning Fang Zhang; Bao Yu Le; Jian Feng Liu; Xiao Jun Liu; Bu Gao Li (Journal of Genetics, 2018)

Transcriptomic analysis and dynamic expression of genes reveal flavonoid synthesis in Scutellaria viscidula - Chengke Bai; Jun Xu; Bo Cao; Xia Li; Guishuang Li (Acta Physiologiae Plantarum, 2018)

De novo transcriptome assembly based on RNA-seq and dynamic expression of key enzyme genes in loganin biosynthetic pathway of Cornus officinalis - Chengke Bai; Yongmei Wu; Bo Cao; Jun Xu; Guishuang Li (Tree Genetics & Genomes, 2018)

Toxicity of seven insecticides to different developmental stages of the whitefly Bemisia tabaci MED (Hemiptera: Aleyrodidae) in multiple field populations of China - Jin-Cui Chen; Ze-Hua Wang; Li-Jun Cao; Ya-Jun Gong; Ary A. Hoffmann; Shu-Jun Wei (Ecotoxicology, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Efficacy of carbon dioxide treatments for the control of the two-spotted spider mite, Tetranychus urticae, and treatment impact on plant seedlings - Ya-Jun Gong; Li-Jun Cao; Ze-Hua Wang; Xiao-Yi Zhou; Jin-Cui Chen; Ary Anthony Hoffmann; Shu-Jun Wei (Experimental and Applied Acarology, 2018)

Phenotypic plasticity may help lizards cope with increasingly variable temperatures - Liang Ma; Bao-jun Sun; Peng Cao; Xing-han Li; Wei-guo Du (Oecologia, 2018)

Full genome sequence of the first bluetongue virus serotype 21 (BTV-21) isolated from China: evidence for genetic reassortment between BTV-21 and bluetongue virus serotype 16 (BTV-16) - Shaomin Qin; Heng Yang; Yixuan Zhang; Zhanhong Li; Jun Lin; Lin Gao; Defang Liao; Yingying Cao; Pengfei Ren; Huachun Li; Jianmin Wu (Archives of Virology, 2018)

Ecosystem assessment and protection effectiveness of a tropical rainforest region in Hainan Island, China - Jun Zhai; Peng Hou; Wei Cao; Min Yang; Mingyong Cai; Jing Li (Journal of Geographical Sciences, 2018)

Spectral Characteristics of Autofluorescence in Renal Tissue and Methods for Reducing Fluorescence Background in Confocal Laser Scanning Microscopy - Yang Zhang; Yang Wang; Wei-Wei Cao; Ke-Tao Ma; Wei Ji; Zi-Wei Han; Jun-Qiang Si; Li Li (Journal of Fluorescence, 2018)

Stochastic modeling for time series InSAR: with emphasis on atmospheric effects - Yunmeng Cao; Zhiwei Li; Jianchao Wei; Jun Hu; Meng Duan; Guangcai Feng (Journal of Geodesy, 2018)

Characteristics of polycyclic aromatic hydrocarbons in PM2.5 emitted from different cooking activities in China - Yun-Chun Li; Jia-Qian Qiu; Man Shu; Steven Sai Hang Ho; Jun-Ji Cao; Ge-Hui Wang; Xian-Xiang Wang; Xiao-Qing Zhao (Environmental Science and Pollution Research, 2018)

Minimally Toxic Dose of Lipopolysaccharide and α-Synuclein Oligomer Elicit Synergistic Dopaminergic Neurodegeneration: Role and Mechanism of Microglial NOX2 Activation - Wei Zhang; Jun-hua Gao; Zhao-fen Yan; Xi-yan Huang; Peng Guo; Li Sun; Zhuo Liu; Yang Hu; Li-jun Zuo; Shu-yang Yu; Chen-Jie Cao; Xiao-min Wang; et al. (Molecular Neurobiology, 2018)

L1CAM drives oncogenicity in esophageal squamous cell carcinoma by stimulation of ezrin transcription - Jin-Cheng Guo; Yang-Min Xie; Li-Qiang Ran; Hui-Hui Cao; Chun Sun; Jian-Yi Wu; Zhi-Yong Wu; Lian-Di Liao; Wei-Jiang Zhao; Wang-Kai Fang; En-Min Li; Li-Yan Xu; et al. (Journal of Molecular Medicine, 2017)

Comparative proteomics analysis of young spikes of wheat in response to Fusarium graminearum infection - Lina Ding; Ming Li; Peng Li; Jun Cao (Acta Physiologiae Plantarum, 2017)

Petrogenesis and geodynamic setting of the Triassic granitoid plutons in West Qinling, China: insights from LA-ICP-MS zircon U–Pb ages, Lu–Hf isotope signatures and geochemical characteristics of the Zhongchuan pluton - Shang-Song Yang; Jia-Jun Liu; Fangfang Zhang; Feng Yuan; De-Gao Zhai; Yu-Jie Li; Yanfu Liao; Qiang Cao (International Geology Review, 2017)

An analytical method for quantifying the correlation among slope failure modes in spatially variable soils - Dong Zheng; Dian-Qing Li; Zi-Jun Cao; Xiao-Song Tang; Kok-Kwang Phoon (Bulletin of Engineering Geology and the Environment, 2017)

Protodioscin ameliorates oxidative stress, inflammation and histology outcome in Complete Freund’s adjuvant induced arthritis rats - Jia-Yu Liu; Ya-Ling Hou; Rong Cao; Hong Xia Qiu; Guo-Hua Cheng; Ran Tu; Li Wang; Jun-Li Zhang; Dan Liu (Apoptosis, 2017)

Two new phenolic glycosides from the stem of Zanthoxylum armatum DC - Tao Guo; Li-Ping Dai; Xiao-Feng Tang; Tong-Tong Song; Ya Wang; Ai-Hong Zhao; Ying-Ying Cao; Jun Chang (Natural Product Research, 2017)

Mapping stripe rust resistance gene YrZH22 in Chinese wheat cultivar Zhoumai 22 by bulked segregant RNA-Seq (BSR-Seq) and comparative genomics analyses - Yong Wang; Jingzhong Xie; Huaizhi Zhang; Bingmin Guo; Shunzong Ning; Yongxing Chen; Ping Lu; Qiuhong Wu; Miaomiao Li; Deyun Zhang; Guanghao Guo; Yan Zhang; et al. (Theoretical and Applied Genetics, 2017)

Genome re-sequencing analysis uncovers pathogenecity-related genes undergoing positive selection in Magnaporthe oryzae - Jidong Cao; Yongqi Yu; Junkai Huang; Rui Liu; Yan Chen; Suiyan Li; Jun Liu (Science China Life Sciences, 2017)

Reliability-based robust geotechnical design using Monte Carlo simulation - Xing Peng; Dian-Qing Li; Zi-Jun Cao; Wenping Gong; C. Hsein Juang (Bulletin of Engineering Geology and the Environment, 2017)

Increases of Galectin-1 and its S-nitrosylated form in the Brain Tissues of Scrapie-Infected Rodent Models and Human Prion Diseases - Yan-Jun Guo; Qi Shi; Xiao-Dong Yang; Jian-Le Li; Yue Ma; Kang Xiao; Cao Chen; Jun Han; Xiao-Ping Dong (Molecular Neurobiology, 2017)

Puerarin may protect against Schwann cell damage induced by glucose fluctuation - Bing Xue; Lin Wang; Zhe Zhang; Rui Wang; Xin-xin Xia; Ping-ping Han; Li-jun Cao; Yong-hui Liu; Lian-qing Sun (Journal of Natural Medicines, 2017)

Cancer risk from gaseous carbonyl compounds in indoor environment generated from household coal combustion in Xuanwei, China - Ka-Hei Lui; Wen-Ting Dai; Chi-Sing Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Bei Wang; Jinwen Li; Jun-Ji Cao; Shun-Cheng Lee; Kin-Fai Ho (Environmental Science and Pollution Research, 2017)

Optimized monitoring sites for detection of biodiversity trends in China - Haigen Xu; Mingchang Cao; Yi Wu; Lei Cai; Yun Cao; Hui Ding; Peng Cui; Jun Wu; Zhi Wang; Zhifang Le; Xiaoqiang Lu; Li Liu; et al. (Biodiversity and Conservation, 2017)

Identification and Characterization of Chalcone Synthase Gene Family Members in Nicotiana tabacum - Shuai Chen; Xuhao Pan; Yiting Li; Lijie Cui; Yinchao Zhang; Zhiming Zhang; Guangtang Pan; Jun Yang; Peijian Cao; Aiguo Yang (Journal of Plant Growth Regulation, 2017)

Propofol attenuates H2O2-induced oxidative stress and apoptosis via the mitochondria- and ER-medicated pathways in neonatal rat cardiomyocytes - Xue-Ru Liu; Lu Cao; Tao Li; Lin-Lin Chen; Yi-Yan Yu; Wen-Jun Huang; Li Liu; Xiao-Qiu Tan (Apoptosis, 2017)

Elements in Fine Particulate Matter (PM $$_{2.5}$$ 2.5 ) from Indoor Air During Household Stoves Coal Combustion at Xuanwei, China - K. H. Lui; C. S. Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Jinwen Li; Jun-Ji Cao; S. C. Lee; K. F. Ho (Aerosol Science and Engineering, 2017)

U–Pb dating of zircon and cassiterite from the Early Cretaceous Jiaojiguan iron-tin polymetallic deposit, implications for magmatism and metallogeny of the Tengchong area, western Yunnan, China - Hua-Wen Cao; Yun-Hui Zhang; Qiu-Ming Pei; Rong-Qing Zhang; Li Tang; Bin Lin; Guo-Jun Cai (International Geology Review, 2017)

Proteomic Analyses for the Global S-Nitrosylated Proteins in the Brain Tissues of Different Human Prion Diseases - Li-Na Chen; Qi Shi; Bao-Yun Zhang; Xiao-Mei Zhang; Jing Wang; Kang Xiao; Yan Lv; Jing Sun; Xiao-Dong Yang; Cao Chen; Wei Zhou; Jun Han; et al. (Molecular Neurobiology, 2016)

A novel method for primary neuronal culture and characterization under different high temperature - Tao Zhang; Huaiqiang Hu; Zhen Tao; Bing Niu; Shusheng Jiao; Jun Zhang; Yiyang Li; Bingzhen Cao (In Vitro Cellular & Developmental Biology - Animal, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Transcriptome Sequencing of the Sweet Potato Progenitor (Ipomoea Trifida (H.B.K.) G. Don.) and Discovery of Drought Tolerance Genes - Qinghe Cao; Ang Li; Jinyang Chen; Yu Sun; Jun Tang; An Zhang; Zhilin Zhou; Donglan Zhao; Daifu Ma; Shan Gao (Tropical Plant Biology, 2016)

Purification, Chemical Characterization, and Bioactivity of an Extracellular Polysaccharide Produced by the Marine Sponge Endogenous Fungus Alternaria sp. SP-32 - Yin Chen; Wen-Jun Mao; Meng-Xia Yan; Xue Liu; Shu-Yao Wang; Zheng Xia; Bo Xiao; Su-Jian Cao; Bao-Qin Yang; Jie Li (Marine Biotechnology, 2016)

Development of microsatellite markers for the plant bug, Pachypeltis micranthus (Hemiptera: Miridae) - Jia-Ying Zhu; Sang-Zi Ze; Li-Jun Cao; Bin Yang (Applied Entomology and Zoology, 2016)

Enhancement of random finite element method in reliability analysis and risk assessment of soil slopes using Subset Simulation - Dian-Qing Li; Te Xiao; Zi-Jun Cao; Chuang-Bing Zhou; Li-Min Zhang (Landslides, 2016)

A critical role of LAMP-1 in avian reovirus P10 degradation associated with inhibition of apoptosis and virus release - Haiyang Wu; Zhiyuan He; Jun Tang; Xiaoqi Li; Hong Cao; Yongqiang Wang; Shijun J. Zheng (Archives of Virology, 2016)

Identification of putative phosphoproteins in wheat spikes induced by Fusarium graminearum - Lina Ding; Ruiying Yang; Guoxing Yang; Jun Cao; Peng Li; Yang Zhou (Planta, 2016)

Inhibition of Rac1 Activity in the Hippocampus Impairs the Forgetting of Contextual Fear Memory - Lizhu Jiang; Rongrong Mao; Qixin Zhou; Yuexiong Yang; Jun Cao; Yuqiang Ding; Yuan Yang; Xia Zhang; Lingjiang Li; Lin Xu (Molecular Neurobiology, 2016)

Deficient and excess dietary selenium levels affect growth performance, blood cells apoptosis and liver HSP70 expression in juvenile yellow catfish Pelteobagrus fulvidraco - Jun-Ru Hu; Yan-Hua Huang; Guo-Xia Wang; Ying-Xia Wu; Jian-An Xian; An-Li Wang; Jun-Ming Cao (Fish Physiology and Biochemistry, 2016)

Isolation, complete genome sequencing, and phylogenetic analysis of the first Chuzan virus in China - Fang Wang; Jun Lin; Jitao Chang; Yingying Cao; Shaomin Qin; Jianmin Wu; Li Yu (Virus Genes, 2016)

A Simple Fluorescence Probe Based on Aggregation-Induced Emission (AIE) Property for the Detection of Mg2+ Ions - Yan-Jiang Bian; Lu-Qiong Wang; Fu-Xiang Cao; Li-Jun Tang (Journal of Fluorescence, 2016)

Protective action of the phyllanthin against carbon tetrachloride-induced hepatocyte damage in Cyprinus carpio - Rui Jia; Jin-Liang Du; Li-Ping Cao; Ying-Juan Liu; Pao Xu; Guo-Jun Yin (In Vitro Cellular & Developmental Biology - Animal, 2016)

A Study of 2,3,7,8-Tetrachlorodibenzo-p-dioxin Induced Liver Injury in Jian Carp (Cyprinus carpio var. Jian) Using Precision-Cut Liver Slices - Jin-Liang Du; Li-Ping Cao; Ying-Juan Liu; Rui Jia; Guo-Jun Yin (Bulletin of Environmental Contamination and Toxicology, 2016)

Hsp70 plays an important role in high-fat diet induced gestational hyperglycemia in mice - Baoheng Xing; Lili Wang; Qin Li; Yalei Cao; Xiujuan Dong; Jun Liang; Xiaohua Wu (Journal of Physiology and Biochemistry, 2015)

QTL mapping for flowering time in different latitude in soybean - Sijia Lu; Ying Li; Jialin Wang; Peerasak Srinives; Haiyang Nan; Dong Cao; Yanping Wang; Jinliang Li; Xiaoming Li; Chao Fang; Xinyi Shi; Xiaohui Yuan; et al. (Euphytica, 2015)

Subchronic effects of cadmium on the gonads, expressions of steroid hormones and sex-related genes in tilapia Oreochromis niloticus - Yongju Luo; Dan Shan; Huan Zhong; Yi Zhou; Wenzhi Chen; Jinling Cao; Zhongbao Guo; Jun Xiao; Fulin He; Yifan Huang; Jian Li; Heming Huang; et al. (Ecotoxicology, 2015)

Rapid cloning and bioinformatic analysis of spinach Y chromosome-specific EST sequences - CHUAN-LIANG DENG; WEI-LI ZHANG; YING CAO; SHAO-JING WANG; SHU-FEN LI; WU-JUN GAO; LONG-DOU LU (Journal of Genetics, 2015)

Kocuria subflava sp. nov., isolated from marine sediment from the Indian Ocean - Zhao Jiang; Wei-Hua Zhang; Chang-Guo Yuan; Jia-Yang Chen; Li-Xiang Cao; Dong-Jin Park; Min Xiao; Chang-Jin Kim; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Effects of Graded Levels of Chromium Methionine on Performance, Carcass Traits, Meat Quality, Fatty Acid Profiles of Fat, Tissue Chromium Concentrations, and Antioxidant Status in Growing-Finishing Pigs - Yao-Yao Tian; Li-Min Gong; Jian-Xiang Xue; Jun Cao; Li-Ying Zhang (Biological Trace Element Research, 2015)

Downregulation of the lycopene ε-cyclase gene confers tolerance to salt and drought stress in Nicotiana tabacum - Yanmei Shi; Pingping Liu; Yuzhen Xia; Pan Wei; Wenzheng Li; Wei Zhang; Xia Chen; Peijian Cao; Yalong Xu; Lifeng Jin; Feng Li; Zhaopeng Luo; et al. (Acta Physiologiae Plantarum, 2015)

Effects of cold acclimation on sugar metabolism and sugar-related gene expression in tea plant during the winter season - Chuan Yue; Hong-Li Cao; Lu Wang; Yan-Hua Zhou; Yu-Ting Huang; Xin-Yuan Hao; Yu-Chun Wang; Bo Wang; Ya-Jun Yang; Xin-Chao Wang (Plant Molecular Biology, 2015)

Hepatoprotective and antioxidant effects of phyllanthin against carbon tetrachloride-induced liver injury in Cyprinus carpio - Rui Jia; Jin-Liang Du; Li-Ping Cao; Ying-Juan Liu; Pao Xu; Guo-Jun Yin (Aquaculture International, 2015)

Population genetic structure and approximate B ayesian computation analyses reveal the southern origin and northward dispersal of the oriental fruit moth G rapholita molesta ( L epidoptera: T ortricidae) in its native range - Shu‐Jun Wei; Li‐Jun Cao; Ya‐Jun Gong; Bao‐Cai Shi; Su Wang; Fan Zhang; Xiao‐Jun Guo; Yuan‐Min Wang; Xue‐Xin Chen (Molecular Ecology, 2015)
The oriental fruit moth ( OFM ) Grapholita molesta is one of the most destructive orchard pests. Assumed to be native to China, the moth is now distributed throughout the world. However, the evolutionary history of this moth in its native range remains unknown. In this study, we explored the population genetic structure, dispersal routes and demographic history of the OFM in China and South Korea based on mitochondrial genes and microsatellite loci. The Mantel test indicated a significant correlation between genetic distance and geographical distance in the populations. Bayesian analysis of population genetic structure ( baps ) identified four nested clusters, while the geneland analysis inferred five genetic groups with spatial discontinuities. Based on the approximate Bayesian computation approach, we found that the OFM was originated from southern China near the Shilin area of Yunnan Province. The early divergence and dispersal of this moth was dated to the Penultimate glaciation of Pleistocene. Further dispersal from southern to northern region of China occurred before the last glacial maximum, while the expansion of population size in the derived populations in northern region of China occurred after the last glacial maximum. Our results indicated that the current distribution and structure of the OFM were complicatedly influenced by climatic and geological events and human activities of cultivation and wide dissemination of peach in ancient China. We provide an example on revealing the origin and dispersal history of an agricultural pest insect in its native range as well as the underlying factors.

Diversity and space–time dynamics of endophytic archaea from sugar beet in the north slope of Tianshan Mountain revealed by 454 pyrosequencing and T-RFLP - YingWu Shi; MuSi TaPa; Chun Li; HongMei Yang; Tao Zhang; Yan Gao; Jian Sun; Jun Zeng; Qing Lin; ZhenHua Cao; KuEr OuTi; YuGuo Li; et al. (World Journal of Microbiology and Biotechnology, 2015)

Analysis of the sucrose synthase gene family in tobacco: structure, phylogeny, and expression patterns - Zhong Wang; Pan Wei; Mingzhu Wu; Yalong Xu; Feng Li; Zhaopeng Luo; Jianfeng Zhang; Ang Chen; Xiaodong Xie; Peijian Cao; Fucheng Lin; Jun Yang (Planta, 2015)

Complete genome sequence of a new recombinant echovirus 25 strain isolated from a neonatal patient with hand, foot, and mouth disease complicated by encephalitis in Beijing, China - Hongjie Li; Yixing Meng; Lin Pang; Jinqiu Liang; Hongping Lu; Qi Wang; Pu Liang; Jinfeng Cao; Shun-ai Liu; Jun Cheng (Virus Genes, 2015)

Petrogenesis of diabase from accretionary prism in the southern Q iangtang terrane, central T ibet: Evidence from U – P b geochronology, petrochemistry and Sr – Nd – Hf – O isotope characteristics - Jin‐Xiang Li; Ke‐Zhang Qin; Guang‐Ming Li; Jun‐Xing Zhao; Ming‐Jian Cao (Island Arc, 2015)
The B angong– N ujiang suture ( BNS ) between the L hasa and Q iangtang terranes is an important boundary and its petrogenesis is controversial. Diabase from the accretionary prism in the southern Q iangtang terrane yields a zircon U – Pb age of 181.3 ± 1.4 Ma. All the diabases show tholeiitic basalt compositions, gentle enrichment patters of light rare earth elements ( REE ), variable enrichment in incompatible element concentrations (e.g. Th and Rb ), and no anomaly in high field strength elements (e.g. Nb and Ta ), similar to that of enriched mid‐ocean ridge basalt ( E ‐ MORB ). They have relatively homogeneous whole rock Nd (ε Nd (t) = 7.3–9.1) and zircon Hf – O isotopic compositions (ε Hf (t) = 14.8–16.1, and δ 18 O = 4.57–6.12‰), possibly indicating melting of the depleted mantle and no significant crustal contamination during the petrogenesis. The element variations suggest that the diabases were formed by plume–ridge interaction at a mid‐ocean ridge within the B angong– N ujiang ocean.

Genes regulating lipid and protein metabolism are highly expressed in mammary gland of lactating dairy goats - Hengbo Shi; Jiangjiang Zhu; Jun Luo; Wenting Cao; Huaiping Shi; Dawei Yao; Jun Li; Yuting Sun; Huifen Xu; Kang Yu; Juan J. Loor (Functional & Integrative Genomics, 2015)

Omega-3 Fatty Acids and Primary and Secondary Prevention of Cardiovascular Disease - Yong Cao; Lei Lu; Jun Liang; Min Liu; Xianchi Li; RongRong Sun; Yi Zheng; Peiying Zhang (Cell Biochemistry and Biophysics, 2015)

Association mapping of salinity and alkalinity tolerance in improved japonica rice (Oryza sativa L. subsp. japonica Kato) germplasm - Di Cui; Chang-ying Xu; Chun-gang Yang; Qi-xing Zhang; Jun-guo Zhang; Xiao-ding Ma; Yong-li Qiao; Gui-lan Cao; San-yuan Zhang; Long-zhi Han (Genetic Resources and Crop Evolution, 2015)

Identification and phylogenetic analysis of late embryogenesis abundant proteins family in tomato (Solanum lycopersicum) - Jun Cao; Xiang Li (Planta, 2015)

Effective identification and localization of immature precursors in bone marrow biopsy - Guitao Cao; Ling Li; Weiting Chen; Yehua Yu; Jun Shi; Guixu Zhang; Xuehua Liu (Medical & Biological Engineering & Computing, 2015)

Isolation and characterization of pyrroline-5-carboxylate synthetase gene from perennial ryegrass (Lolium perenne L.) - Li Cao; Lei Han; Hua-li Zhang; Hai-bo Xin; Muhammad Imtiaz; Ming-Fang Yi; Zhen-Yuan Sun; Guan-Sheng Ju; Yong-Qiang Qian; Jun-Xiang Liu (Acta Physiologiae Plantarum, 2015)

Proteins involved in nodulation competitiveness of two Bradyrhizobium diazoefficiens strains induced by soybean root exudates - Yao Liu; Dawei Guan; Xin Jiang; Mingchao Ma; Li Li; Fengming Cao; Huijun Chen; Delong Shen; Jun Li (Biology and Fertility of Soils, 2015)

E2F1 regulates p53R2 gene expression in p53-deficient cells - Jun-Juan Qi; Ling Liu; Ji-Xiang Cao; Guo-Shun An; Shu-Yan Li; Gang Li; Hong-Ti Jia; Ju-Hua Ni (Molecular and Cellular Biochemistry, 2015)

Isoflurane Protects Against Injury Caused by Deprivation of Oxygen and Glucose in Microglia Through Regulation of the Toll-Like Receptor 4 Pathway - Hai-Fei Xiang; Dong-Hang Cao; Yan-Qing Yang; Hui-Qin Wang; Li-Jun Zhu; Bin-Hao Ruan; Jing Du; Ming-Cang Wang (Journal of Molecular Neuroscience, 2014)

Effects of Chromium Methionine Supplementation on Growth Performance, Serum Metabolites, Endocrine Parameters, Antioxidant Status, and Immune Traits in Growing Pigs - Yao-Yao Tian; Li-Ying Zhang; Bing Dong; Jun Cao; Jian-Xiang Xue; Li-Min Gong (Biological Trace Element Research, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Preliminary analysis of spatiotemporal pattern of global land surface water - Xin Cao; Jun Chen; LiJun Chen; AnPing Liao; FangDi Sun; Yang Li; Lei Li; ZhongHui Lin; ZhiGuo Pang; Jin Chen; ChaoYing He; Shu Peng (Science China Earth Sciences, 2014)

Glial Cell-Derived Neurotrophic Factor Attenuates Neuropathic Pain in a Mouse Model of Chronic Constriction Injury: Possible Involvement of E-cadherin/p120ctn Signaling - Cunjin Wang; Hongjun Wang; Jun Pang; Li Li; Suming Zhang; Ge Song; Na Li; Junping Cao; Licai Zhang (Journal of Molecular Neuroscience, 2014)

A novel method for determining the anisotropy of geophysical parameters: unit range variation increment (URVI) - Yun-Meng Cao; Zhi-Wei Li; Jian-Chao Wei; Wen-Jun Zhan; Jian-Jun Zhu; Chang-Cheng Wang (Applied Geophysics, 2014)

Fine mapping of a dominant thermo-sensitive genic male sterility gene (BntsMs) in rapeseed (Brassica napus) with AFLP- and Brassica rapa-derived PCR markers - Xinhua Zeng; Wenpin Li; Yuhuan Wu; Fang Liu; Junling Luo; Yinglong Cao; Li Zhu; Yunjing Li; Jun Li; Qingbo You; Gang Wu (Theoretical and Applied Genetics, 2014)

The changes of renewable water resources in China during 1956–2010 - YuanYuan Li; JianTing Cao; FuXin Shen; Jun Xia (Science China Earth Sciences, 2014)

The colonization patterns of different fungi on roots of Cymbidium hybridum plantlets and their respective inoculation effects on growth and nutrient uptake of orchid plantlets - Xiao-Lan Zhao; Jing-Ze Yang; Shu Liu; Chun-Li Chen; Hai-Yan Zhu; Jun-Xi Cao (World Journal of Microbiology and Biotechnology, 2014)

Analysis of synonymous codon usage in enterovirus 71 - Hua Zhang; Hong-wei Cao; Feng-qi Li; Zi-ye Pan; Zhi-jun Wu; Yan-hong Wang; Yu-dong Cui (VirusDisease, 2014)

Role and Mechanism of Microglial Activation in Iron-Induced Selective and Progressive Dopaminergic Neurodegeneration - Wei Zhang; Zhao-fen Yan; Jun-hua Gao; Li Sun; Xi-yan Huang; Zhuo Liu; Shu-yang Yu; Chen-Jie Cao; Li-jun Zuo; Ze-Jie Chen; Yang Hu; Fang Wang; et al. (Molecular Neurobiology, 2014)

Interval Q inversion based on zero-offset VSP data and applications - Gu-Lan Zhang; Xi-Ming Wang; Zhen-Hua He; Jun-Xing Cao; Ke-En Li; Jiao-Jun Rong (Applied Geophysics, 2014)

Silencing MAP3K1 expression through RNA interference enhances paclitaxel-induced cell cycle arrest in human breast cancer cells - Pinghua Hu; Qin Huang; Zhihua Li; Xiaobo Wu; Qianwen Ouyang; Jun Chen; Yali Cao (Molecular Biology Reports, 2014)

Up-regulating Blood Brain Barrier Permeability of Nanoparticles via Multivalent Effect - Xihui Gao; Jun Qian; Shuyan Zheng; Ying Xiong; Jiahao Man; Binxin Cao; Lu Wang; Shenghong Ju; Cong Li (Pharmaceutical Research, 2013)

Comparative Analysis of Gene Expression Profiles Between Cortex and Thalamus in Chinese Fatal Familial Insomnia Patients - Chan Tian; Di Liu; Qing-Lan Sun; Chen Chen; Yin Xu; Hui Wang; Wei Xiang; Hans A Kretzschmar; Wei Li; Cao Chen; Qi Shi; Chen Gao; et al. (Molecular Neurobiology, 2013)

Microdissection and painting of the Y chromosome in spinach (Spinacia oleracea) - Chuan-liang Deng; Rui-yun Qin; Ying Cao; Jun Gao; Shu-fen Li; Wu-jun Gao; Long-dou Lu (Journal of Plant Research, 2013)

Neurotoxicity and Reactive Astrogliosis in the Anterior Cingulate Cortex in Acute Ciguatera Poisoning - Xu Zhang; Bing Cao; Jun Wang; Jin Liu; Vivian Oi Vian Tung; Paul Kwan Sing Lam; Leo Lai Chan; Ying Li (NeuroMolecular Medicine, 2013)

Evaluation of Burma Reed as Substrate for Production of Pleurotus eryngii - Xian-lu Zeng; Jun-fang Lin; Li-qiong Guo; Rong-wei Cao; Wei-qiang Zeng (Indian Journal of Microbiology, 2013)

Temperature and precipitation variations at two meteorological stations on eastern slope of Gongga Mountain, SW China in the past two decades - Yan-hong Wu; Wei Li; Jun Zhou; Yang Cao (Journal of Mountain Science, 2013)

Two new diterpenes from Caesalpinia minax Hance - Guo-Xu Ma; Jing-Quan Yuan; Li Cao; Jun-Shan Yang; Xu-Dong Xu (Natural Product Research, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Involvement of ZEB1 and E-cadherin in the invasion of lung squamous cell carcinoma - Jiaxing Zhang; Chenhui Lu; Jun Zhang; Jiuhong Kang; Chuanwu Cao; Maoquan Li (Molecular Biology Reports, 2013)

Exon 47 skipping of fibrillin-1 leads preferentially to cardiovascular defects in patients with thoracic aortic aneurysms and dissections - Wen-Jing Wang; Peili Han; Jun Zheng; Fang-Yuan Hu; Yun Zhu; Jin-Sheng Xie; Jian Guo; Zhe Zhang; Jie Dong; Gu-Yan Zheng; Huiqing Cao; Tian-Shu Liu; et al. (Journal of Molecular Medicine, 2013)

Beraprost sodium attenuates cigarette smoke extract-induced apoptosis in vascular endothelial cells - Yan Chen; Hong Luo; Naixin Kang; Chaxiang Guan; Yingjiao Long; Jun Cao; Qin Shen; Junli Li; Min Yang; Hong Peng; Ping Chen (Molecular Biology Reports, 2012)

Synthesis and antihypertensive activity evaluation in spontaneously hypertensive rats of lacidipine analogues - Zeng-jun Guo; Kai Zhou; Yong-xiao Cao; Yan Li; San-qi Zhang (Medicinal Chemistry Research, 2012)

Urban transformation of a metropolis and its environmental impacts - Zhan Tian; Guiying Cao; Jun Shi; Ian McCallum; Linli Cui; Dongli Fan; Xinhu Li (Environmental Science and Pollution Research, 2012)

VEGF is essential for the growth and migration of human hepatocellular carcinoma cells - Lei Zhang; Jia-Ning Wang; Jun-Ming Tang; Xia Kong; Jian-Ye Yang; Fei Zheng; Ling-Yun Guo; Yong-Zhang Huang; Li Zhang; Lin Tian; Shu-Fen Cao; Chang-Hai Tuo; et al. (Molecular Biology Reports, 2012)

Apolipoprotein A-I mimetic peptide D-4F promotes human endothelial progenitor cell proliferation, migration, adhesion though eNOS/NO pathway - Zhengang Zhang; Jianhua Qun; Chunmei Cao; Jun Wang; Wei Li; Yong Wu; Lin Du; Pei Zhao; Kaizheng Gong (Molecular Biology Reports, 2012)

Update analysis of studies on the MMP-9 −1562 C>T polymorphism and cancer risk - Li-Feng Zhang; Yuan-Yuan Mi; Qiang Cao; Wei Wang; Chao Qin; Jun-Feng Wei; Yao-Jun Zhou; Yong-Fei Li; Min Tang; Wei-Min Liu; Wei Zhang; Jian-Gang Zou (Molecular Biology Reports, 2012)

Polymorphisms in chicken extracellular fatty acid binding protein gene - Zhi-yuan Zhao; Li Zhang; Bing-wang Du; Ning-xian Cao; Xin-sheng Jiang; Wen-xia Tian; Shu-jun Li; Wei-wei Wu; Chang-hui Ye (Molecular Biology Reports, 2012)

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Rare earth element geochemistry of hydrothermal deposits from Southwest Indian Ridge - Zhimin Cao; Hong Cao; Chunhui Tao; Jun Li; Zenghui Yu; Liping Shu (Acta Oceanologica Sinica, 2012)

Effect of long-term administration of dietary β-1,3-glucan on growth, physiological, and immune responses in Litopenaeus vannamei (Boone, 1931) - Hong-Xia Zhao; Jun-Ming Cao; An-Li Wang; Zhen-Yu Du; Chao-Xia Ye; Yan-Hua Huang; Han-Bing Lan; Ting-Ting Zhou; Guo-Li Li (Aquaculture International, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Phylogenic analysis of Chinese Leishmania isolates based on small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA) - Wang Guan; De-Ping Cao; Ke sun; Jia-nan Xu; Jun-rong Zhang; Da-Li Chen; Jian-Ping Chen (Acta Parasitologica, 2012)
The leishmaniases are zoonotic diseases caused by protozoan parasites of the genus Leishmania. Leishmaniases are still endemic in China, especially in the west and northwest froniter regions. To revalue the preliminary phylogenetic results of Chinese Leishmania isolates, we amplified partial fragment of small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA), then tested the phylogenetic relationships among Chinese Leishmania isolates and their relatives by analyzing SSU rRNA gene sequences and 7SL RNA gene sequences. 19 SSU RNA sequences and 9 7SL RNA sequences were obtained in our study, then analyzed with 42 SSU RNA sequences and 32 7SL RNA sequences retrieved from Genbank, respectively. In the Bayesian analysis of the SSU RNA gene, the isolate MHOM/CN/93/GS7 and the isolate IPHL/CN/77/XJ771 are members of Leishmania donovani complex, while the isolate MHOM/CN/84/JS1 clustered with Leishmania tropica. The other 11 Chinese Leishmania isolates (MHOM/CN/90/WC, MCAN/CN/90/SC11, MHOM/CN/80/XJ801, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/ 89/GS5) form an unclassified group, defined as Leishmania sp., and the most relative species to this group is L. tarentolae. In the Bayesian analysis of the 7SL RNA gene, 9 Chinese Leishmania isolates also formed an unclassified group with L. tarentolae, including canine isolate 10, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/ CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/89/GS5. We concluded that: (1) Chinese Leishmania isolates are non-monophyly group; (2) an unclassified group may exist in China, and the most relative species to this group is L. tarentolae; (3) MHOM/CN/84/JS1, which was previously assigned as L. donovani, was most genetically related to L. tropica strain MHOM/SU/74/K27.

RNASEL −1385G/A polymorphism and cancer risk: a meta-analysis based on 21 case–control studies - Li-Feng Zhang; Yuan-Yuan Mi; Chao Qin; Yong Wang; Qiang Cao; Jun-Feng Wei; Yao-Jun Zhou; Ning-Han Feng; Wei Zhang (Molecular Biology Reports, 2011)

Induction of DIMBOA accumulation and systemic defense responses as a mechanism of enhanced resistance of mycorrhizal corn (Zea mays L.) to sheath blight - Yuan Yuan Song; Man Cao; Li Jun Xie; Xiao Ting Liang; Ren Sen Zeng; Yi Juan Su; Jing Hua Huang; Rui Long Wang; Shi Ming Luo (Mycorrhiza, 2011)

Physical and Mechanical Properties of Fine-Grained Soil in the Zhejiang-Fujian Coastal Area, China - Yuan-Qin Xu; Pei-Ying Li; Ping Li; Le-Jun Liu; Cheng-Xiao Cao; Xiu-Li Feng (Marine Georesources & Geotechnology, 2011)

A Novel PrP Partner HS-1 Associated Protein X-1 (HAX-1) Protected the Cultured Cells Against the Challenge of H2O2 - Yuan-Yuan Jing; Xiao-Li Li; Qi Shi; Zhao-Yun Wang; Yan Guo; Ming-Ming Pan; Chan Tian; Shu-Ying Zhu; Cao Chen; Han-Shi Gong; Jun Han; Chen Gao; et al. (Journal of Molecular Neuroscience, 2011)

Microsatellite Analysis of Homozygosity Progression of Heterozygous Genotypes Segregating in the Rice Subspecies Cross Pei’ai64s/Nipponbare - Yong-shu Liang; Qi-jun Zhang; Shi-quan Wang; Li-yong Cao; Zhi-qiang Gao; Ping Li; Shi-hua Cheng (Biochemical Genetics, 2011)

Activated Immune Cells in Parkinson's Disease - Jun-Jun Cao; Kang-Sheng Li; Yan-Qin Shen (Journal of Neuroimmune Pharmacology, 2011)

shRNA targeting SFRP2 promotes the apoptosis of hypertrophic scar fibroblast - Zhicheng Sun; Shirong Li; Chuan Cao; Jun Wu; Bing Ma; Vu Tran (Molecular and Cellular Biochemistry, 2011)

Pseudonocardia sichuanensis sp. nov., a novel endophytic actinomycete isolated from the root of Jatropha curcas L. - Sheng Qin; Ke Xing; Shi-Min Fei; Qiang Lin; Xiu-Min Chen; Cheng-Liang Cao; Yong Sun; Yun Wang; Wen-Jun Li; Ji-Hong Jiang (Antonie van Leeuwenhoek, 2011)

A mutant of infectious Asia 1 serotype foot-and-mouth disease virus with the deletion of 10-amino-acid in the 3A protein - Shuang Li; Mingchun Gao; Runxiang Zhang; Ge Song; Jun Song; Dandan Liu; Yongsheng Cao; Tingting Li; Bo Ma; Xiangtao Liu; Junwei Wang (Virus Genes, 2010)

Amino acid sequence analysis and identification of mutations under positive selection in hemagglutinin of 2009 influenza A (H1N1) isolates - Xiaofan Ding; Lifang Jiang; Changwen Ke; Zhan Yang; Chunliang Lei; Kaiyuan Cao; Jun Xu; Lin Xu; Xingfen Yang; Yonghui Zhang; Ping Huang; Weijun Huang; et al. (Virus Genes, 2010)

Isolation and identification of a phosphate-solubilizing bacterium Pantoea stewartii subsp. stewartii g6, and effects of temperature, salinity, and pH on its growth under indoor culture conditions - Xiao-Juan Hu; Zhuo-Jia Li; Yu-Cheng Cao; Jun Zhang; Ying-Xue Gong; Yu-Feng Yang (Aquaculture International, 2010)

Effects of Reactive Oxygen Species Metabolic System on Soybean (Glycine max) Under Exogenous Chitosan to Ozone Stress - Tian Hong Zhao; Jun Li Wang; Yan Wang; Jia Wei Sun; Ying Cao (Bulletin of Environmental Contamination and Toxicology, 2010)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Neural circuits and temporal plasticity in hindlimb representation of rat primary somatosensory cortex: revisited by multi-electrode array on brain slices - Dan-Dan Wang; Zhen Li; Ying Chang; Rui-Rui Wang; Xue-Feng Chen; Zhen-Yu Zhao; Fa-Le Cao; Jian-Hui Jin; Ming-Gang Liu; Jun Chen (Neuroscience Bulletin, 2010)

A Multiresidue Method for 20 Pesticides in Radix paeoniae Alba of Chinese Herb by Gas Chromatography with Electron-capture Detection - Gao Qian; Hua Rimao; Tang Feng; Wu Xiangwei; Li Xuede; Cao Haiqun; Shi Yanhong; Tang Jun (Bulletin of Environmental Contamination and Toxicology, 2010)

The polymorphisms of UCP1 genes associated with fat metabolism, obesity and diabetes - Jun-jing Jia; Yun-bo Tian; Zhen-hui Cao; Lin-li Tao; Xi Zhang; Si-zhen Gao; Chang-rong Ge; Qiu-Ye Lin; M. Jois (Molecular Biology Reports, 2010)

Effects of moniliformin and selenium on human articular cartilage metabolism and their potential relationships to the pathogenesis of Kashin-Beck disease - An Zhang; Jun-ling Cao; Bo Yang; Jing-hong Chen; Zeng-tie Zhang; Si-yuan Li; Qiang Fu; Clare E. Hugnes; Bruce Caterson (Journal of Zhejiang University-SCIENCE B, 2010)

Porphyrin and Galactosyl Conjugated Micelles for Targeting Photodynamic Therapy - De-Qun Wu; Ze-Yong Li; Cao Li; Jian-Jun Fan; Bo Lu; Cong Chang; Si-Xue Cheng; Xian-Zheng Zhang; Ren-Xi Zhuo (Pharmaceutical Research, 2010)

Manganese-induced changes of the biochemical characteristics of the recombinant wild-type and mutant PrPs - Xiao-Li Li; Chen-Fang Dong; Gui-Rong Wang; Rui-Min Zhou; Qi Shi; Chan Tian; Chen Gao; Guo-Yong Mei; Cao Chen; Kun Xu; Jun Han; Xiao-Ping Dong (Medical Microbiology and Immunology, 2009)

Identification and Expression Pattern of a Novel NAM, ATAF, and CUC-Like Gene from Citrus sinensis Osbeck - Yong-Zhong Liu; M. N. R. Baig; Rui Fan; Jun-Li Ye; Yin-Chuan Cao; Xiu-Xin Deng (Plant Molecular Biology Reporter, 2009)

Independence of stem and leaf hydraulic traits in six Euphorbiaceae tree species with contrasting leaf phenology - Jun-Wen Chen; Qiang Zhang; Xiao-Shuang Li; Kun-Fang Cao (Planta, 2009)

Phase I clinical trial on intracoronary administration of Ad-hHGF treating severe coronary artery disease - Zhi-Jian Yang; You-Rong Zhang; Bo Chen; Shu-Lan Zhang; En-Zhi Jia; Lian-Sheng Wang; Tie-Bing Zhu; Chun-Jian Li; Hui Wang; Jun Huang; Ke-Jiang Cao; Wen-Zhu Ma; et al. (Molecular Biology Reports, 2009)

Ectopic overexpression of AtHDG11 in tall fescue resulted in enhanced tolerance to drought and salt stress - Ya-Jun Cao; Qiang Wei; Yang Liao; He-Ling Song; Xian Li; Cheng-Bin Xiang; Ben-Ke Kuai (Plant Cell Reports, 2009)

Molecular mutations associated with the in vitro passage of virulent porcine reproductive and respiratory syndrome virus - Wei Han; Jia-Jun Wu; Xiao-Yu Deng; Zhen Cao; Xiu-ling Yu; Chuan-Bin Wang; Tie-Zhu Zhao; Nan-Hua Chen; Hong-Hui Hu; Wang Bin; Li-Li Hou; Li-Lin Wang; et al. (Virus Genes, 2009)

Physiological Stress of High NH 4 + Concentration in Water Column on the Submersed Macrophyte Vallisneria Natans L. - Te Cao; Ping Xie; Zhongqiang Li; Leyi Ni; Meng Zhang; Jun Xu (Bulletin of Environmental Contamination and Toxicology, 2009)

Association of the mutation for the human carboxypeptidase E gene exon 4 with the severity of coronary artery atherosclerosis - En-Zhi Jia; Jie Wang; Zhi-Jian Yang; Tie-Bing Zhu; Lian-Sheng Wang; Hui Wang; Chun-Jian Li; BO Chen; Ke-Jiang Cao; Jun Huang; Wen-Zhu Ma (Molecular Biology Reports, 2009)

Identification of QTLs for the resistance to rice stripe virus in the indica rice variety Dular - Shu-Jun Wu; Huan Zhong; Yong Zhou; Hui Zuo; Li-Hui Zhou; Jin-Yan Zhu; Cao-Qiu Ji; Shi-Liang Gu; Ming-Hong Gu; Guo-Hua Liang (Euphytica, 2009)

Promotion of the articular cartilage proteoglycan degradation by T-2 toxin and selenium protective effect - Si-yuan Li; Jun-ling Cao; Zhong-li Shi; Jing-hong Chen; Zeng-tie Zhang; Clare E. Hughes; Bruce Caterson (Journal of Zhejiang University-SCIENCE B, 2008)

The selective 5-HT1A receptor antagonist WAY-100635 inhibits neuronal activity of the ventromedial prefrontal cortex in a rodent model of Parkinson’s disease - Jian Cao; Jian Liu; Qiao-Jun Zhang; Tao Wang; Shuang Wang; Ling-Na Han; Qiang Li (Neuroscience Bulletin, 2007)

Role of P-glycoprotein in Limiting the Brain Penetration of Glabridin, An Active Isoflavan from the Root of Glycyrrhiza glabra - Xi-Yong Yu; Shu-Guang Lin; Zhi-Wei Zhou; Xiao Chen; Jun Liang; Xue-Qing Yu; Balram Chowbay; Jing-Yuan Wen; Wei Duan; Eli Chan; Xiao-Tian Li; Jie Cao; et al. (Pharmaceutical Research, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

A Male Reproduction-Related Kazal-Type Peptidase Inhibitor Gene in the Prawn, Macrobrachium rosenbergii: Molecular Characterization and Expression Patterns - Jun-Xia Cao; Jie-Qiong Dai; Zhong-Min Dai; Guo-Li Yin; Wei-Jun Yang (Marine Biotechnology, 2007)

The influence of feeding rate on growth, feed efficiency and body composition of juvenile grass carp (Ctenopharyngodon idella) - Zhen-Yu Du; Yong-Jian Liu; Li-Xia Tian; Jian-Guo He; Jun-Ming Cao; Gui-Ying Liang (Aquaculture International, 2006)

Species diversity of Lachnum (Helotiales, Hyaloscyphaceae) from temperate China - Ming Ye; Shu-qing Cao; Shao-tong Jiang; Li-jun Pan; Shui-zhong Luo; Xing-jiang Li (Journal of Zhejiang University-SCIENCE B, 2006)

Gene expression profiling in rice young panicle and vegetative organs and identification of panicle-specific genes through known gene functions - Jiabin Tang; Hong’ai Xia; Dayong Li; Mengliang Cao; Yong Tao; Wei Tong; Xiuqing Zhang; Songnian Hu; Jian Wang; Jun Yu; Huanming Yang; Lihuang Zhu (Molecular Genetics and Genomics, 2005)

Environmental geography in China: retrospect and prospect - Tao Shu; Wang Xuejun; Hu Jianying; Xu Fuliu; Liu Wenxin; Li Bengang; Cao Jun (Journal of Geographical Sciences, 2004)

A method for lake ecosystem health assessment: an Ecological Modeling Method (EMM) and its application - Fu-Liu Xu; Richard W. Dawson; Shu Tao; Jun Cao; Ben-Gang Li (Hydrobiologia, 2001)